School-based professional development in a developing context: Lessons learnt from a case study in Zambia - Haßler, Björn; Hennessy, S.; Cross, A. (Professional Development in Education, 2014)
This paper reports on the development and outcomes of the second phase of OER4Schools, a school-based professional development programme supporting interactive forms of subject teaching in conjunction with Open Educational Resources (OER) and technology in Zambian primary schools. We worked with partners to identify the needs of school-based continuing professional development adapted to the local context; the programme was based on participatory, collaborative and inquiry-based pedagogies for both classroom learning and teacher development. We worked over a one-year period with four experienced teachers in two basic (primary) schools serving disadvantaged communities. Data were collected from observations, interviews, surveys, lesson planning/review meetings and team workshops. All participants integrated OER and technology into mathematics and science lessons and developed more interactive practices, including collaborative learning. Professional dialogue, quality conversations, reflective practice, cultural sensitivity, peer learning and cooperation were pivotal mechanisms through which teachers shifted their focus from teaching (and teacher exposition) to student learning. Seeing students as capable individuals, teachers raised their expectations and developed insight into interactive practices such as group work, providing meaningful opportunities for student collaboration and active learning by all.
00015 EdTechHub.Source: 2129771:7RVZCL3K shortDOI: 10/gfv5xw KerkoCite.ItemAlsoKnownAs: 10.1080/19415257.2014.938355 10/gfv5xw 2129771:7RVZCL3K 2339240:6HHB3GBE 2405685:3RWNJGGM 2405685:72I5EQTH 2405685:RUTXQFGV
Keywords: Author:Haßler; Open Educational Resources; Zambia; digital technology; dode_eth-src-dode; dode_eth-trf2-dode; interactive pedagogy; reflective practice; school-based professional development; sub-Saharan Africa

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
00000 EdTechHub.Source: 2129771:D2GQYC5S KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v5i1.264 2129771:43ZT3XWL 2129771:52KKAHKR 2129771:AAT7FR3H 2129771:D2GQYC5S 2129771:LDWSNI7T 2129771:LHMXV7QF 2249382:CS9PALG8 2317526:6IH7CD39 2317526:PP4CHVEG 2339240:2BCABLG6 2339240:4N3G4XDJ 2339240:9BPXVI62 2339240:C7CKIPL7 2339240:D83N6FTA 2339240:HGHAYJ5G 2339240:HR2YGWX3 2339240:P65I7MGU 2339240:YSVITTWH 2405685:3GSCKVWC 2405685:7X2D9JDG 2405685:CUHYHFLV 2405685:M8UDHT7A 2405685:NKSYKNQN 2405685:NVEVT9HX 2405685:NZ3GKZCR 2405685:T2I86FZT 2405685:ZFJ79LQS 2486141:Z3PRLX4K 257089:AJJPQKDF 261451:JC3NQMN3 261495:BWD9L8FL 261495:TCP47GGI
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

Dual-mode teacher professional development: challenges and re-visioning future TPD in Indonesia - Widodo, Ari; Riandi (Teacher Development, 2013)
This paper presents the results of a two-year research project aimed at developing a teacher professional development (TPD) model in Indonesia. New government policies in this nation, its archipelagic nature, vast numbers of teachers and scarcity of support resources present a unique challenge to TPD. A needs assessment was conducted to identify teachers’ professional needs. Based on the results of this assessment, a dual-mode TPD that combines face-to-face sessions and online sessions was developed. Participation in face-to-face sessions was relatively high but the participation rate in online sessions was very low. Incentives, teachers’ autonomy as professional learners, ICT skills and infrastructure are important considerations when designing TPD in Indonesia. This study and an analysis of TPD policy allow us to suggest future directions for TPD in Indonesia
Place: United Kingdom Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.ebscohost.com/login.aspx?direct=true&db=bri&AN=BEI.221367&site=ehost-live&scope=site KerkoCite.ItemAlsoKnownAs: 10.1080/13664530.2013.813757 2339240:CB38DZV3 2339240:QP2WUG5A 2405685:M5WDVH5K 2405685:REGZ6H9H 2405685:T4TMJ4LR 2534378:9P4LRFZC 2534378:BR8DXZB4 2534378:UHSPASDV 2534378:Z8BCLDYY
Keywords: CONTINUING education; EDUCATION & state; EDUCATION – Forecasting; ERIC; Current Index to Journals in Education (CIJE); Education–Teaching Methods And Curriculum; Educational Change; Educational Strategies; Elementary Secondary Education; FORECASTING; Faculty Development; Foreign Countries; HIGHER education; Higher Education; INDONESIA; Indonesia; Information Skills; Instructional Design; Interviews; Models; Needs Assessment; Online instruction; PROFESSIONAL education; Pedagogical Content Knowledge; Postsecondary Education; Professional development; Public policy; Questionnaires; Science Teachers; TEACHER certification; TEACHER development; TEACHER education; Teacher Education; Teacher education; __:import:01; __:match:final; __:matched; __:study_id:2097039; ___working_potential_duplicate; __finaldtb; dual-mode professional development; online training; teacher certification; teacher education; teacher education futures; teacher professional development in Indonesia

Evaluating the impact of teacher professional development: an evidence-based framework - King, Fiona (Professional Development in Education, 2014)
shortDOI: 10/gfw2mh KerkoCite.ItemAlsoKnownAs: 10.1080/19415257.2013.823099 10/gfw2mh 2405685:EUPCICWT
Keywords: C:Ireland

School-based professional development in one Lebanese school: how much is too much? - Nabhani, Mona; Bahous, Rima; Hamdan, Zeina (Professional Development in Education, 2012)
This case study examines the attitudes of the secondary and middle school teachers at one school in Lebanon regarding the effect of the school’s professional development (PD) programs on the quality of their teaching practices and motivation. It also examines teachers’ attitudes regarding PD as well as their recommendations to improve the quality of the PD program provided by their school. Questionnaires, focus group interviews and observations were conducted to collect and triangulate data results. Results show that teachers regard PD in their school as beneficial in general but able to be enhanced further. Although the attitude of novice teachers towards PD is more favorable than that of veteran teachers, findings show that the overall teachers’ attitude towards PD is a negative one. Modifications and suggestions to improve the quality of the PD activities are proposed by the teachers. The school offers a prosperous PD program, but its fruitfulness will remain limited unless an organizational structure is created.
shortDOI: 10/fzxm7p KerkoCite.ItemAlsoKnownAs: 10.1080/19415257.2011.639077 10/fzxm7p 2339240:9WFGU8AX 2339240:WLWXRWJ2 2405685:DMXQEDYG 2405685:I8KIIXIE
Keywords: Lebanon; professional development; schools; ⛔ No DOI found

Teachers’ professional development through the English in Action Secondary Teaching and Learning Programme in Bangladesh: experience from the UCEP schools - Shohel, M. Maruf C; Banks, Frank (Procedia-Social and Behavioral Sciences, 2010)
This paper explores the English in Action (EIA) intervention in Bangladesh and explores how the school-based support systems impact on classroom practice in Underprivileged Children’s Educational Programs (UCEP) Schools. It presents evidence to demonstrate how in-school training helps teachers’ professional development (TDP). This paper explores TPD by analysing interviews with UCEP school administrators and teachers who are participating in the pre-pilot EIA intervention. It draws a conclusion that school-based support systems combined with technology enhanced open and distance learning (ODL) are contributing significantly to TPD as an in-service training
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.sbspro.2010.03.894 2339240:WE7Z36DR 2405685:VDJRNRTI 2534378:A22MYIWP 2534378:HS2WT9YY 2534378:Q2THK4LH
Keywords: EiA Intervention; Experiential Learning; Secondary Teaching and Learning Programme; Teachers’ Professional Development; UCEP-Bangladesh; __:import:01; __:match:final; __:matched; __:study_id:2457264; __finaldtb

School-based teachers’ professional development through technology-enhanced learning in Bangladesh - Shohel, M. Mahruf C.; Banks, Frank (Teacher Development, 2012)
To promote significant pedagogical change, the most successful teacher education programmes for the global south happen in the school context. This paper is based on a pre-pilot intervention study of an international education development programme in Bangladesh. Technology-enhanced learning, in this case the use of the Apple® iPod® (iPod touch®), was used to support teachers’ teaching and learning in their school contexts. This paper presents evidence to demonstrate how such school-based technology-enhanced support systems impact on classroom practice and help teachers’ professional development. Using the case of a pre-pilot intervention in the Underprivileged Children’s Educational Programs schools, it explores the teachers’ professional development by analysing interviews with the teachers who were participating in the pre-pilot intervention programme, and draws the conclusion from the collected data that school-based teachers’ professional development through technology-enhanced learning is contributing significantly to in-service training in a resource-constrained context.
Publisher: Routledge _eprint: https://doi.org/10.1080/13664530.2012.668103 KerkoCite.ItemAlsoKnownAs: 10.1080/13664530.2012.668103 10/gf5f6p 2339240:QYT78QZJ 2405685:AJFFY6AZ 2534378:EYTQ9C76 2534378:ILM8S5MC 2534378:L6R23M7S 2534378:PXRSVU2M 2534378:TBRE94GM 2534378:U2JMZZFP
Keywords: AUDIOVISUAL education; BANGLADESH; Bangladesh; COMPUTER assisted instruction; ENGLISH language – Study & teaching – Foreign speakers; Education–Teaching Methods And Curriculum; Educational technology; LANGUAGE teachers; Learning; PROFESSIONAL education; Professional development; SECONDARY school teachers; TEACHER development; TEACHERS – Attitudes; Teacher education; UCEP-Bangladesh; __:import:01; __:match:final; __:matched; __:study_id:2099954; ___working_potential_duplicate; hand-held device; school-based; teachers' professional development; teachers’ professional development; technology-enhanced learning

Massive Open Online Courses (MOOCs) for Professional Teacher and Teacher Educator Development: A Case of TESSA MOOC in Kenya - Wambugu, Patriciah W. (Universal Journal of Educational Research, 2018)
This study intends to present a bespoke teacher professional development MOOC designed by Teacher Education for Sub-Saharan Africa (TESSA) team that allows MOOCs to become a viable means offering cost-effective, quality professional teacher development. TESSA is a network of teachers and teacher educators, working to improve classroom teaching in Africa. TESSA MOOC is an innovative approach to capacity building for teacher educators and teachers across Africa. The study presents outputs of an evaluation of TESSA MOOC course undertaken by Kenyan teachers and teacher educators. The experiences of the participants were that the TESSA MOOC was a new but interesting, appealing and flexible course. In addition, the participants were able to learn from one another and what they learnt may impact on their pedagogical skills. Key challenges identified include difficulties in downloading of materials due to lack of internet connectivity and use of ICT phobia for learning. MOOCs represent an untapped potential for teacher professional development that can be a cost and resource effective means to deliver quality education to teachers and teacher educators. Therefore, the teachers and teacher educators may need to exploit this learner based TESSA MOOC to build capacity for teaching.
Publisher: Horizon Research Publishing KerkoCite.ItemAlsoKnownAs: 10.13189/ujer.2018.060604 10/gf622k 2339240:FWBVWVA2 2405685:ARBG7E6A
Keywords: Educational Quality; Faculty Development; Foreign Countries; Information Technology; Online Courses; Teacher Education; Teacher Educators; Teacher Effectiveness

School-based teachers' professional development through technology-enhanced learning in Bangladesh - Mahruf C Shohel, M; Banks, Frank (Teacher Development, 2012)
To promote significant pedagogical change, the most successful teacher education programmes for the global south happen in the school context. This paper is based on a pre-pilot intervention study of an international education development programme in Bangladesh. Technology-enhanced learning, in this case the use of the Apple® iPod® (iPod touch®), was used to support teachers' teaching and learning in their school contexts. This paper presents evidence to demonstrate how such school-based technology-enhanced support systems impact on classroom practice and help teachers' professional development. Using the case of a pre-pilot intervention in the Underprivileged Children's Educational Programs schools, it explores the teachers' professional development by analysing interviews with the teachers who were participating in the pre-pilot intervention programme, and draws the conclusion from the collected data that school-based teachers' professional development through technology-enhanced learning is contributing significantly to in-service training in a resource-constrained context.
Place: Abingdon Publisher: Taylor & Francis Ltd. shortDOI: 10/gf5f6p KerkoCite.ItemAlsoKnownAs: 10.1080/13664530.2012.668103 10/gf5f6p 2405685:NA7NT9BB 2534378:EYTQ9C76
Keywords: Bangladesh; Education–Teaching Methods And Curriculum; Educational technology; Learning; Professional development; Teacher education; UCEP-Bangladesh; ___working_potential_duplicate; hand-held device; school-based; teachers' professional development; technology-enhanced learning

The ‘trainer in your pocket’: mobile phones within a teacher continuing professional development program in Bangladesh - Walsh, Christopher S.; Power, Tom; Khatoon, Masuda; Biswas, Sudeb Kumar; Paul, Ashok Kumar; Sarkar, Bikash Chandra; Griffiths, Malcolm (Professional Development in Education, 2013)
Examples of mobile phones being used with teachers to provide continuing professional development (CPD) in emerging economies at scale are largely absent from the research literature. We outline English in Action’s (EIA) model for providing 80,000 teachers with CPD to improve their communicative language teaching in Bangladesh over nine years. EIA’s CPD program is delivered face to face and supported through open distance learning (ODL). This innovative model of teacher CPD is supported through peer learning and self-study using a variety of print, audio and video resources. Drawing on the success of EIA’s pilot studies, where internal and external evaluation reported significant improvement in teachers’ and students’ English-language competence after one year, the current phase is using low-cost mobile phones, or the ‘trainer in your pocket’ to deliver CPD to 12,500 teachers through 2015. We believe EIA’s teacher CDP model is best suited to assist the project in achieving one of its primary goals: to increase the English-language proficiency of 12 million students, allowing them to access greater social and economic opportunities in the future. We argue EIA’s use of mobile phones for the provision of teacher CPD – at scale – is timely and replicable in both developed and developing contexts.
Publisher: Routledge _eprint: https://doi.org/10.1080/19415257.2013.766232 KerkoCite.ItemAlsoKnownAs: 10.1080/19415257.2013.766232 2339240:4SYER8H6 2405685:3WMSFI3D
Keywords: English in Action; communicative language teaching; mobile phones; open distance learning; school-based professional development (SBPD); teachers’ continuing professional development (CPD)

Teacher Professional Development in Tanzania: Challenges and Opportunities - Komba, Sotco Claudius; Mwakabenga, Rehema Japhet (Educational Leadership, 2019)
This chapter is about teacher professional development in Tanzania. The authors have examined the current status of teacher professional development in Tanzania, focusing on predominant perspectives on the concept and provision modalities. In addition, the authors have identified challenges facing teacher professional development in Tanzania, most of which seem to be systemic. The challenges include lack of explicit policy and guidelines for teacher professional development, limited knowledge on teacher professional development among teacher professional development stakeholders, predominance of traditional approach to teacher professional development, and ineffective organization of teacher professional development activities. It is, thus, concluded that a number of opportunities are available for effective teacher professional development in Tanzania. These include strengthening the available institutions responsible for teacher professional development, making use of different teacher professional development providers available in the country to promote professional development activities for teachers through a harmonized scheme and capitalizing on the use of different communication networks and the national optic fiber to promote self-directed teacher professional development.
Publisher: IntechOpen KerkoCite.ItemAlsoKnownAs: 10.5772/intechopen.90564 2339240:9MJFKUCS 2405685:632GMNKZ
Keywords: _Tanzania; _final_bib

Teachers’ self-directed professional development: science and mathematics teachers’ adoption of ICT as a professional development strategy - Mushayikwa, Emmanuel (African Journal of Research in Mathematics, Science and Technology Education, 2013)
This paper is part of a larger study that was carried out to investigate the use of information communication technology (ICT) in the self-directed professional development (SDPD) of mathematics and science teachers in Zimbabwe. The educational context provides an example of how teachers compensated for lack of structured government initiatives to support teachers' professional development. This paper focuses on the ways in which these teachers were using ICT resources to further their professional development. The study is based on 259 questionnaire responses from A-level Science and Mathematics teachers in Zimbabwe. Doyle and Ponder's "Practicality Ethic" and Loucks-Horsley et al.'s "Concerns-Based Adoption Model" provided the theoretical framework for analysing teachers' decision making and led to the development of a model for teacher empowerment with respect to the use of ICT. The study results showed that around 60% of teachers experienced difficulties in accessing ICT for their professional development. About half of the non-users did not access ICT even when it was available at their schools. Some of those who did access ICT used innovative methods to ensure access, including using their own resources, and pooling resources. The findings also show that teachers have three main drivers for using ICT for SDPD, including word processing for generating instructional materials; accessing and downloading web-based learning materials; and emailing for networking with peers and professional organisations. The results of this study demonstrate the great potential that ICT has for teachers' SDPD.
Extra URL: https://www.tandfonline.com/doi/full/10.1080/10288457.2013.848540 KerkoCite.ItemAlsoKnownAs: 10.1080/10288457.2013.848540 2339240:IK7J9JJ2 2405685:NB55PITP 2534378:QSCE4PB5
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2096430; __finaldtb

MOOCs for Teacher Professional Development: Reflections and Suggested Actions - Misra, Pradeep Kumar (Open Praxis, 2018)
Teacher Professional Development (TPD) has become a major policy priority within education systems worldwide. But keeping teachers professionally up-to-date and providing them professional development opportunities on continuing basis is a big challenge. Massive Open Online Courses (MOOCs) can be a cost and resource effective means to complement the traditional methods of professional development of teachers. This optimism is based on the assumption that use of MOOCs will facilitate mass training of teachers as per their convenience and ease. The other assumption is that being MOOCs-based training, it will be easy to adapt it to different cultures and languages. Considering these assumptions, this concept paper which is based on reviews of different reports, documents and research papers - discusses the challenges of TPD, reflects upon promises of using MOOCs for TPD; details initiatives and experiences of using MOOCs for TPD; and suggests actions for promoting the use of MOOCs for TPD.
KerkoCite.ItemAlsoKnownAs: 10.5944/openpraxis.10.1.780 2339240:27J8DKI6 2405685:AYFYMSM8

Improving teacher professional development for online and blended learning: a systematic meta-aggregative review - Philipsen, Brent; Tondeur, Jo; Pareja Roblin, Natalie; Vanslambrouck, Silke; Zhu, Chang (Educational Technology Research and Development, 2019)
In order to fully realise the potential of online and blended learning (OBL), teacher professional development (TPD) strategies on how to teach in an online or blended learning environment are needed. While many studies examine the effects of TPD strategies, fewer studies target the specific important components of these strategies. This study addresses that gap by conducting a systematic review of qualitative data consisting of 15 articles on TPD that targets OBL. Using a meta-aggregative approach, six different synthesised findings were identified and integrated into a visual framework of the key components of TPD for OBL. These synthesised findings are the base for the action recommendations which present specific and contextualised suggestions. Taken together, the findings can inform in-service teachers and trainers, together with further research and development efforts that are concerned with TPD for OBL.
Extra URL: https://doi.org/10.1007/s11423-019-09645-8 KerkoCite.ItemAlsoKnownAs: 10.1007/s11423-019-09645-8 2405685:BVQU5XV8 2534378:4WR2J4Z5

Teacher Professional Development and Student Literacy Growth: a Systematic Review and Meta-analysis - Basma, Badriah; Savage, Robert (Educational Psychology Review, 2018)
This systematic review explores the impact of teacher professional development (PD) on student reading achievement. The first part of the literature evaluates all available existing systematic reviews and meta-analyses of PD intervention studies. No quality reviews of PD and reading specifically (distinct from ‘attainment’) were found. There was a little overlap of studies in existing reviews. The second part of the systematic review focuses on the most recent intervention studies exploring PD and student reading achievement. The results of a meta-analysis of all high-quality studies are presented in the third part of the paper. This analysis showed no strong evidence of publication bias and an effect size for PD on student literacy of g = 0.225. This effect was moderated by the number of hours of PD whereby studies with fewer than 30 h of PD was significant for student reading outcomes (g = 0.367, p < 0.001) but more than 30 PD hours was not significant (g = 0.143, p > .05). Following a Weight of Evidence assessment, analysis showed that nearly all high-quality articles involved shorter PD. Weight of Evidence was a significant moderator, (g = 0.408, p < 0.001 for high-quality studies, g = 0.077, p > 0.5, n.s., for medium quality studies). Our review suggests that only high-quality studies of short teacher PD currently provide evidence of impact on student’s reading achievement.
shortDOI: 10/ghgn5t KerkoCite.ItemAlsoKnownAs: 10.1007/s10648-017-9416-4 10/ghgn5t 2405685:9XT28XJI
Keywords: C: International

Pedagogic change by Zambian primary school teachers participating in the OER4Schools professional development programme for one year - Hennessy, Sara; Haßler, Björn; Hofmann, R. (Research Papers in Education, 2016)
Supporting and upskilling teachers are essential to enhancing the quality of learning in developing contexts – the focus of Education For All – yet little evidence exists concerning what kinds of teacher education are actually most effective and what changes in ‘quality’ are desired and feasible. This paper illustrates how a concrete, research-informed school-based, model of professional development in sub-Saharan Africa can address the quality agenda. It reports on a trial of a pioneering, multimedia programme supporting interactive mathematics and science teaching using open educational resources and classroom digital technology, where available. The programme was carefully adapted to the Zambian context and ran weekly for one school year with 12 teachers in a low-resourced primary school. The study examined the impact on teachers' thinking and classroom practices. Data were derived from observations, lesson and workshop recordings, teacher interviews, portfolios and audio diaries. Through a teacher-led workshop approach and trialling new pedagogical strategies, teachers raised their expectations of pupils, adapted to learners’ knowledge levels, used more practical and group work, and integrated technology use. Pupils built deeper understanding of subject matter, were actively engaged, worked collaboratively and used digital technologies for problem-solving.
shortDOI: 10/gftr46 KerkoCite.ItemAlsoKnownAs: 10.1080/02671522.2015.1073343 10/gftr46 10/ghgnfx 2129771:4DDI7MD4 2129771:CPWUEHPK 2129771:DLXY6Q8J 2129771:QGHFB3QL 2129771:WHB6UUT9 2339240:8PZIPSBY 2339240:ASBRKMNU 2339240:UTDG7DWR 2339240:VBAD27XQ 2405685:C677I5RF 2405685:CHHQANDG 2405685:CSCFPKV2 2405685:F6292I9Z 2405685:LDKZC9TP 2405685:NAJLZ3FE 2405685:NK5HW6CV 2405685:R5KQR27A 2405685:S9FRC57W 2405685:VZ562RQX 2405685:YBR4RYHA 2534378:4NJUGCID 2534378:E2PEHWQT 2534378:GGBWWEIN 2534378:HQ26LIRW 2534378:QVE8VZAZ 2534378:Z7EEHWT2 257089:AGK9WB3X 257089:FXEJEAA9 261451:ENUVRNA2 261495:4NPFWURU 261495:YIZHH9Z5
Keywords: C:sub-Saharan Africa; CAREER development; EDUCATION – Study & teaching; GRADUATE education; PROFESSIONAL education; TEACHER training; ZAMBIA; Zambia; __:import:01; __:match:final; __:matched; __:study_id:2099887; ___working_potential_duplicate; __finaldtb; digital technology; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode; interactive pedagogy; open educational resources; sub-Saharan Africa; teacher professional development

Implementing school-based teacher development in Tanzania - Hardman, Frank; Hardman, Jan; Dachi, Hillary; Elliott, Louise; Ihebuzor, Noel; Ntekim, Maniza; Tibuhinda, Audax (Professional Development in Education, 2015)
This paper reports on the findings of a pilot school-based professional development programme for Tanzanian primary school teachers launched in February 2011 and evaluated in December 2012 by the Ministry of Education and Vocational Training with the support of UNICEF. The study set out to investigate the effectiveness and efficiency of the pilot programme in changing pedagogical practices before it was scaled up nationally. It was found that teachers who had participated in the school-based training showed significant differences in their pedagogical practices and demonstrated a positive attitude towards their training and their pupils, and saw teaching and learning as an interactive, communicative process. Drawing on the findings, the paper explores the challenges and the lessons learned for scaling up school-based teacher development at the national level in Tanzania and other countries in the east and southern African region.
Publisher: Routledge _eprint: https://doi.org/10.1080/19415257.2015.1026453 shortDOI: 10/gfv5xx KerkoCite.ItemAlsoKnownAs: 10.1080/19415257.2015.1026453 10/gfv5xx 2129771:2ABESKPA 2405685:2A8AKS3Z 2405685:5228WPEN 2405685:N44VX4DB 2534378:2UNZYMXP 2534378:ZQIPTYJL
Keywords: Tanzania; __C:filed:1; capacity development; primary education; quality education; school-based teacher development; teacher education reform

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using ICT, 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school...
Publisher: Open Campus, The University of the West Indies, West Indies KerkoCite.ItemAlsoKnownAs: 2339240:JX8TEHVV 2405685:UB39IXQK
Keywords: ⛔ No DOI found

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using ICT, 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school...
Publisher: Open Campus, The University of the West Indies, West Indies KerkoCite.ItemAlsoKnownAs: 2339240:JX8TEHVV 2405685:UB39IXQK
Keywords: ⛔ No DOI found

Teacher knowledge and employer-driven professional development: a critical analysis of the Gauteng Department of Education programmes - de Clercq, Francine; Shalem, Yael (Southern African Review of Education, 2014)
There is growing consensus in international and local literature that, to be effective, professional development activities (PDAs) should focus on ways of teaching that improve learners' learning, but there is no clear consensus on the teaching focus and the form in which teacher learning is organised. Drawing from literature on teacher knowledge, in particular Shulman's distinction between subject matter and pedagogical content knowledge (PCK), this article critically reviews the PDAs provided by the Gauteng Department of Education (GDE), South Africa. It identifies 2009 as a turning point in the GDE provision of PDAs. Until 2009, most PDAs were targeted at the improvement of a few discrete aspects of teacher practice, to comply with a new curriculum framework. Around 2009, the GDE turned towards scripted teaching in a form of standardised lesson plans, to engineer a whole new practice for teachers in order to improve learners' results. The argument of this article is that teacher knowledge of subject matter, consisting of knowledge of the substantive and syntactic aspects of the curriculum content and beyond, has not been imparted to teachers by employer-driven curriculum implementation workshops or short courses, and that only a limited number of teaching routines such as sequencing and pacing of the curriculum content can be imparted by scripted lesson plans. Although the idea of scripting a new practice is understandable in the light of the general agreement that PDAs in South Africa failed to make a difference to teachers' practice and to learners' performance, it is essential to understand its limitations., Y. (2014) Teacher knowledge and employer-driven professional development: A critical analysis of the Gauteng Department of Education programmes. Southern African Review of Education, 20(1): 129-147.
KerkoCite.ItemAlsoKnownAs: 2339240:59VJE745 2405685:Z6VARPVH 2534378:7FDZ8B93
Keywords: ⛔ No DOI found

Identifying the essential ingredients to literacy and numeracy improvement: Teacher professional development and coaching, student textbooks, and structured teachers’ guides - Piper, Benjamin; Simmons Zuilkowski, Stephanie; Dubeck, Margaret; Jepkemei, Evelyn; King, Simon J. (World Development, 2018)
Several rigorously evaluated programs have recently shown positive effects on early literacy and numeracy outcomes in developing countries. However, these programs have not been designed to evaluate which ingredients of the interventions are most essential to improve literacy outcomes. Policy makers therefore lack evidence as to whether program ingredients such as teacher professional development (PD), instructional coaching, learner materials, teachers’ guides, community support, or technology are required for program impact. The Kenya Primary Math and Reading Initiative was a randomized controlled trial that compared three treatment groups with speciﬁc ingredients and a control group. Using literacy and numeracy outcome measures for grades 1 and 2, we evaluated the beneﬁts of the following ingredients: (1) teacher PD and teacher instructional support and coaching; (2) revised student books in literacy and numeracy, at a 1:1 ratio, added to PD and instructional support; and (3) structured teacher lesson plans added to student books, PD, and instructional support. We found that two of the three combinations of ingredients had statistically signiﬁcant positive impacts on learning outcomes. The results showed that the third combination—PD, teacher instructional support and coaching, 1:1 student books, and structured teacher lesson plans—was most effective. A cost-effectiveness analysis on the ingredients showed that the option of PD and instructional support, 1:1 revised books, and teachers’ guides was the most expensive, but that the additional impact on learning made this the most cost-effective intervention. This study rigorously analyzes which ingredients for literacy and numeracy improvement would be most effective for overall impact, and suggests to policy makers that careful decisions regarding program ingredients will lead to more effectively designed and implemented interventions to improve learning in developing countries.
EdTechHub.Copy: 2129771:3IIW96ZB shortDOI: 10/gftrqf KerkoCite.ItemAlsoKnownAs: 10.1016/j.worlddev.2018.01.018 10/gftrqf 2129771:3IIW96ZB 2339240:AUEREUTT 2339240:NNWXI67C 2339240:QWI89XDJ 2339240:X37484JK 2405685:37II7RPP 2405685:4PBTS4CP 2405685:5LADY8ET 2405685:L36BGXMK 2405685:PT6BTPEC
Keywords: Africa; C:Kenya; Literacy; Numeracy; Program Evaluation; Program evaluation; Quantitative; Randomized controlled trial; Reading; Teacher Professional Development; ___working_potential_duplicate; numeracy; randomized control trial

The cascade model of teachers’ continuing professional development in Kenya: A time for change? - Bett, Harry Kipkemoi (Cogent Education, 2016)
Kenya is one of the countries whose teachers the UNESCO (2015) report cited as lacking curriculum support in the classroom. As is the case in many African countries, a large portion of teachers in Kenya enter the teaching profession when inadequately prepared, while those already in the field receive insufficient support in their professional lives. The cascade model has often been utilized in the country whenever need for teachers’ continuing professional development (TCPD) has arisen, especially on a large scale. The preference for the model is due to, among others, its cost effectiveness and ability to reach out to many teachers within a short period of time. Many researchers have however cast aspersions with this model for its glaring shortcomings. On the contrary, TCPD programmes that are collaborative in nature and based on teachers’ contexts have been found to be more effective than those that are not. This paper briefly examines cases of the cascade model in Kenya, the challenges associated with this model and proposes the adoption of collaborative and institutionbased models to mitigate these challenges. The education sectors in many nations in Africa, and those in the developing world will find the discussions here relevant.
shortDOI: 10/gfw2mk KerkoCite.ItemAlsoKnownAs: 10.1080/2331186X.2016.1139439 10/gfw2mk 2405685:K8ZKUDQE

Teachers of Refugees: A Review of the Literature - Richardson, Emily (Education Development Trust, 2018)
The United Nations High Commissioner for Refugees (UNHCR) estimates that 65.6 million people are forcibly displaced, having either crossed national borders or become internally displaced within their own countries. Of this estimate, over 22.5 million are refugees. Over half of the world's refugees are children. With an average length of displacement of approximately 20 years, the majority of these children will spend their entire childhoods away from home. Refugee children have limited access to basic social services like healthcare and education. Given the length of their displacement, generations of refugee children throughout the world could miss out on education altogether. Numerous studies show that the teacher is the most important in-school factor affecting the quality of education, particularly in refugee contexts, where the teacher is sometimes the only resource available to students. In refugee contexts where infrastructure and resources are limited, the role of the teacher is particularly important to the quality of education. However few studies to date have examined the role of teachers in refugee contexts. With more literature focusing on refugee children and youth, little is known about who the teachers of refugees are and how they are recruited, trained, retained, compensated and managed in their contexts. Importantly, there is little research on national teachers who are teaching refugee children; rather, much of the available literature focuses on refugee teachers – that is, teachers who are also refugees. In addition, this lack of literature on teachers of refugees hinders our understanding not only of their needs but also of 'how refugees can contribute to education in their host countries and (eventually) to their home countries'. The purpose of this literature review is to survey policies, practices and debates that governments and their partners must navigate to provide education for refugee populations, and the strategies they have used to select and manage teaching forces. The review analyses findings from the main literature on teachers of refugees according to the following themes: (1) recruitment, certification and selection of teachers; (2) teacher preparation and development; (3) teacher remuneration and incentives; and (4) teacher retention. In addition, for each of these themes, this review highlights the salient gaps in the research and suggests an agenda for further research. [Co-written with Leonora MacEwen and Ruth Naylor.]
Publication Title: Education Development Trust KerkoCite.ItemAlsoKnownAs: 2339240:KDEC9GDD 2405685:B3J76PXB
Keywords: Google Scholar/ teacher "professional development" AND refugees AND technology; RER theme_supporting educators

Teachers’ conception towards the use of social networks as a tool for professional development in Tanzania government secondary schools: the case of Dodoma municipality - Manyama, Charles (University of Dodoma, 2017)
The current study sought to assess teachers' conception toward the use of social networks as a tool for professional development in Tanzania government secondary schools the case of Dodoma Municipality. Thus, the specific objectives of this study were to assess the influence of demographic characteristics on the use of social networks or as a tool for professional development. To assess teachers conception on the available social networks opportunity that can support professional development, to investigate teachers use of social networks available for professional development, to explore the perceived benefits of using social networks opportunity as a tool for professional development and to examine limitation that hinder teachers for professional development. The study was guided by social-cognitive theory, community of practice model (CoP) and technology acceptance model (TAM). A cross-section research design was used to collect data that involved 84 teachers‟ from ten secondary schools, six head of schools three quality assurers and one respondent from DEO office. SPSS computer program was used to analyze the data. Qualitative data were analyzes through content analysis and quantitative data were analyzed statistically using descriptive and inferential statistics by using SPSS Version 20, and Microsoft Excel were highly used. Linear regression techniques were used to seek whether there is a relationship between demographic characteristics and the use of social networks. The survey results showed that there is no significant relationship between demographic factors with the use of social networks as a tool for professional development. Either teachers have positive conceptions towards the use of social networks as a tool for professional development. Furthermore, teachers use SNs for communicating with their fellow from different groups but it is not effectively integrated into professional development. The findings indicate that, to a large extent, teachers agreed that SNs make them to be more creative and help them to improve their communication skills. In addition the findings indicated that teachers lack training on how to integrate SNs in TPD. Finally,the researcher recommend that, educational stakeholders should provide financial and material support to teachers in order to overcome challenge that limit the use of technology in teaching and learning.
Accepted: 2018-04-11T09:35:23Z Publisher: The University of Dodoma KerkoCite.ItemAlsoKnownAs: 2339240:YDEVGFS3 2405685:U59ER7CF
Keywords: ⛔ No DOI found

Using video for professional development: the role of the discussion facilitator - Coles, Alf (Journal of Mathematics Teacher Education, 2013)
Past research into the use of video for professional development has failed to problematise or theorise sufﬁciently the role of the discussion facilitator. It has been reported consistently that it can be hard or take time to establish norms for discussion of video but little has been said about reasons why, or the role of the discussion facilitator. As a starting point in this area, I suggest ﬁves aspects or decision points in the role of the facilitator. Two aspects are taken from the literature and the others are drawn from empirical data, collected as part of an enactivist study into the use of video in one secondary school. At the school, teachers commented on ﬁnding video watching in a group more useful than lesson observation, with no evidence of this taking time to develop. I offer speculations, based on enactivist category theory, as to why the use of video in this school is effective. Having presented key aspects of the role of the facilitator of video use, a further look at the detail of the data from discussions serves to highlight some of the complexities involved in just one of the categories (and, by implication, the others). I conclude that the role of the facilitator cannot be separated from a consideration of the historical context in which discussion takes place.
shortDOI: 10/gf7gq6 KerkoCite.ItemAlsoKnownAs: 10/gf7gq6 2405685:GIYVKDIG 2534378:DGNEMY2J

Teachers’ professional development through the English in action secondary teaching and learning programme in Bangladesh: Experience from the UCEP schools - Shohel, M; Banks, F; Banks, F (Procedia - Social and Behavioral Sciences, 2010)
This paper explores the English in Action (EIA) intervention in Bangladesh and explores how the school-based support systems impact on classroom practice in Underprivileged Children’s Educational Programs (UCEP) Schools. It presents evidence to demonstrate how in-school training helps teachers’ professional development (TDP). This paper explores TPD by analysing interviews with UCEP school administrators and teachers who are participating in the pre-pilot EIA intervention. It draws a conclusion that school-based support systems combined with technology enhanced open and distance learning (ODL) are contributing significantly to TPD as an in-service training.
KerkoCite.ItemAlsoKnownAs: 10/bfg65g 2339240:M5TKZEV8 2405685:LQTN958P

Teacher educators and OER in East Africa: Interrogating pedagogic change - Wolfenden, Freda; Auckloo, Pritee; Buckler, Alison; Cullen, Jane (Adoption and Impact of OER in the Global South, 2017)
This study examines the use of Open Educational Resources (OER) in six teacher education institutions in three contrasting East African settings – Mauritius, Tanzania and Uganda – all of which had previous engagement with OER initiatives. Drawing primarily on interviews with teacher educators, the study examines how and when teacher educators engage with OER, the factors that support and constrain sustained OER engagement, and the influence of such engagement on their teaching practice. It seeks to answer the following three research questions: What kinds of OER are teacher educators aware of and how do they access them? How and for what purpose are they using the OER? What intended and enacted pedagogic practices are associated with OER use? The study takes a sociocultural approach, paying attention to the practices of teacher educators and the context and culture of the teacher education institutions within which they work, as well as the national policies relevant to these institutions. Surveys were sent to academic staff at each of the participating institutions who were, or had been, involved in curriculum development work involving OER. Male and female educators from different disciplinary backgrounds and with varying roles and periods of service within the institutions were targeted. From the respondents, selected individuals were asked to participate in semi-structured interviews concerning OER and their pedagogical practices. A total of 58 surveys were completed by teacher educators along with 36 in-depth teacher educator interviews and six institutional stakeholder interviews. The results of the study indicate that teacher educators’ understanding and use of OER is highly fragmented, with little traction at department or institutional level. At all the study sites there was dissonance between the ways in which individual educators are using OER and the dominant institutional values and discourse. There were also numerous structural and cultural factors acting to limit agency with regards to OER use. The demands of curriculum and assessment, professional identity, digital skills, provision of equipment and connectivity, values and weak cultures of collaboration all exerted an influence and enabled or constrained teacher educators’ efforts to achieve agency with OER. For a small number of teacher educators (OER “champions”), OER provides a tool for extending their agency to move towards more participatory practices. In their interviews, several of these educators spoke of the formative role of academic training and many were linked to external OER networks. These elements of historic identity formation influence how they respond to OER, and enhance their confidence to take risks in moving beyond conventional practice. Enabling educators to act in an agentive way with OER is not easy. Moving forward, attention should be given to issues of access so that educators are able to locate and view OER relatively easily and experiment with their use. This study recommends that time be made available for educators to enhance their skills in working digitally and to become familiar with principles of learning design such that these become integral dimensions of their professional identity. It is also argued that extending and deepening engagement with OER requires opportunities for professional dialogue and collaboration to support the development of productive educator identities with OER and transformation of the community’s field of practice.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1094850 2339240:CV3YAJZ6 2405685:T9JSZ9PS
Keywords: East Africa; Global South; Mauritius; OEP; OER; Open Education; Open Educational Resources; ROER4D; Tanzania; Uganda; _not_EdTechHub; _zenodoOTHER; agency; pedagogy; teacher education

Moving education into the digital age: the contribution of teachers' professional development - Twining, P.; Raffaghelli, J.; Albion, P.; Knezek, D. (Journal of Computer Assisted Learning, 2013)
This article introduces the main outcomes of discussions at EDUsummIT 2011 by the specific Technical Working Group on Teacher Professional Development (TWG3). The focus was to explore how professional development of teachers may ensure that teachers are better prepared to use information and communication technology (ICT) to promote 21st century learning. The article is organized into three main sections: a review of key literature on professional development of teachers (TPD), in general and with specific reference to ICT; a summary of the key points emerging from TWG3's discussions; and recommendations for action. On the basis of discussions held within the TWG3, the authors concluded that effective TPD requires changes at several levels of educational systems (political, institutional and individual), and that ICTs should be seen as an opportunity for introducing new goals, structures and roles that support these changes. It is significant that while many of the issues highlighted by the group are well established, addressing them continues to be problematic globally.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/jcal.12031 KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12031 2339240:Q58NA4JQ 2405685:AQTVKM4U 2405685:GF53869U 2405685:HQMJZWT7 2534378:DKXRGCIE 2534378:NESJ6YZV
Keywords: ICT; IT; digital age; policy recommendations; practitioner research; teacher professional development; transformation

The role of video in teacher professional development - Marsh, Brian; Mitchell, Nick (Teacher Development, 2014)
shortDOI: 10/gf7grh KerkoCite.ItemAlsoKnownAs: 10.1080/13664530.2014.938106 10/gf7grh 2339240:6U4RC34H 2339240:NUKR7Z5G 2405685:AT5BDZWD 2405685:PUT3TV3R 2405685:QX23PU84

Teacher Professional Development around the World: The Gap between Evidence and Practice - Popova, Anna; Evans, David K.; Breeding, Mary E.; Arancibia, Violeta (World Bank, 2018)
shortDOI: 10/ghgngf KerkoCite.ItemAlsoKnownAs: 10.1596/1813-9450-8572 10/ghgngf 2339240:XS7TPHW4 2405685:RJX4M8AM 2405685:SQ5CWK8Q 2486141:U6AFHNPF
Keywords: C:Low- and middle-income countries

The Influence of Teachers’ Professional Development Activities on the Factors Promoting ICT Integration in Primary Schools in Mongolia - Li, Shengru; Yamaguchi, Shinobu; Sukhbaatar, Javzan; Takada, Jun-ichi (Education Sciences, 2019)
This paper examines the influences of professional development activities on important teacher-level factors that are important for the use of Information and Communication Technology (ICT) in education for primary school teachers in Mongolia. The study utilizes the survey data collected in 2012 (n = 826) and 2016 (n = 1161) to identify the changes in factors that are important to the use of ICT in education. The study result shows that six teacher level factors that are important for the ICT integration have been improved over time through professional development activities. These are professional competency in educational use of ICT, collaboration for ICT integration, benefits on use of ICT, autonomy to innovate, recognition as a professional, and skills and practices in educational use of ICT. This provides supporting evidence to educational practitioners for the implementation of effective professional development programs to promote ICT integration in education, especially in the developing country’s context.
Number: 2 Publisher: Multidisciplinary Digital Publishing Institute KerkoCite.ItemAlsoKnownAs: 10.3390/educsci9020078 2339240:XWWZXZ76 2405685:EENQXYD4
Keywords: ICT in education; ___working_potential_duplicate; auto_merged; education policy; educational change; factors promoting ICT integration; teacher’s professional development

Professional Development Research: Consensus, Crossroads, and Challenges - Hill, Heather C.; Beisiegel, Mary; Jacob, Robin (Educational Researcher, 2013)
Commentaries regarding appropriate methods for researching professional development have been a frequent topic in recent issues of Educational Researcher as well as other venues. In this article, the authors extend this discussion by observing that randomized trials of specific professional development programs have not enhanced our knowledge of effective program characteristics, leaving practitioners without guidance with regard to best practices. In response, the authors propose that scholars should execute more rigorous comparisons of professional development designs at the initial stages of program development and use information derived from these studies to build a professional knowledge base. The authors illustrate with examples of both a proposed study and reviews of evidence on key questions in the literature.
Publisher: American Educational Research Association shortDOI: 10/gdqbjb KerkoCite.ItemAlsoKnownAs: 10.3102/0013189X13512674 10/gdqbjb 2405685:638YT9CJ 2405685:X5HM4IVD 2534378:YPGSUAT2
Keywords: C:International

Preliminary impacts of the “Learning to Read in a Healing Classroom” intervention on teacher well-being in the Democratic Republic of the Congo - Wolf, Sharon; Torrente, Catalina; Frisoli, Paul; Weisenhorn, Nina; Shivshanker, Anjuli; Annan, Jeannie; Aber, J. Lawrence (Teaching and Teacher Education, 2015)
This article examines the impacts of a partial year of implementation of Learning to Read in a Healing Classroom (LRHC), a curricular and social-emotional teacher professional development intervention in southeastern Democratic Republic of the Congo, on teacher professional well-being. Using a cluster-randomized control trial, this study assesses LRHC impacts on a sample of 346 teachers from 64 primary schools. We find statistically significant increases in job dissatisfaction for female teachers and increases in motivation for the least experienced teachers. Implications are discussed for the role of teacher professional development and well-being in improving education in low resource and conflict-affected contexts.
shortDOI: 10/f7zk3n KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2015.08.002 10/f7zk3n 2339240:J5TZZGLX 2405685:FVVYBX4Y 2405685:JGP79B9M
Keywords: Democratic Republic of the Congo; International education; Motivation; Teacher professional development

The Effect of Teacher Coaching on Instruction and Achievement: A Meta-Analysis of the Causal Effect - Kraft, Matthew A.; Blazar, David; Hogan, Dylan (Review of Educational Research, 2018)
Teacher coaching has emerged as a promising alternative to traditional models of professional development. We review the empirical literature on teacher coaching and conduct meta-analyses to estimate the mean effect of coaching programs on teachers’ instructional practice and students’ academic achievement. Combining results across 60 studies that employ causal research designs, we find pooled effect sizes of 0.49 standard deviations (SD) on instruction and 0.18 SD on achievement. Much of this evidence comes from literacy coaching programs for prekindergarten and elementary school teachers. Although these findings affirm the potential of coaching as a development tool, further analyses illustrate the challenges of taking coaching programs to scale while maintaining effectiveness. Average effects from effectiveness trials of larger programs are only a fraction of the effects found in efficacy trials of smaller programs. We conclude by discussing ways to address scale-up implementation challenges and providing guidance for future causal studies.
shortDOI: 10/ggjrhd KerkoCite.ItemAlsoKnownAs: 10.3102/0034654318759268 10/ggjrhd 2339240:94ATJ2KM 2339240:L9J24WV4 2339240:Q2UV8HVZ 2339240:Y3AHBV5R 2405685:2CWW72YN 2405685:3DXSV98B 2405685:6L7LJIMQ 2405685:JXICF3W3 2405685:KJDH8RVK 2405685:R4WDE3P4 2534378:9LCRTTXK
Keywords: C:High-income countries; C:United States; ___working_potential_duplicate; effect size; experimental design; meta-analysis; professional development; school/teacher effectiveness; teacher education/development

Teacher design in teams as a professional development arrangement for developing technology integration knowledge and skills of science teachers in Tanzania - Kafyulilo, Ayoub; Fisser, Petra; Voogt, Joke (Education and Information Technologies, 2016)
This study investigated the impact of teacher design teams as a professional development arrangement for developing technology integration knowledge and skills among in-service science teachers. The study was conducted at a secondary school in Tanzania, where 12 in-service science teachers participated in a workshop about technology integration in science teaching and worked in design teams to prepare technology-enhanced biology, chemistry and physics lessons. Through collaboration in design teams, teachers were able to make science animations using PowerPoint and record videos to use in their teaching. The designed lessons were taught in the classroom and reflected upon thereafter by all teachers. In order to determine the change in teachers’ technology integration knowledge and skills, data were collected before and after the professional development arrangement by using questionnaire, interview and observation data. Focus group discussion and reflection questionnaire data were used to assess teachers’ experience of working in design teams at the end of the professional development arrangement. Findings showed an increase in teachers’ technology integration knowledge and skills between pre- and post-measurements. Collaboration in design teams had the potential for teachers to share knowledge, skills, experience and challenges related to technology-enhanced teaching.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-014-9321-0 10/gf5f4m 2339240:7CEQ93PT 2339240:JGN4RV5I 2339240:UY65BS7S 2405685:JSZJ37ZS 2405685:RUYKREG7 2534378:3QB7Y6QJ 2534378:55Q9N5GF 2534378:56IKE4DH 2534378:7PX4TKVE 2534378:SYZ7CCCB 2534378:ZSZNYZ9S
Keywords: CAREER development; CHEMISTRY education; Computer Software; Computers–Information Science And Information Theory; Cooperation; EDUCATIONAL technology; ERIC; Current Index to Journals in Education (CIJE); Educational technology; Focus Groups; Foreign Countries; In-service science teachers; Interviews; Lesson design in teams; Lesson plans; MICROSOFT PowerPoint (Computer software); Observation; PROFESSIONAL education; Professional Development; Professional development; Questionnaires; Reflection; SCIENCE teachers; SECONDARY schools; Science Instruction; Science Teachers; Science teachers; Secondary Education; Secondary Schools; Secondary school teachers; TPACK; Tanzania; Teaching Methods; Teamwork; Technology Integration; Technology Uses in Education; Technology integration knowledge and skills; Visual Aids; _Source:Intuitive; _THEME: Curriculum and resources; _THEME: Open systems; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2096124; __finaldtb

Challenges and opportunities for teacher professional development in interactive use of technology in African schools - Hennessy, Sara; Haßler, Bjoern; Hofmann, Riikka (Technology, Pedagogy and Education, 2015)
This article examines the supporting and constraining factors influencing professional learning about interactive teaching and mobile digital technology use in low-resourced basic schools in sub-Saharan Africa. It draws on a case study of iterative development and refinement of a school-based, peer-facilitated professional learning programme (‘OER4Schools’) that integrated use of mobile technologies, digital open educational resources and interactive pedagogy. The research and development involved teachers in three Zambian primary schools and culminated in an extensive multimedia resource. Using an ecological framework, factors emerging were characterised at three levels: teacher, school, and the wider community and policy context. They include school organisation and leadership, teacher motivation and perceptions of opportunities for professional learning and change, teacher views of pupil capabilities, availability of resources, teacher collaboration, and viewpoints of parents and policymakers. [ABSTRACT FROM PUBLISHER]
Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.ebscohost.com/login.aspx?direct=true&db=bri&AN=111289127&site=ehost-live&scope=site KerkoCite.ItemAlsoKnownAs: 10.1080/1475939X.2015.1092466 10/gfv5xz 2129771:L2HUHYLN 2339240:24LHAF5C 2339240:K9R22K2F 2339240:WV3XY5NW 2405685:6ZLKKKH7 2405685:8V49PM4G 2405685:KILQYYBU 2405685:SXKPQUJ5 2534378:6TMRG3EP 2534378:BF6PBW3F 2534378:QQ6BVI89
Keywords: ADULTS; AFRICA; Article; CAREER development; Digital Technology; EDUCATION; EDUCATIONAL technology research; Interactive Pedagogy; Open Educational Resources; PRIMARY school teachers; Sub-Saharan Africa; Zambia; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2099892; __finaldtb; digital technology; interactive pedagogy; open educational resources; sub-Saharan Africa; teacher professional development

Improving Literacy Instruction in Kenya Through Teacher Professional Development and Text Messages Support: A Cluster Randomized Trial - Jukes, Matthew C. H.; Turner, Elizabeth L.; Dubeck, Margaret M.; Halliday, Katherine E.; Inyega, Hellen N.; Wolf, Sharon; Zuilkowski, Stephanie Simmons; Brooker, Simon J. (Journal of Research on Educational Effectiveness, 2017)
We evaluated a program to improve literacy instruction on the Kenyan coast using training workshops, semiscripted lesson plans, and weekly text-message support for teachers to understand its impact on students’ literacy outcomes and on the classroom practices leading to those outcomes. The evaluation ran from the beginning of Grade 1 to the end of Grade 2 in 51 government primary schools chosen at random, with 50 schools acting as controls. The intervention had an impact on classroom practices with effect sizes from 0.57 to 1.15. There was more instruction with written text and more focus on letters and sounds. There was a positive impact on three of four primary measures of children’s literacy after two years, with effect sizes up to 0.64, and school dropout reduced from 5.3% to 2.1%. This approach to literacy instruction is sustainable, and affordable and a similar approach has subsequently been adopted nationally in Kenya.
shortDOI: 10/gftrwn KerkoCite.ItemAlsoKnownAs: 10.1080/19345747.2016.1221487 10/gftrwn 2339240:BHTFCPZY 2339240:NZ4F4CI7 2339240:WQWT3F9T 2405685:8RA9QUBS 2405685:KF3AT824 2405685:L29LKK2H 2405685:NZMWQR53 2405685:ZPZ33ATM 2534378:5AX7B2XZ 2534378:69A797YC 2534378:6YQFC9JR 2534378:DNVP68DF 2534378:JCAY2TT6 2534378:LP5IEPIP 2534378:M4JQTSXE 2534378:NJKCAKUT
Keywords: Africa; Classroom Observation Techniques; Dropout Rate; ERIC; Current Index to Journals in Education (CIJE); Early Childhood Education; Effect Size; Elementary Education; Elementary School Students; Elementary School Teachers; Faculty Development; Foreign Countries; Grade 1; Grade 2; Handheld Devices; Improving Learning in Sub-Saharan Africa Using Rigorous Research Designs; Intelligence Tests; Intervention; Interviews; Kenya; Literacy Education; Maximum Likelihood Statistics; Pretests Posttests; Primary Education; Program Effectiveness; Promising Interventions Are Great; but Are They Enough?; Questionnaires; RCT; Randomized Controlled Trials; Raven Progressive Matrices; Rural Schools; Statistical Analysis; Teacher Improvement; Teaching Methods; Telecommunications; What We Are Learning About Early Education in Sub-Saharan Africa; __:import:01; __:match:final; __:matched; __:study_id:2096051; ___working_potential_duplicate; __finaldtb; early grade reading; literacy instruction

Using video to support in-service teacher professional development: the state of the field, limitations and possibilities - Major, L; Watson, Steven (Technology Pedagogy and Education, 2017)
KerkoCite.ItemAlsoKnownAs: 10.1080/1475939X.2017.1361469 2339240:4W59D9U3 2405685:TKGRWCS3 2405685:W7DDRAT9 2405685:WF9QFYZY 2534378:YYFW64KC
Keywords: C: International; ⛔ No DOI found

Technology-Supported Professional Development for Teachers: Lessons from Developing Countries - McAleavy, Tony; Hall-Chen, Alex; Horrocks, Sarah; Riggall, Anna (Education Development Trust, 2018)
This report captures what might be learnt from a selection of the world’s most interesting examples of technology-assisted in-service professional development in lower-income countries and from wider reflections about the potential of technology to enhance the professional learning of teachers.
KerkoCite.ItemAlsoKnownAs: 2339240:CNU2GKRL 2339240:KPPU5Z99 2339240:RNRNDVLK 2339240:S2XT5FSG 2339240:UYNN98AQ 2339240:Z8QK9TIS 2405685:4JNZ9RRF 2405685:58SRHUVT 2405685:CF2KPK7I 2405685:DJG72BUZ 2405685:FXXS4882 2405685:LW3BSKJ4 2405685:ZEBNC5TV 2534378:6GQU9R37 2534378:ARJJXBIL 2534378:TQ4YR37L 2534378:WSS9V2GJ 2534378:XIMVL4RJ
Keywords: Africa; Bangladesh; Blended Learning; C:Low- and middle-income countries; Developing Nations; ERIC; Resources in Education (RIE); Educational Technology; Elementary Education; Elementary School Teachers; Faculty Development; Foreign Countries; Handheld Devices; India; Inservice Teacher Education; Kenya; Large Group Instruction; Nigeria; Online Courses; Pakistan; Policymakers; Practitioners; Refugees; Shared Resources and Services; Social Media; Teaching Methods; Technology Integration; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; ⛔ No DOI found

Teacher coaching in Kenya: Examining instructional support in public and nonformal schools - Piper, Benjamin; Zuilkowski, Stephanie Simmons (Teaching and Teacher Education, 2015)
Instructional coaching has improved student outcomes in the United States, and may help to solve Kenya's literacy problems. Coaching is costly, however, and evidence is lacking regarding the most cost-efficient teacher-to-coach ratio. We used student literacy outcome data from more than 8000 students participating in the Kenya Primary Math and Reading Initiative—a randomized controlled trial of instructional interventions in public and nonformal schools—to fill this gap. Coaches in larger public zones made fewer visits per teacher, and teacher-coach ratio and student performance were negatively associated. Using causal methods, we concluded that lower ratios might improve nonformal school outcomes.
shortDOI: 10/f63z7b KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2015.01.001 10/f63z7b 2339240:76EQG2NV 2405685:LM7EYD5E 2405685:WU59KPEH 261495:QBFNURGR
Keywords: AWP2; C:Kenya; CitedIn:AKFC; CitedIn:OER4Schools-HHH3-B; Coaching; Instruction; Kenya; Literacy; PRIMR; professional development

Supporting teachers learning through the collaborative design of technology-enhanced science lessons - Kafyulilo, Ayoub C.; Fisser, Petra; Voogt, Joke (Journal of Science Teacher Education, 2015)
This study used the Interconnected Model of Professional Growth (Clarke & Hollingsworth in Teaching and Teacher Education, 18, 947–967, 2002) to unravel how science teachers’ technology integration knowledge and skills developed in a professional development arrangement. The professional development arrangement used Technological Pedagogical Content Knowledge as a conceptual framework and included collaborative design of technology-enhanced science lessons, implementation of the lessons and reflection on outcomes. Support to facilitate the process was offered in the form of collaboration guidelines, online learning materials, exemplary lessons and the availability of an expert. Twenty teachers participated in the intervention. Pre- and post-intervention results showed improvements in teachers’ perceived and demonstrated knowledge and skills in integrating technology in science teaching. Collaboration guidelines helped the teams to understand the design process, while exemplary materials provided a picture of the product they had to design. The availability of relevant online materials simplified the design process. The expert was important in providing technological and pedagogical support during design and implementation, and reflected with teachers on how to cope with problems met during implementation.
Publisher: Routledge _eprint: https://doi.org/10.1007/s10972-015-9444-1 KerkoCite.ItemAlsoKnownAs: 10.1007/s10972-015-9444-1 2339240:G8S6AKP2 2405685:3EYMBZ8B
Keywords: Design teams; Interconnected model of professional growth; Professional development; Support; TPACK; Teachers; Technology

Supporting teachers learning through the collaborative design of technology-enhanced science lessons - Kafyulilo, Ayoub C.; Fisser, Petra; Voogt, Joke (Journal of Science Teacher Education, 2015)
This study used the Interconnected Model of Professional Growth (Clarke & Hollingsworth in Teaching and Teacher Education, 18, 947–967, 2002) to unravel how science teachers’ technology integration knowledge and skills developed in a professional development arrangement. The professional development arrangement used Technological Pedagogical Content Knowledge as a conceptual framework and included collaborative design of technology-enhanced science lessons, implementation of the lessons and reflection on outcomes. Support to facilitate the process was offered in the form of collaboration guidelines, online learning materials, exemplary lessons and the availability of an expert. Twenty teachers participated in the intervention. Pre- and post-intervention results showed improvements in teachers’ perceived and demonstrated knowledge and skills in integrating technology in science teaching. Collaboration guidelines helped the teams to understand the design process, while exemplary materials provided a picture of the product they had to design. The availability of relevant online materials simplified the design process. The expert was important in providing technological and pedagogical support during design and implementation, and reflected with teachers on how to cope with problems met during implementation.
Publisher: Routledge _eprint: https://doi.org/10.1007/s10972-015-9444-1 KerkoCite.ItemAlsoKnownAs: 10.1007/s10972-015-9444-1 10/gf7gx7 2339240:BKA45HWC 2339240:F3ZCM7SP 2405685:RNWUSFG4 2534378:325RP7HZ 2534378:8BHL2SZV 2534378:DDGZAF8Q 2534378:U7WD44V7 2534378:UWU5LPCD
Keywords: Design teams; Interconnected model of professional growth; Professional development; Support; TPACK; Teachers; Technology; _Source:Intuitive; _THEME: Open systems; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2425910; __finaldtb

Supporting teachers learning through the collaborative design of technology-enhanced science lessons - Kafyulilo, Ayoub C.; Fisser, Petra; Voogt, Joke (Journal of Science Teacher Education, 2015)
This study used the Interconnected Model of Professional Growth (Clarke & Hollingsworth in Teaching and Teacher Education, 18, 947–967, 2002) to unravel how science teachers’ technology integration knowledge and skills developed in a professional development arrangement. The professional development arrangement used Technological Pedagogical Content Knowledge as a conceptual framework and included collaborative design of technology-enhanced science lessons, implementation of the lessons and reflection on outcomes. Support to facilitate the process was offered in the form of collaboration guidelines, online learning materials, exemplary lessons and the availability of an expert. Twenty teachers participated in the intervention. Pre- and post-intervention results showed improvements in teachers’ perceived and demonstrated knowledge and skills in integrating technology in science teaching. Collaboration guidelines helped the teams to understand the design process, while exemplary materials provided a picture of the product they had to design. The availability of relevant online materials simplified the design process. The expert was important in providing technological and pedagogical support during design and implementation, and reflected with teachers on how to cope with problems met during implementation.
Publisher: Routledge _eprint: https://doi.org/10.1007/s10972-015-9444-1 KerkoCite.ItemAlsoKnownAs: 10.1007/s10972-015-9444-1 2339240:G8S6AKP2 2405685:3EYMBZ8B
Keywords: Design teams; Interconnected model of professional growth; Professional development; Support; TPACK; Teachers; Technology

Promoting Student–Teacher Interactions: Exploring a Peer Coaching Model for Teachers in a Preschool Setting - Johnson, Stacy R.; Finlon, Kristy J.; Kobak, Roger; Izard, Carroll E. (Early Childhood Education Journal, 2017)
Peer coaching provides an attractive alternative to traditional professional development for promoting classroom quality in a sustainable, cost-effective manner by creating a collaborative teaching community. This exploratory study describes the development and evaluation of the Colleague Observation And CoacHing (COACH) program, a peer coaching program designed to increase teachers’ effectiveness in enhancing classroom quality in a preschool Head Start setting. The COACH program consists of a training workshop on coaching skills and student-teacher interactions, six peer coaching sessions, and three center meetings. Pre-post observations of emotional support, classroom organization, and instructional support using the Classroom Assessment Scoring System of twelve classrooms assigned to peer coaching were compared to twelve control classrooms at baseline and following the intervention. Findings provide preliminary support that the peer coaching program is perceived as acceptable and feasible by the participating preschool teachers and that it may strengthen student–teacher interactions. Further program refinement and evaluation with larger samples is needed to enhance student–teacher interactions and, ultimately, children’s adaptive development.
shortDOI: 10/gbjks7 KerkoCite.ItemAlsoKnownAs: 10.1007/s10643-016-0790-1 10/gbjks7 2405685:5SRMZ3SD
Keywords: Classroom quality; Head Start; Peer coaching; Professional development; Professional learning communities; Student–teacher interactions

Digital literacies for international teacher education: a Ghanaian perspective - Taner, Lisa (The Open University, 2018)
Teacher education in Sub Saharan Africa has been highlighted as key in helping to ensure inclusive and equitable quality education across the continent. Digital technologies that support new modes of teacher education can improve access and quality in developing regions (Moon and Villet, 2017a, b; Moon, 2007; Power, 2013), however little is known about how teachers develop digital literacies to enable them to effectively use these new resources, nor the ways in which student teachers are introduced to the technologies they need to support their professional development. Given the scarcity of research in this area and with teacher support and preparation having been the least examined topics in mobile learning research, this project investigated the ways in which student teachers in one College of Education in Ghana participate in learning experiences that develop their digital literacies to support their professional development throughout the college course, both on campus and in school placements. Using ethnographic approaches within a sociocultural theoretical rationale, the aim of this research was to address the gap in literature by examining the ways in which student teachers participate in learning experiences that develop their digital literacies during their training at a College of Education in Ghana. In view of the slow pace of ICT infrastructure advancement in Ghanaian schools, tutors at one college of education are encouraging the use of student teachers’ personal devices such as mobile phones to support their professional learning, both on campus and in the absence of other equipment in school placements. Smartphone use was found to be an enabling tool for students, whose formal and informal use of communication tools such as WhatsApp supported their developing professionalism and gave them access to new ways to locate and use materials for teaching and their wider professional development, including the academic requirements of their courses.
http://oro.open.ac.uk/54964/ KerkoCite.ItemAlsoKnownAs: 2339240:6I3C4XC6 2405685:UFXME9DD
Keywords: THEME: Curriculum and resources; THEME: Education management; THEME: Open systems; THEME: School management; THEME: Teacher Professional Development; _Source:Intuitive; ___working_potential_duplicate

Digital literacies for international teacher education: a Ghanaian perspective - Taner, Lisa (The Open University, 2018)
Teacher education in Sub Saharan Africa has been highlighted as key in helping to ensure inclusive and equitable quality education across the continent. Digital technologies that support new modes of teacher education can improve access and quality in developing regions (Moon and Villet, 2017a, b; Moon, 2007; Power, 2013), however little is known about how teachers develop digital literacies to enable them to effectively use these new resources, nor the ways in which student teachers are introduced to the technologies they need to support their professional development. Given the scarcity of research in this area and with teacher support and preparation having been the least examined topics in mobile learning research, this project investigated the ways in which student teachers in one College of Education in Ghana participate in learning experiences that develop their digital literacies to support their professional development throughout the college course, both on campus and in school placements. Using ethnographic approaches within a sociocultural theoretical rationale, the aim of this research was to address the gap in literature by examining the ways in which student teachers participate in learning experiences that develop their digital literacies during their training at a College of Education in Ghana. In view of the slow pace of ICT infrastructure advancement in Ghanaian schools, tutors at one college of education are encouraging the use of student teachers’ personal devices such as mobile phones to support their professional learning, both on campus and in the absence of other equipment in school placements. Smartphone use was found to be an enabling tool for students, whose formal and informal use of communication tools such as WhatsApp supported their developing professionalism and gave them access to new ways to locate and use materials for teaching and their wider professional development, including the academic requirements of their courses.
http://oro.open.ac.uk/54964/ KerkoCite.ItemAlsoKnownAs: 2339240:6I3C4XC6 2405685:UFXME9DD
Keywords: THEME: Curriculum and resources; THEME: Education management; THEME: Open systems; THEME: School management; THEME: Teacher Professional Development; _Source:Intuitive; ___working_potential_duplicate

The potential of MOOCs for large-scale teacher professional development in contexts of mass displacement - Kennedy, Eileen; Laurillard, Diana (London Review of Education, 2019)
The mass displacement of people across the world, currently estimated at 65 million, creates a massive demand for new forms of education for children, young people and adults. However, this cannot be addressed without attending to what this means for teachers and other professionals involved in education and training. Clearly, there is a need for large-scale teacher professional development (TPD). Digital technology has the potential to meet this demand, but challenges are presented by the poor digital infrastructure in contexts of mass displacement. Data from two projects are analysed to explore the viability of scaling up TPD in the form of co-designed massive open online courses (MOOCs). The first data set is from a co-designed TPD MOOC project Blended Learning Essentials, to show that digital technology can be effective for scaling up TPD, but that a sustainability plan must be in place from the outset. The second data set is from a project that built on the first to run stakeholder co-design workshops in Lebanon, as a way of developing large-scale TPD in this most challenging context. Lebanon has the highest proportion of refugee to host communities in the world. This case study indicates that MOOCs could be viable in such a context, but also highlights the need to balance the generic principles being offered with a focus on localized practice. A theory of change is presented to outline a method of meeting these challenges by employing a co-design methodology to create self-sustaining digital TPD in the context of Lebanon, and to test this model with the contexts of mass displacement experienced by other participants in the MOOC.
Publisher: UCL IOE Press shortDOI: 10/gg39w8 KerkoCite.ItemAlsoKnownAs: 10.18546/LRE.17.2.04 10.18546/lre.17.2.04 10/gg39w8 2339240:8UKVPWIZ 2339240:HI8ZPSQY 2339240:IQ8CXXW6 2405685:BPEFU8Q5 2405685:G4UWRHU7 2405685:HZVTXVSX 2534378:G73NNFJ5 2534378:SB3A7XEN 2534378:XASAZC2M
Keywords: BLENDED learning; CO DESIGN MOOCS REFUGEES TEACHERS THEORY OF CHANGE; DIGITAL technology; Design; Digital technology; Education; Google Scholar/ "blended learning" refugee education; Lebanon; MASSIVE open online courses; MOOCs; Online instruction; PROFESSIONAL education; Professional development; RER theme_supporting educators; TEACHER development; __:import:01; __:match:final; __:matched; __:study_id:2095772; ___working_potential_duplicate; __finaldtb; co-design; refugees; teachers; theory of change

Examining sustained impacts of two teacher professional development programs on professional well-being and classroom practices - Wolf, Sharon; Peele, Morgan E. (Teaching and Teacher Education, 2019)
We examine second-year impacts of a 1-year pre-primary teacher training and coaching program, delivered with and without parental-awareness meetings, evaluated with a school-level randomized trial. Outcomes included teachers’ professional well-being and classroom practices. Most gains observed during the program year faded out. However, there were small sustained impacts on the implementation of training activities. Counteracting effects of the parental-awareness meetings were evident, with suggestive evidence that teachers in this treatment group displayed lower scores on one dimension of classroom qualitydSupporting Student Expressiondcompared to controls. Implications for professional development and educational quality are discussed.
shortDOI: 10/ggjk6c KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2019.07.003 10/ggjk6c 2339240:GB3MPNJU 2405685:M8ZR3GRF
Keywords: _proposed-for: Scoping review

Not just for special occasions: supporting the professional learning of teachers through critical reflection with audio-visual information - Saito, Eisuke; Khong, Thi Diem Hang (Reflective Practice, 2017)
Despite increased use of professional learning communities in the teacher education field, they do not necessarily guarantee change in teachers’ daily practice. This study is a multiple case study of three school leaders in Vietnam to connect their teachers’ learning and practice by utilising visual records. In the cases studied, we see a progression of models of joint reflection based on visual information, from only occasional reflection to daily critical reflection, the latter of which the authors call ‘vide-flection’ referring to a process for people to consider their actions, thoughts, or experiences by utilising video-recorded images. For joint vide-flection, school leaders visit every classroom for several minutes every day to observe the wellbeing and learning of pupils and video-record struggles or breakthroughs in children’s learning; they share those images with teachers to jointly reflect on the situations. Through this vide-flection, teachers develop more detailed awareness of pupils needs.
Publisher: Routledge _eprint: https://doi.org/10.1080/14623943.2017.1361921 KerkoCite.ItemAlsoKnownAs: 10.1080/14623943.2017.1361921 2339240:UPNEHQVJ 2405685:8CQU3AHD
Keywords: Reflective practice; Vietnam; critical reflection; professional learning; teacher professional development; vide-flection

Developing Great Teaching: Lessons from the international reviews into effective professional development - Cordingley, Philippa; Higgins, Steve; Coe, Rob; Greany, Toby; Buckler, N.; Coles-Jordan, D.; Crisp, B.; Saunders, L. (Teacher Development Trust, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:UQJ8GNC7 2405685:4CD9B9MI 2405685:LLH3AAD5 2534378:BF6I8W9B
Keywords: C:England / International; ___working_potential_duplicate

Teachers’ professional development for ICT integration: Towards a reciprocal relationship between research and practice - Albion, Peter R.; Tondeur, Jo; Forkosh-Baruch, Alona; Peeraer, Jef (Education and Information Technologies, 2015)
Publisher: Springer KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-015-9401-9 2339240:U649AIAT 2405685:2YQNCPBE

Pakistani Teacher-Educator Professional Learning through an International Blended Course - Impedovo, Maria Antonietta; Malik, Sufiana Khatoon (Open Praxis, 2019)
International teacher-educator learning supports a more complex vision of teacher professionalism for both developed and developing countries. The aim of this paper is the analysis of Pakistani teacher-educator professional learning after attending an international blended course, considering the impact of online and face-to-face participation and the main competencies involved in their professional learning. The blended learning course attended by the Pakistani Teacher-educators is part of an international project between Europe and Asia. The analysis is carried out using written traces in the online platform; 47 questionnaires at the end of the face-to-face training sessions in Pakistan and 10 deep-interviews with Pakistani educators; the written traces, open questions, and deep-interviews were qualitatively analyzed. Additionally, the educators' technological, pedagogical and instructional design and interpersonal and intercultural skills were also analysed. The paper considers how international learning could affect the professional learning of teacher-educators in Global South and the centrality of the design of innovative learning courses for today's environment of international globalization.
Publisher: International Council for Open and Distance Education KerkoCite.ItemAlsoKnownAs: 10.5944/openpraxis.11.2.928 2339240:YNGS2RBD 2405685:DLCJJKLI
Keywords: Blended Learning; Cultural Awareness; Faculty Development; Foreign Countries; Instructional Design; International Education; Interpersonal Competence; Professionalism; Skill Development; Teacher Educator Education; Teacher Educators; Teaching Skills; Technological Literacy

A case study of using an online community of practice for teachers' professional development at a secondary school in China - Wang, Qiyun; Lu, Zhiping (Learning, Media and Technology, 2012)
In this case study, an online community was designed at a secondary school in China for the teachers to prepare their lessons collectively, reflect on their teaching practices, collect comments from peers, and share resources. A survey was administered to the teachers to investigate their perceptions on the online community for their professional development. Two hundred and eighty-three teachers responded to the survey and eight teachers were further interviewed by email. The result showed that most teachers liked using the online community as they could gain subject knowledge and could obtain support from peers, share experiences and get feedback, and exchange resources. Also, online entries confirmed that transformational changes in teaching pedagogy and students' learning activities occurred along the time. However, certain teachers did not participate in the online community frequently. This paper describes the context of the case study, design dimensions of the online community, teachers' positive perceptions on using the online community, and transformational changes. Also, strategies for promoting effective use of the online community are discussed and follow-up studies to address the challenges involved in this study are proposed. [PUBLICATION ABSTRACT]
Place: Basingstoke Publisher: Taylor & Francis Ltd. Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1240554543?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1080/17439884.2012.685077 2339240:IW35GJG8 2405685:5KA76IR7 2405685:5UJZ5TUP 2534378:7P96MCEU 2534378:I2ZKMFEE 2534378:TEPS99BX
Keywords: Case Studies; China; Communities of Practice; Distance Education; ERIC; Current Index to Journals in Education (CIJE); Education–Teaching Methods And Curriculum; Educational Practices; Electronic Learning; Electronic Mail; Foreign Countries; Interviews; Learning; Lesson Plans; Mail Surveys; Online instruction; Participant Satisfaction; Pedagogy; Polls & surveys; Professional Development; Professional development; Secondary Education; Secondary School Teachers; Secondary school teachers; Teacher Surveys; Teaching Methods; Technology Uses in Education; Transformative Learning; __:import:01; __:match:final; __:matched; __:study_id:2096477; __finaldtb; community of practice; lesson planning; professional development; reflection; technology

Designing a program of teacher professional development to support beginning reading acquisition in coastal Kenya - Dubeck, Margaret M.; Jukes, Matthew C.H.; Brooker, Simon J.; Drake, Tom L.; Inyega, Hellen N. (International Journal of Educational Development, 2015)
What should be considered when developing a literacy intervention that asks teachers to implement new instructional methods? How can this be achieved with minimal support within existing policy? We argue that two broad sets of considerations must be made in designing such an intervention. First, the intervention must be effective by bridging the gap between current teacher practice and the scientiﬁc literature on effective instruction. This broad consideration is detailed with 10 design recommendations. Second, the intervention must be amenable to being scaled-up and mainstreamed as part of government policy. This involves being (i) simple and replicable; (ii) well received by teachers; and (iii) cost effective. The paper describes how these factors were considered in the design of a literacy intervention in government primary schools in coastal Kenya. It also includes reactions from teachers about the intervention and their change in knowledge.
shortDOI: 10/f7fghr KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2014.11.022 10/f7fghr 2405685:4WTUAF8V 2405685:USCCYKCK 2534378:5GJ88R44 2534378:DLHXICEY 2534378:NIUAY2PP
Keywords: ADULTS; BEST practices; EDUCATION; EDUCATIONAL innovations; EDUCATIONAL intervention; ELEMENTARY education; KENYA; Kenya; LITERACY; Literacy; Perception; Reading instruction; TEACHER development; TEACHING methods; Teacher education; Text messages; __:import:01; __:match:final; __:matched; __:study_id:2099920; ___working_potential_duplicate; __finaldtb

Designing a program of teacher professional development to support beginning reading acquisition in coastal Kenya - Dubeck, Margaret M.; Jukes, Matthew C.H.; Brooker, Simon J.; Drake, Tom L.; Inyega, Hellen N. (International Journal of Educational Development, 2015)
What should be considered when developing a literacy intervention that asks teachers to implement new instructional methods? How can this be achieved with minimal support within existing policy? We argue that two broad sets of considerations must be made in designing such an intervention. First, the intervention must be effective by bridging the gap between current teacher practice and the scientific literature on effective instruction. This broad consideration is detailed with 10 design recommendations. Second, the intervention must be amenable to being scaled-up and mainstreamed as part of government policy. This involves being (i) simple and replicable; (ii) well received by teachers; and (iii) cost effective. The paper describes how these factors were considered in the design of a literacy intervention in government primary schools in coastal Kenya. It also includes reactions from teachers about the intervention and their change in knowledge. [ABSTRACT FROM AUTHOR]
Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.ebscohost.com/login.aspx?direct=true&db=bri&AN=108296506&site=ehost-live&scope=site KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2014.11.022 2339240:B8GCJR9U 2405685:7W777384 2534378:5GJ88R44 2534378:DLHXICEY 2534378:NIUAY2PP
Keywords: ADULTS; BEST practices; EDUCATION; EDUCATIONAL innovations; EDUCATIONAL intervention; ELEMENTARY education; KENYA; Kenya; LITERACY; Literacy; Perception; Reading instruction; TEACHER development; TEACHING methods; Teacher education; Text messages; __:import:01; __:match:final; __:matched; __:study_id:2099920; __finaldtb

Live video classroom observation: an effective approach to reducing reactivity in collecting observational information for teacher professional development - Liang, Jiwen (Journal of Education for Teaching: International Research and Pedagogy, 2015)
This paper examines the significance of live video classroom observations of teaching practice to reduce reactivity (the observer effect) so as to obtain more credible observational information for teacher professional development in a secondary school in the largest city in southern China. Although much has been discussed regarding the use of remote live video classroom observation for professional development, the advantage of remote live video classroom observation in reducing reactivity has often been overlooked. Using the case study method, the research reported here focuses on two components: conducting live video classroom observation and the use of the live video classroom observation in reducing reactivity. This paper suggests that live video classroom observation is effective in reducing reactivity and helps avoid subjective judgement and increase feedback sources, thus providing a solution to compensate for the limitations of traditional classroom observations.
Publisher: Routledge, Available from: Taylor & Francis, Ltd. 325 Chestnut Street Suite 800, Philadelphia, PA 19106 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1720065888?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1080/02607476.2015.1045314 2405685:XGZM5SEC 2534378:69WEYDDC 2534378:6KGYG6GM 2534378:NCYRP586
Keywords: Administrator Attitudes; Case Studies; Case studies; China; Classroom Observation Techniques; Classroom observation; ERIC; Current Index to Journals in Education (CIJE); Education; Effectiveness; Faculty Development; Feedback; Feedback (Response); Foreign Countries; Interviews; Principals; Professional development; Qualitative Research; Secondary Education; Secondary School Teachers; Secondary schools; Teacher Attitudes; Teacher education; Teaching; Teaching Methods; Teaching methods; Video; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2096967; __finaldtb

Live video classroom observation: an effective approach to reducing reactivity in collecting observational information for teacher professional development - Liang, Jiwen (Journal of Education for Teaching: International Research and Pedagogy, 2015)
This paper examines the significance of live video classroom observations of teaching practice to reduce reactivity (the observer effect) so as to obtain more credible observational information for teacher professional development in a secondary school in the largest city in southern China. Although much has been discussed regarding the use of remote live video classroom observation for professional development, the advantage of remote live video classroom observation in reducing reactivity has often been overlooked. Using the case study method, the research reported here focuses on two components: conducting live video classroom observation and the use of the live video classroom observation in reducing reactivity. This paper suggests that live video classroom observation is effective in reducing reactivity and helps avoid subjective judgement and increase feedback sources, thus providing a solution to compensate for the limitations of traditional classroom observations.
Publisher: Routledge, Available from: Taylor & Francis, Ltd. 325 Chestnut Street Suite 800, Philadelphia, PA 19106 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1720065888?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1080/02607476.2015.1045314 2339240:VQ7H8WUD 2405685:63X8MEP4 2534378:69WEYDDC 2534378:6KGYG6GM 2534378:NCYRP586
Keywords: Administrator Attitudes; Case Studies; Case studies; China; Classroom Observation Techniques; Classroom observation; ERIC; Current Index to Journals in Education (CIJE); Education; Effectiveness; Faculty Development; Feedback; Feedback (Response); Foreign Countries; Interviews; Principals; Professional development; Qualitative Research; Secondary Education; Secondary School Teachers; Secondary schools; Teacher Attitudes; Teacher education; Teaching; Teaching Methods; Teaching methods; Video; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2096967; __finaldtb

Live video classroom observation: an effective approach to reducing reactivity in collecting observational information for teacher professional development - Liang, Jiwen (Journal of Education for Teaching: International Research and Pedagogy, 2015)
This paper examines the significance of live video classroom observations of teaching practice to reduce reactivity (the observer effect) so as to obtain more credible observational information for teacher professional development in a secondary school in the largest city in southern China. Although much has been discussed regarding the use of remote live video classroom observation for professional development, the advantage of remote live video classroom observation in reducing reactivity has often been overlooked. Using the case study method, the research reported here focuses on two components: conducting live video classroom observation and the use of the live video classroom observation in reducing reactivity. This paper suggests that live video classroom observation is effective in reducing reactivity and helps avoid subjective judgement and increase feedback sources, thus providing a solution to compensate for the limitations of traditional classroom observations.
Publisher: Routledge, Available from: Taylor & Francis, Ltd. 325 Chestnut Street Suite 800, Philadelphia, PA 19106 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1720065888?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1080/02607476.2015.1045314 2339240:VQ7H8WUD 2405685:63X8MEP4 2534378:69WEYDDC 2534378:6KGYG6GM 2534378:NCYRP586
Keywords: Administrator Attitudes; Case Studies; Case studies; China; Classroom Observation Techniques; Classroom observation; ERIC; Current Index to Journals in Education (CIJE); Education; Effectiveness; Faculty Development; Feedback; Feedback (Response); Foreign Countries; Interviews; Principals; Professional development; Qualitative Research; Secondary Education; Secondary School Teachers; Secondary schools; Teacher Attitudes; Teacher education; Teaching; Teaching Methods; Teaching methods; Video; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2096967; __finaldtb

Developing TPACK in science and mathematics teacher education in Tanzania: A proof of concept study - Kafyulilo, Ayoub; Fisser, Petra (Collaborative Curriculum Design for Sustainable Innovation and Teacher Learning, 2019)
Since 1997, the government of Tanzania has made several attempts at introducing technology into education. However, despite these efforts technology has not become integrated into educational practice. A main reason is that teachers do not embrace the use of technology in their teaching. This study was initiated to design, implement and evaluate a professional development arrangement aimed at promoting teachers’ use of technology in their teaching practice. The study started with a ‘proof of concept’ study. Based on experiences in Ghana and Kuwait, a professional development arrangement was developed that incorporated ‘learning technology by design’ to prepare pre-service science and math teachers for using technology in their teaching. The experiences from this study informed the design of a professional development arrangement for practicing science teachers. The iterative design, implementation and evaluation of the professional development arrangements will be presented and discussed.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-030-20062-6_8 2339240:MQPLNUJN 2405685:Z8QTSILA

Blog-based professional development of English teachers in Mumbai: the potential of innovative practice under scrutiny - Khan, Atiya (Australasian Journal of Educational Technology, 2017)
The professional development of teachers in India is still, by and large, based on formal and outdated professional learning traditions, often characterised by crash courses and one-off workshops. In education, blogs have proven to be an effective means of establishing and maintaining collaborative learning networks and helping members reflect on their professional practices. Information and communications technology (ICT) enabled practices of teacher professional development is still in its infancy in India. Moreover, there is limited research in India to secure foundational understanding of how and in what ways teachers of English in India use blogs for their professional development. This study explores the use of teacher reflective practice, teacher networking, and teacher collaboration, beyond formal ICT training, through blog-based professional development of English teachers in the Mumbai region of India. Using data collected from 32 teachers from three private schools in Mumbai, through ICT interactive workshop observations, questionnaires, interviews, and blog comments, this action case study explains whether and why blogging, as a learning community, has the potential to add significant value to existing professional development of English teachers in Mumbai.
Publisher: Australasian Society for Computers in Learning in Tertiary Education, Ascilite Secretariat, P.O. Box 44, Figtree, NSW, Australia Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1969007459?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.14742/ajet.2784 2405685:EPKS7TDM 2534378:MQYLKXN6 2534378:Y6KUBK5K
Keywords: Action Research; Case Studies; Communities of Practice; Diaries; ERIC; Current Index to Journals in Education (CIJE); Electronic Publishing; English (Second Language); Faculty Development; Foreign Countries; India; Language Teachers; Participant Observation; Private Schools; Qualitative Research; Questionnaires; Reflective Teaching; Second Language Instruction; Semi Structured Interviews; Teacher Collaboration; Web Sites; Workshops; __:import:01; __:match:final; __:matched; __:study_id:2096053; __finaldtb

Effective Teacher Professional Development - Darling-Hammond, Linda; Hyler, Maria E; Gardner, Madelyn (Learning Policy Institute, 2016)
Teacher professional learning is of increasing interest as one way to support the increasingly complex skills students need to succeed in the 21st century. However, many teacher professional development initiatives appear ineffective in supporting changes in teacher practices and student learning. To identify the features of effective professional development, this paper reviews 35 methodologically rigorous studies that have demonstrated a positive link between teacher professional development, teaching practices, and student outcomes. It identifies features of these approaches and offers descriptions of these models to inform those seeking to understand how to foster successful strategies.
KerkoCite.ItemAlsoKnownAs: 2339240:EXG2P88C 2339240:FAGZPTMD 2339240:KZWPKKEX 2405685:3EICVTPU 2405685:5UT4JT9U 2405685:7VUTJF44 2405685:DFJ5VQ9P 2405685:L5AA7H42 2534378:LEAZX89C 2534378:VMCMZ256
Keywords: C:United States / International; ___working_potential_duplicate; important; ⛔ No DOI found

Design-based online teacher professional development to introduce integration of STEM in Pakistan - Anwar, Tasneem (University of Minnesota, 2017)
In today's global society where innovations spread rapidly, the escalating focus on science, technology, engineering and mathematics (STEM) has quickly intensified in the United States, East Asia and much of Western Europe. Our ever-changing, increasingly global society faces many multidisciplinary problems, and many of the solutions require the integration of multiple science, technology, engineering, and mathematics (STEM) concepts. Thus, there is a critical need to explore the integration of STEM subjects in international education contexts. This dissertation study examined the exploration of integration of STEM in the unique context of Pakistan. This study used three-phase design-based methodological framework derived from McKenney and Reeves (2012) to explore the development of a STEM focused online teacher professional development (oTPD-STEM) and to identify the design features that facilitate teacher learning. The oTPD-STEM program was designed to facilitate eight Pakistani elementary school teachers' exploration of the new idea of STEM integration through both practical and theoretical considerations. This design-based study employed inductive analysis (Strauss and Corbin, 1998) to analyze multiple data sources of interviews, STEM perception responses, reflective learning team conversations, pre-post surveys and artifacts produced in oTPD-STEM. Findings of this study are presented as: (1) design-based decisions for oTPD-STEM, and (2) evolution in understanding of STEM by sharing participant teachers' STEM model for Pakistani context. This study advocates for the potential of school-wide oTPD for interdisciplinary collaboration through support for learner-centered practices. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]
ISBN: 9781369679038 Pages: 284 Publication Title: ProQuest LLC KerkoCite.ItemAlsoKnownAs: 2339240:9I4QVZDI 2339240:DBDFJKBJ 2339240:X7AAWQUH 2405685:4364Q9YV 2405685:FR3HXWGG 2405685:MRNCUA28 2405685:XZPKBXP2 2534378:CGYHJZSS 2534378:DN6N2JCI 2534378:JGZHHY6I 2534378:PULZXS5Y 2534378:VMIH94FH
Keywords: 0530:Teacher education; 0714:Science education; Attitude Measures; Community of practice; Design; Design-based research; ERIC; Resources in Education (RIE); Education; Educational Technology; Elementary Education; Elementary School Teachers; Faculty Development; Foreign Countries; Interdisciplinary Approach; Interviews; Models; Online Courses; Online teacher professional development; Pakistan; Reflective practices; STEM Education; Science education; Stem integration; Student Centered Learning; Teacher Attitudes; Teacher education; Technology Uses in Education; __:import:01; __:match:final; __:matched; __:study_id:2096054; __finaldtb

JiFUNzeni: a blended learning approach for sustainable teachers' professional development - Onguko, Brown Bully (Electronic Journal of e-Learning, 2014)
JiFUNzeni blended learning approach is a sustainable approach to provision of professional development (PD) for those in challenging educational contexts. JiFUNzeni approach emphasizes training regional experts to create blended learning content, working with appropriate technology while building content repositories. JiFUNzeni approach was fieldtested though a design-based research intervention conducted in rural western Kenya. The field test included design, development and implementation of a blended learning course for teachers’ professional development utilizing appropriate technologies including tablets powered by solar energy, open educational resources and open source software. One year after the intervention, follow-up interviews were conducted with eight of the ten teachers and two professional development tutors (PDTs) who participated in the research. The findings from the follow-up interviews shared in this paper revealed that: teachers still used cooperative learning and activity-based learning strategies in their teaching. The PDTs on the other hand designed, developed and implemented one other jiFUNzeni blended learning course for twelve teachers in one school in Korogocho slum in Nairobi city. Implementation by PDTs of jiFUNzeni approach confirmed that they had learned through a sustainable way of delivering professional development in challenging educational contexts. The PDTs utilized the instructional design approaches learned through their participation in the research in designing blended learning content, while they also innovated new ways of developing self-study content as an important creative addition to what they had previously learned. Two teenage children participated in digital content development by advising the PDTs on some appropriate ways of applying technology thus, attesting to the fact that digital natives are important reciprocal supporters to digital immigrants and vice versa.
KerkoCite.ItemAlsoKnownAs: 2339240:5SCGRA3U 2339240:M7R5EIZL 2339240:TS6R3E24 2339240:VWE52LMG 2339240:YMBURAH4 2405685:AKXHE6HE 2405685:Q3Y6Z65Z 2405685:U5WZEBXT 2405685:UNATTHSB 2405685:XVE57FFE 2534378:7WCVV8XM 2534378:DW5I8PW4 2534378:T6RRJMGR
Keywords: Blended Learning; Computer Software; Computers; Cooperative Learning; Cooperative learning; Course Content; Design; Disadvantaged Environment; Distance learning; Education–Computer Applications; Educational Technology; Elementary School Teachers; Faculty Development; Foreign Countries; Handheld Devices; Instructional Design; Internet; Interviews; Kenya; Learning Activities; Multimedia Materials; Open Source Technology; Program Development; Qualitative Research; Rural Areas; Self Evaluation (Individuals); Sustainability; Teacher Attitudes; Teaching Methods; Training; __:import:01; __:match:final; __:matched; __:study_id:2096405; ___working_potential_duplicate; __finaldtb; ⛔ No DOI found

Perspectives on technology, resources and learning: Productive classroom practices, effective teacher professional development - Haßler, Björn; Major, L.; Warwick, P.; Watson, S.; Hennessy, S.; Nicholl, B. (University of Cambridge, 2016)
EdTechHub.Source: 2129771:XWX767NR KerkoCite.ItemAlsoKnownAs: 2129771:XWX767NR 2339240:LXSZ3BDY 2405685:KP542JTW
Keywords: dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No DOI found

The Effect of Teachers' Professional Development in Video Technology on Mathematics and the English Language Learning of Preschoolers in a Rural Primary School in Pakistan. - Ikram, Hamid (2016)
The purpose of this mixed methods study was to examine the effect of teachers' professional development in video technology (PBS & Sesame Street videos) on mathematics and the English language learning among nursery students in the rural area of Pakistan where it was impossible for students to experience watching videos for learning purposes. This study showed teachers' motivation and frustration, before and after professional development, toward the use of video technology in the classroom. Also, this study showed the effect of learning videos assisted with games, coloring activities, and portfolios on student's English and mathematics' learning. The demographics of gender, socioeconomic status of the students, parents' education and occupation, learning resources at home for children, and the use of technology and media at home were contrasted to examine how they affect students learning of mathematics and English. The participants of the study were 80 nursery students and two English and math teachers in a rural primary school of Punjab province in Pakistan. Data were collected through a semi-structured interview protocol, biographical survey, and English and math tests. The demographic characteristics of the participants revealed that there were 55 percent female students and 45 percent male students ranging in age from 4 to 6 years. The demographics also revealed that 81 percent of the students belonged to households that had not more than $100 income per month. The findings supported that a majority of the students belonged to low socioeconomic status (SES), and fathers were the main source of household income. The findings showed that fathers' level of education was higher than that of the mothers' level of education. The effective delivery of the content with videos and students' engagement motivated teachers. The use of videos remarkably enhanced students' learning of math numbers and English alphabet in experimental classrooms. However, the lack of funds and technology training was the biggest frustration for teachers. The findings from this research contributed to the literature about teachers' professional development and use of learning media. The findings also identified the reasons behind teachers' frustration and motivation to bring technology in the classroom. Consequently, these study findings informed administrators, teachers, and parents to improve existing teaching and learning practices at early education level in Pakistan. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]
KerkoCite.ItemAlsoKnownAs: 2339240:FLFX5IGI 2339240:GEMLTXYF 2405685:KFYBLHY6 2405685:RP6L4XQU
Keywords: Educational Media; Educational Technology; Elementary School Teachers; English Language Learners; Foreign Countries; Mathematics Education; Mathematics Instruction; Mixed Methods Research; Pakistan; Preschool Children; Professional Development; Rural Schools; Second Language Learning; Semi Structured Interviews; Surveys; Technology Uses in Education; Video Technology

The ‘trainer in your pocket’: mobile phones within a teacher continuing professional development program in Bangladesh - Walsh, Christopher S.; Power, Tom; Khatoon, Masuda; Biswas, Sudeb Kumar; Paul, Ashok Kumar; Sarkar, Bikash Chandra; Griffiths, Malcolm (Professional Development in Education, 2013)
shortDOI: 10/gftr32 KerkoCite.ItemAlsoKnownAs: 10.1080/19415257.2013.766232 10/gftr32 2405685:WABHFRL5
Keywords: ___working_potential_duplicate

The ‘trainer in your pocket’: mobile phones within a teacher continuing professional development program in Bangladesh - Walsh, Christopher S.; Power, Tom; Khatoon, Masuda; Biswas, Sudeb Kumar; Paul, Ashok Kumar; Sarkar, Bikash Chandra; Griffiths, Malcolm (Professional Development in Education, 2013)
shortDOI: 10/gftr32 KerkoCite.ItemAlsoKnownAs: 10.1080/19415257.2013.766232 10/gftr32 2405685:WABHFRL5
Keywords: ___working_potential_duplicate

The ‘trainer in your pocket’: mobile phones within a teacher continuing professional development program in Bangladesh - Walsh, Christopher S.; Power, Tom; Khatoon, Masuda; Biswas, Sudeb Kumar; Paul, Ashok Kumar; Sarkar, Bikash Chandra; Griffiths, Malcolm (Professional Development in Education, 2013)
KerkoCite.ItemAlsoKnownAs: 10/gftr32 2339240:CKY3C4AK 2405685:7I9NQ7GL
Keywords: ___working_potential_duplicate

MOOCs as an alternative for teacher professional development: examining learner persistence in one Chinese MOOC - Wang, Qiong; Chen, Bodong; Fan, Yizhou; Zhang, Guogang (Peking University, 2018)
Massive Open Online Courses (MOOCs) have developed into a significant international movement, showing great promise in addressing equity, quality, and efficiency issues in global education. To date, many MOOCs have been developed specifically for teacher professional development (TPD). In this regard, an important empirical question remains to be addressed: How and to what extent can MOOCs support equity, quality, and efficiency in teacher professional development? To help fill this knowledge gap, this study, conducted from 2014 to 2016, focused on persistent teacher-learners in a TPD MOOC that was offered for seven consecutive rounds by the X-Learning Center of Peking University. The study found that more than 15% of the 105,383 teachers who enrolled in this MOOC were persistent teacher-learners, defined as learners who enrolled in multiple rounds. Data analysis showed that these persistent teacher-learners had diverse motivations for re-enrollment, including refreshing conceptual understanding, achieving higher scores, earning course certification, and discussing practical problems. The study also found that the persistent teacher-learners developed self-regulated learning skills in the course of multiple rounds of the MOOC and showed significantly higher learning achievement than one-time enrollees. Qualitative and quantitative analysis of both clicklog data and interview data revealed additional insights into the persistent teacher-learners’ learning within the MOOC and their real-world teaching practice beyond the MOOC. Overall, this study contributes to an improved understanding of the potential of MOOCs as an alternative TPD delivery mode in developing countries and sheds light on the future design of effective TPD through MOOCs.
Publisher: Foundation for Information Technology Education and Development, Inc.(FIT-ED) KerkoCite.ItemAlsoKnownAs: 2339240:8MN7IEZ9 2405685:3UKER6KZ 2405685:S4HRXBMD 2534378:KW6CG8KS 2534378:WIIQZEB5
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2425977; __finaldtb; tpdsysrev_potential_duplicate; ⛔ No DOI found

Theme 5: Teaching and Learning Materials (Professional Development Guide For Student Teachers) - T-TEL Professional Development Programme (Ministry of Education (Ghana), 2016)
EdTechHub.ItemAlsoKnownAs: 2405685:Q6V7CX64

Localizing OER in Afghanistan: Developing a Multilingual Digital Library for Afghan Teachers - Oates, Lauryn; Hashimi, Jamshid (Open Praxis, 2016)
The Darakht-e Danesh (‘knowledge tree’) Online Library is the first open educational resource (OER) initiative in Afghanistan, established to enhance teacher subject-area knowledge, access and use of learning materials, and to foster more diverse teaching methodologies in order to improve learning outcomes in Afghan classrooms. This paper describes our experience developing this local language digital library, buildings its responsiveness to our audience of users as we progressed, customizing both the interface and the resources for Afghanistan’s education environment. We innovated methods to devise relevant local content, localized usability, developed different access models to reach different populations of users, integrated impact measurement, and opted to openly license material in the library’s collection. By making digital educational content open from the first introduction of digital repositories of learning objects in Afghan languages, we have an opportunity to establish the principle of openness and to promote open practices in teacher professional development in Afghanistan. The paper aims to share lessons on how OER can be customized for multilingual, resource-scarce contexts drawing from our experience to date in Afghanistan, and seeking to contribute to the literature on localization and multilingual OER.
Number: 2 shortDOI: 10/gg26fk KerkoCite.ItemAlsoKnownAs: 10.5944/openpraxis.8.2.288 10/gg26fk 2339240:C7TTPCLP 2339240:PYPNI5CG 2405685:6JQMFU42 2405685:GL8KDFQU 4803016:FHBDTUMJ
Keywords: Afghanistan; OER; language; localization; open access; teacher education; teacher professional development; teaching and learning materials

Teacher professional development using mobile technologies in a large-scale project: lessons learned from Bangladesh - Shrestha, Prithvi (International Journal of Computer-Assisted Language Learning and Teaching (IJCALLT), 2012)
Publisher: IGI Global KerkoCite.ItemAlsoKnownAs: 10.4018/ijcallt.2012100103 10/gftr3z 2339240:6D45UDBE 2405685:SU6CDMZY 2534378:KGBGU7A7 2534378:LQMP437N

Reforming teacher education in Nigeria: Laying a foundation for the future - Barnes, Adrienne E.; Boyle, Helen; Zuilkowski, Stephanie Simmons; Bello, Zaliha Nasiruddeen (Teaching and Teacher Education, 2019)
Teacher educators in Nigeria receive limited professional development, particularly regarding the instruction of early grade reading skills. As part of the USAID-funded Northern Education Initiative Plus project, Florida State University faculty provided intensive teacher educator professional development to staff at four Teacher Education Institutions in northern Nigeria. Positive impacts on teacher educator knowledge, skills, and attitudes were observed related to content and pedagogical knowledge, use of participatory teaching and learning activities in the college classrooms, and improvement in student teacher engagement and learning. Continued success of the implemented model for training will be dependent upon national adoption and scale up.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2018.12.017 2339240:982EMD2L 2405685:7EPWKCK2

Teacher peer support in social network sites - Kelly, Nick; Antonio, Amy (Teaching and Teacher Education, 2016)
This paper describes the types of support that teachers are accessing through the Social Network Site (SNS) ‘Facebook’. It describes six ways in which teachers support one another within online groups. It presents evidence from a study of a large, open group of teachers online over a twelve week period, repeated with multiple groups a year later over a one week period. The findings suggest that large open groups in SNSs can be a useful source of pragmatic advice for teachers but that these groups are rarely a place for reflection on or feedback about teaching practice.
shortDOI: 10/f8np5n KerkoCite.ItemAlsoKnownAs: 10/f8np5n 2405685:FHCG5UYK
Keywords: Beginning teacher; Facebook; Natural language processing; Online professional development; Social network; Teacher; Teacher education

Characteristics of effective teacher professional development: what we know, what we don’t, how we can find out - Sims, Sam; Fletcher-Wood, Harry (2018)
Several influential reviews and one meta-review have converged on the position that teacher professional development (PD) is more effective when it is: sustained, collaborative, subject-specific, draws on external expertise, has buy-in from teachers and is practice-based. This consensus view has now been incorporated in government policy and official guidance in several countries. Despite this, several recent PD programmes incorporating these characteristics have failed to have any detectable impact on pupil attainment. This article reviews the evidence underpinning the consensus, arguing that the reviews on which it based are methodologically flawed because they employ inappropriate exclusion criteria and depend on an invalid inference method. The consensus view is therefore likely to be inaccurate. Researchers would make more progress on identifying characteristics of effective professional development by looking for alignment between evidence from basic research on human skill acquisition and features of rigorously-evaluated PD interventions.
KerkoCite.ItemAlsoKnownAs: 2339240:2VB6UKTN 2405685:75VHL4AH 2405685:UH59JRDH
Keywords: C:International; CitedIn:OER4Schools-HHH3-A; ⛔ No DOI found

Not just for special occasions: supporting the professional learning of teachers through critical reflection with audio-visual information - Saito, Eisuke; Khong, Thi Diem Hang (Reflective Practice, 2017)
Despite increased use of professional learning communities in the teacher education field, they do not necessarily guarantee change in teachers’ daily practice. This study is a multiple case study of three school leaders in Vietnam to connect their teachers’ learning and practice by utilising visual records. In the cases studied, we see a progression of models of joint reflection based on visual information, from only occasional reflection to daily critical reflection, the latter of which the authors call ‘vide-flection’ referring to a process for people to consider their actions, thoughts, or experiences by utilising video-recorded images. For joint vide-flection, school leaders visit every classroom for several minutes every day to observe the wellbeing and learning of pupils and video-record struggles or breakthroughs in children’s learning; they share those images with teachers to jointly reflect on the situations. Through this vide-flection, teachers develop more detailed awareness of pupils needs. [ABSTRACT FROM PUBLISHER]
Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.ebscohost.com/login.aspx?direct=true&db=bri&AN=126003617&site=ehost-live&scope=site KerkoCite.ItemAlsoKnownAs: 10.1080/14623943.2017.1361921 2405685:BC5IPJP7 2534378:8GYBJJ8Z 2534378:R2HCJDDM
Keywords: ADULTS; AUDIOVISUAL aids in education; AUDIOVISUAL materials; CRITICAL thinking studies; DATA analysis software; DESCRIPTIVE statistics; EDUCATION; FOCUS groups; INTERVIEWING; PROFESSIONAL education; PROFESSIONAL employee training; REFLECTION (Philosophy); RESEARCH funding; Reflective practice; SCHOOL administrators; TEACHER training; TEACHING; THEMATIC analysis; VIETNAM; Vietnam; __:import:01; __:match:final; __:matched; __:study_id:2099873; __finaldtb; critical reflection; professional learning; teacher professional development; vide-flection

Pakistani Teachers' Professional Learning Experiences: Comparing Face-to-Face versus Online Learning - Khan, Asma (TEFLIN Journal, 2018)
This qualitative in-depth interview study investigated the experiences of Pakistani English teachers in an online community, English Companion Ning (ECN). The main purpose of the study was to investigate what ECN meant to these Pakistani teachers and how they found their professional learning experiences different in ECN from face-to-face professional development programs in Pakistan. Data were gathered from six teachers through in-depth interviews, guided tours, field notes, memos, and ECN logs. Using the grounded theory approach, this study analyzed and interpreted the data through initial, focused, and axial coding. Data analysis revealed that being free from budget, temporal, and geographical constraints, the ECN provided numerous opportunities to the Pakistani teachers for a sustained and long-term professional learning in a collaborative setting.
Publisher: Association for the Teaching of English as a Foreign Language in Indonesia (TEFLIN), Malang, East Java, 65145, Indonesia. TEFLIN Publication Division, Department of English, Faculty of Letters, Universitas Negeri Malang, Jalan Semarang 5, KerkoCite.ItemAlsoKnownAs: 10.15639/teflinjournal.v29i1/72-89 10/gj37jn 2339240:J3T4EMAA 2405685:TIQ5LA4J 2534378:HL4Q7FGA 2534378:ML6MLI5W 2534378:SQISWDJS
Keywords: Collaboration; College Faculty; Communities of Practice; Comparative Analysis; Computer assisted language learning; Computer mediated communication; Conventional Instruction; Cooperative Learning; Cooperative learning; Distance learning; ERIC; Current Index to Journals in Education (CIJE); Educational technology; Electronic Learning; English Teachers; English as a second language–ESL; English teachers; Faculty Development; Foreign Countries; Grounded Theory; Higher Education; Interaction; Learning Experience; Linguistics; Pakistan; Professional development; Teacher Attitudes; Teacher education; Teaching; Technology Uses in Education; Web Based Instruction; __:import:01; __:match:final; __:matched; __:study_id:2095920; ___working_potential_duplicate

Pakistani teachers' professional learning experiences: comparing face-to-face versus online learning - Khan, Asma (TEFLIN Journal, 2018)
This qualitative in-depth interview study investigated the experiences of Pakistani English teachers in an online community, English Companion Ning (ECN). The main purpose of the study was to investigate what ECN meant to these Pakistani teachers and how they found their professional learning experiences different in ECN from face-to-face professional development programs in Pakistan. Data were gathered from six teachers through in-depth interviews, guided tours, field notes, memos, and ECN logs. Using the grounded theory approach, this study analyzed and interpreted the data through initial, focused, and axial coding. Data analysis revealed that being free from budget, temporal, and geographical constraints, the ECN provided numerous opportunities to the Pakistani teachers for a sustained and long-term professional learning in a collaborative setting.
Publisher: Association for the Teaching of English as a Foreign Language in Indonesia (TEFLIN), Malang, East Java, 65145, Indonesia. TEFLIN Publication Division, Department of English, Faculty of Letters, Universitas Negeri Malang, Jalan Semarang 5, Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2101887305?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.15639/teflinjournal.v29i1/72-89 2405685:XI6TS4S3 2534378:HL4Q7FGA 2534378:ML6MLI5W 2534378:SQISWDJS
Keywords: Collaboration; College Faculty; Communities of Practice; Comparative Analysis; Computer assisted language learning; Computer mediated communication; Conventional Instruction; Cooperative Learning; Cooperative learning; Distance learning; ERIC; Current Index to Journals in Education (CIJE); Educational technology; Electronic Learning; English Teachers; English as a second language–ESL; English teachers; Faculty Development; Foreign Countries; Grounded Theory; Higher Education; Interaction; Learning Experience; Linguistics; Pakistan; Professional development; Teacher Attitudes; Teacher education; Teaching; Technology Uses in Education; Web Based Instruction; __:import:01; __:match:final; __:matched; __:study_id:2095920; ___working_potential_duplicate

Pakistani teachers' professional learning experiences: comparing face-to-face versus online learning - Khan, Asma (TEFLIN Journal, 2018)
This qualitative in-depth interview study investigated the experiences of Pakistani English teachers in an online community, English Companion Ning (ECN). The main purpose of the study was to investigate what ECN meant to these Pakistani teachers and how they found their professional learning experiences different in ECN from face-to-face professional development programs in Pakistan. Data were gathered from six teachers through in-depth interviews, guided tours, field notes, memos, and ECN logs. Using the grounded theory approach, this study analyzed and interpreted the data through initial, focused, and axial coding. Data analysis revealed that being free from budget, temporal, and geographical constraints, the ECN provided numerous opportunities to the Pakistani teachers for a sustained and long-term professional learning in a collaborative setting.
Publisher: Association for the Teaching of English as a Foreign Language in Indonesia (TEFLIN), Malang, East Java, 65145, Indonesia. TEFLIN Publication Division, Department of English, Faculty of Letters, Universitas Negeri Malang, Jalan Semarang 5, Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2101887305?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.15639/teflinjournal.v29i1/72-89 2405685:5TV4QEFU 2534378:HL4Q7FGA 2534378:ML6MLI5W 2534378:SQISWDJS
Keywords: Collaboration; College Faculty; Communities of Practice; Comparative Analysis; Computer assisted language learning; Computer mediated communication; Conventional Instruction; Cooperative Learning; Cooperative learning; Distance learning; ERIC; Current Index to Journals in Education (CIJE); Educational technology; Electronic Learning; English Teachers; English as a second language–ESL; English teachers; Faculty Development; Foreign Countries; Grounded Theory; Higher Education; Interaction; Learning Experience; Linguistics; Pakistan; Professional development; Teacher Attitudes; Teacher education; Teaching; Technology Uses in Education; Web Based Instruction; __:import:01; __:match:final; __:matched; __:study_id:2095920; ___working_potential_duplicate

A short guide on the use of technology in learning: Perspectives and toolkit for discussion - Haßler, Björn; Major, L; Warwick, P; Watson, S; Hennessy, S; Nichol, B (University of Cambridge, 2016)
Perspectives on Technology, Resources and Learning - Productive Classroom Practices, Effective Teacher Professional Development
EdTechHub.Source: 2129771:IEVE675M shortDOI: 10/ghgk6j KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.2626660 10/ghgk6j 2129771:IEVE675M 2339240:VNSW8D9S 2405685:D2DUUSMC
Keywords: _not_EdTechHub; dode_eth-src-dode; dode_eth-trf2-dode

Learning to argue: A study of four schools and their attempt to develop the use of argumentation as a common instructional practice and its impact on students - Osborne, Jonathan; Simon, Shirley; Christodoulou, Andri; Howell-Richardson, Christina; Richardson, Katherine (Journal of Research in Science Teaching, 2013)
This article reports the outcomes of a project in which teachers' sought to develop their ability to use instructional practices associated with argumentation in the teaching of science—in particular, the use of more dialogic approach based on small group work and the consideration of ideas, evidence, and argument. The project worked with four secondary school science departments over 2 years with the aim of developing a more dialogic approach to the teaching of science as a common instructional practice within the school. To achieve this goal, two lead teachers in each school worked to improve the use of argumentation as an instructional practice by embedding activities in the school science curriculum and to develop their colleague's expertise across the curriculum for 11- to 16-year-old students. This research sought to identify: (a) whether such an approach using minimal support and professional development could lead to measurable difference in student outcomes, and (b) what changes in teachers' practice were achieved (reported elsewhere). To assess the effects on student learning and engagement, data were collected of students' conceptual understanding, reasoning, and attitudes toward science from both the experimental schools and a comparison sample using a set of standard instruments. Results show that few significant changes were found in students compared to the comparison sample. In this article, we report the findings and discuss what we argue are salient implications for teacher professional development and teacher learning. © 2013 Wiley Periodicals, Inc. J Res Sci Teach 50:315–347, 2013
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/tea.21073 KerkoCite.ItemAlsoKnownAs: 10.1002/tea.21073 2339240:4NIGXKV2 2405685:4X4GKSJM 2405685:VIDIRPJ6 2534378:G9ZN4A6P
Keywords: argumentation; dialogic teaching; epistemic learning; student engagement; teacher professional development

Synthesis of Reviews on Teacher Professional Development in Sub-Saharan Africa - Haßler, Björn; D’Angelo, Sophia; Walker, Hannah; Marsden, Melissa (Open Development & Education, 2019)
EdTechHub.Source: 2129771:SC8FTPC4 KerkoCite.ItemAlsoKnownAs: 2129771:SC8FTPC4 2339240:GJ83JMQA 2405685:T7DTBWJB
Keywords: _yl:i; dode_eth-src-dode; dode_eth-trf2-dode

Broadening borders to build better schools: virtual professional learning communities - Carpenter, Daniel; Munshower, Paul (The International Journal of Educational Management, 2019)
PurposeThe purpose of this paper is to explore how rural teachers provided a PLC by leveraging virtual technologies to connect educators of like subject disciplines from several schools, foreign and domestic.Design/methodology/approachA phenomenological case study-based approach was leveraged to investigate established vPLCs at schools (Creswell, 2013; Stake, 2010). Qualitative data were collected from multiple sources to obtain rural teacher perceptions on the impact vPLCs had on their practice (Creswell, 2013).FindingsTeacher collaborative teams build relationships comparable to teams that met face to face as part of a similar PLC and PD experience. Participant reflections in this investigation showed that rural educators favored face-to-face meetings; however, vPLCs provided similar teacher experiences to that of the face-to-face PBL model. Results indicated that educators recognized virtual collaboration just as valuable a tool for enabling PLCs than face-to-face collaborations while still offering similarities to improved teacher practice.Research limitations/implicationsThe research was limited to teachers in rural settings in the USA (Texas) and in the Dominican Republic. The research was limited to teacher perceptions of change, and observed changes as part of their participation in a research-based virtual PLC model. The research was limited to the school setting over an academic year.Practical implicationsThe findings from this study have practical implications for rural teachers and school implementation of a professional learning community model.Originality/valueThe promise provided by this study is that vPLCs may provide opportunity for rural schools to provide a job-embedded professional development model (Croft et al., 2010) for otherwise isolated teachers (Barrett et al., 2015).
Place: Bradford Publisher: Emerald Group Publishing Limited Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2338030077?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1108/IJEM-09-2018-0296 2339240:ITBNKNJS 2405685:493XEK9T 2405685:BXCJZXC3 2534378:9DM4HQE9 2534378:BDJAHBNX 2534378:EEJ2GZ6E
Keywords: Collaboration; Communities of Practice; Computer Mediated Communication; ERIC; Current Index to Journals in Education (CIJE); Education; Educational technology; Faculty Development; Learning; Meetings; Preferences; Professional development; Professional learning communities; Rural Schools; Rural schools; School districts; Teacher Attitudes; Teacher Collaboration; Teacher collaboration; Teachers; Teaching; Virtual professional learning communities; __:import:01; __:match:final; __:matched; __:study_id:2095794; __finaldtb

"For us it was a learning experience": design, development and implementation of blended learning - Onguko, Brown; Jepchumba, Lucy; Gaceri, Petronilla (European Journal of Training and Development, 2013)
Purpose - The purpose of this paper is to share reflections of the three authors on the process of instructional design and implementation of blended learning for teachers' professional development (PD) in rural western Kenya. It proposes reforms in provision of teachers' professional development to enable professional development providers to access specialized skills in instructional design (ID) and blended learning. Design/methodology/approach - The paper resulted from a design-based research including 12 entry and 12 exit interviews, observations of three face-to-face meetings of blended learning sessions and ten classroom observations of teachers implementing new teaching approaches learned through blended learning. Findings - The paper provides insights into the authors' experiences in this research. They shared the following reflections: engagement in ID empowered them and they are confident that they can engage in systematic instructional design on a larger scale; they gained technical knowledge and skills in authoring content in HTML on eXe open source platform; uploading the content and processing audio and video content was equally enthralling to them. Research limitations/implications - Because of the chosen research approach, the research results may lack generalisability. Therefore, researchers are encouraged to consider incorporating the design-based research, instructional design and blended learning approaches used in this study while conducting related research in their dissimilar contexts. Practical implications - The paper includes implications for the design, development and implementation of teachers' professional development for challenging contexts as a contribution towards achievement of both Millennium Development Goals (MDGs) and Education for All (EFA). Originality/value - This paper fulfils an identified need to study provision of professional development for teachers who lack opportunities for professional development.
Place: Limerick Publisher: Emerald Group Publishing Limited Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1430572667?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1108/ejtd-10-2012-0052 2339240:C7CEXRWM 2339240:XN53EQR3 2405685:AFTT7Q76 2405685:UYED6EDY 2405685:ZZ7VUU4G 2534378:32ICX4DB 2534378:UTXP2X7Q
Keywords: 5220:Information technology management; 8306:Schools and educational services; 9177:Africa; Appropriate technology; Audio recordings; Business And Economics–Management; Instructional design; Kenya; Personal development; Professional development; Research; Rural schools; Teaching; Technological change; Training; __:import:01; __:match:final; __:matched; __:study_id:2096396; ___working_potential_duplicate; __finaldtb

Reflective teacher supervision through videos of classroom teaching (supervisión colaborativa docente a través de clases grabadas en video) - Kaneko-Marques, Sandra Mari (PROFILE: Issues in Teachers' Professional Development, 2015)
The main objective of this paper is to briefly present roles of different teacher supervisors according to distinct models, highlighting the importance of collaborative dialogues supported by video recordings. This paper will present results from a qualitative study of an English as a foreign language teacher education course in Brazil. The results indicated that collaborative supervision was an efficient tool to address adversities within educational contexts and that student teachers who observed their pedagogical actions through videos became more reflective and self-evaluative, as they provided a deeper analysis regarding their practice. With collaborative supervision, teacher candidates can be encouraged to recognize and understand the complexities of language learning and teaching both locally and globally.
Publisher: Universidad Nacional de Colombia, Carrera 30 No. 45-03 Ciudad Universitaria, Bogotá, Colombia Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1720057575?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.15446/profile.v17n2.44393 2405685:E3Q476XV 2534378:8NSF3BMX 2534378:VXGS7DTC
Keywords: Brazil; Cooperation; ERIC; Current Index to Journals in Education (CIJE); English (Second Language); English Teachers; Foreign Countries; Higher Education; Observation; Postsecondary Education; Preservice Teacher Education; Qualitative Research; Questionnaires; Reflective Teaching; Second Language Instruction; Self Evaluation (Individuals); Student Teachers; Teacher Supervision; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2098468; __finaldtb

Community-Based Teacher Training: Transformation of Sustainable Teacher Empowerment Strategy in Indonesia - Mardapi, Djemari; Herawan, Tutut (Journal of Teacher Education for Sustainability, 2019)
Teacher empowerment is a central issue in relation to the efforts to improve the quality of education. However, teacher empowerment will remain an abstract idea if its implementation is not supported by an appropriate strategy. The demands for a quality education will be unreciprocated if teachers do not have the opportunity to empower themselves. This research aims to investigate the teacher empowerment strategy in Indonesia, which has been conducted by employing a community-based teacher training program. This study has highlighted several research questions: What is meant by community-based training program? Why is the training program needed? Who is the target of the training program? What model has been used to implement the training? What are the results of the training that has been executed? This research was conducted from November 2018 to January 2019. The research data were collected by means of documentation studies and interviews. The data analysis was carried out quantitatively and qualitatively, where the quantitative analysis was processed based on the document study data, meanwhile the qualitative analysis was performed based on the interview data. The research results showed that community-based teacher training was transformation of teacher development strategy as a follow-up on teachers’ competency test in Indonesia. The community-based teacher training succeeded in increasing the professionalism of teachers in Indonesia, particularly in terms of implementing their pedagogical and professional competencies. The training is also successful in motivating the teachers to engage themselves in continuous learning efforts through building strong teachers’ network and working collaboratively with colleagues. Quantitatively, training was proven to increase the average of teacher competency by 23.97 (on a scale of 100). The research results are expected to provide information about the best practice in teacher coaching that is conducted massively in a national scope based on the local community so that a lifelong learning culture for teachers is established to support the development of sustainable education.
KerkoCite.ItemAlsoKnownAs: 10.2478/jtes-2019-0004 2405685:8YANT76F

Reexamining technology’s role in learner-centered professional development - Polly, Drew; Hannafin, Michael J. (Educational Technology Research and Development, 2010)
The American Psychological Association’s Learner-Centered Principles provide empirically-based approaches to improving teaching and learning. However, in order to facilitate learner-centered, technology-rich instruction to K-12 students, teachers must be afforded opportunities to develop key understandings and skills, rarely evident in most professional development programs. In this paper, we synthesize empirically-based studies and recommendations for teacher learning and propose a learner-centered professional development (LCPD) framework to guide both professional development and empirical work on teacher learning. We describe LCPD components, discuss ways that technology can support LCPD, and highlight implications for research and practice.
shortDOI: 10/fwd4wz KerkoCite.ItemAlsoKnownAs: 10.1007/s11423-009-9146-5 10/fwd4wz 2405685:E28QZPQQ

Reexamining technology’s role in learner-centered professional development - Polly, Drew; Hannafin, Michael J. (Educational Technology Research and Development, 2010)
The American Psychological Association’s Learner-Centered Principles provide empirically-based approaches to improving teaching and learning. However, in order to facilitate learner-centered, technology-rich instruction to K-12 students, teachers must be afforded opportunities to develop key understandings and skills, rarely evident in most professional development programs. In this paper, we synthesize empirically-based studies and recommendations for teacher learning and propose a learner-centered professional development (LCPD) framework to guide both professional development and empirical work on teacher learning. We describe LCPD components, discuss ways that technology can support LCPD, and highlight implications for research and practice.
Extra URL: https://doi.org/10.1007/s11423-009-9146-5 KerkoCite.ItemAlsoKnownAs: 10.1007/s11423-009-9146-5 2339240:F24I3ZNF 2405685:87VETGDX

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using Information and Communication Technology (IJEDICT), 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school factors and system, and other external factors. This exploratory study was conducted within the framework of a teachers’ union to understand members’ preparedness to integrate ICT tools in their teaching practices. Findings indicate the need for in-service professional development activities in the use of ICT for teaching, in teaching in multicultural environments, and in classroom management. Equally important is the role of school management and administration in the adoption and integration of ICT tools in education. In addition, the research provided clear evidence that despite the huge investments into ICT infrastructure by government, inequalities in ICT competencies among teachers remain. The most important conclusion is that the investments being made are politically motivated and that teachers are being side-lined in the decision-making processes and preference given to political visions.
KerkoCite.ItemAlsoKnownAs: 2339240:FCJF68RN 2405685:HQE8MXWS
Keywords: ⛔ No DOI found

Online learning community: A case study of teacher professional development in Indonesia - Sari, Eunice (Intercultural Education, 2012)
This paper investigates the concept of online learning community (OLC) to address the issues of teacher professional development practice in twenty-first-century Indonesia. Teachers in Indonesia are trained in a 'conventional way', hence, not ready to prepare the younger generations for entrance into the twenty-first-century complex life and work environment. The pedagogical transformation of a teacher can be facilitated through teacher professional development. Recent studies show that OLC holds great promise in improving teachers' professional practice. This paper presents key results of the introduction and trialling of OLC with Indonesian teachers and teacher educators between 2009 and 2010 and aims to explore the feasibility of this model to support professional development of teachers in this era. The social learning interactions among community members were examined using Scardamalia's Twelve Socio-Cognitive Determinants of Knowledge Building and Hoftsede's Cultural Dimension Review for Indonesia.
KerkoCite.ItemAlsoKnownAs: 10.1080/14675986.2012.664755 2339240:L9YC4RVC 2405685:W2R874SP

Blog-based professional development of English teachers in Mumbai: The potential of innovative practice under scrutiny | Australasian Journal of Educational Technology - Khan, Atiya (Australian Journal of Educational Technology, 2017)
The professional development of teachers in India is still, by and large, based on formal and outdated professional learning traditions, often characterised by crash courses and one-off workshops. In education, blogs have proven to be an effective means of establishing and maintaining collaborative learning networks and helping members reflect on their professional practices. Information and communications technology (ICT) enabled practices of teacher professional development is still in its infancy in India. Moreover, there is limited research in India to secure foundational understanding of how and in what ways teachers of English in India use blogs for their professional development. This study explores the use of teacher reflective practice, teacher networking, and teacher collaboration, beyond formal ICT training, through blog-based professional development of English teachers in the Mumbai region of India. Using data collected from 32 teachers from three private schools in Mumbai, through ICT interactive workshop observations, questionnaires, interviews, and blog comments, this action case study explains whether and why blogging, as a learning community, has the potential to add significant value to existing professional development of English teachers in Mumbai.
KerkoCite.ItemAlsoKnownAs: 10.14742/ajet.2784 2339240:MKUUJUI9 2405685:XDE87UXV

Evaluating Teachers' Professional Development For ICT Use: Towards Innovative Classroom Practices - Agyei, D. D (International Journal of Education, 2015)
This paper describes an evaluation study designed to investigate the impact of an ICT-Instructional digital innovation in teaching Mathematics, English and Integrated Science subjects from the teacher capacity building professional development programme to classroom implementation at senior high school levels in Ghana. Interviews and survey data were used for data collection following a week professional development programme on the instructional digital learning training. The study demonstrated that the teachers increased in ICT proficiencies but this was limited to their own professional development and not so much of classroom implementation of ICT which results when transfer of learning takes place from training to practice. The study reported that teachers faced a complex mix of factors that when combined, contributed to challenges in transferring the ideas gained in the training programme to the classroom situation. It was evident from the findings that more systematic efforts are needed at the school levels and at the level of stakeholders who implement in-service teachers’ professional development programmes to move the goal of transforming teaching and learning through ICT-based innovations. Based on the outcomes, the study discussed recommendations to help smoothen the transition from teacher professional development programmes to actual classroom implementations in Ghanaian senior high schools and such similar contexts.
KerkoCite.ItemAlsoKnownAs: 2339240:E5S9DU9K 2405685:RHW2CXQ7
Keywords: ⛔ No DOI found

Teachers' professional development in a challenging educational context – a study of actual practice in rural western Kenya - Onguko, Brown (University of Calgary, 2012)
This research adopted a design research approach, utilizing a mixture of methods including narratives, ethnographic observations, qualitative interviews and documentation of design artifacts. It was implemented in a challenging context in Western Kenya. The first research question for this study was: How might professional development (PD), offered through a blended learning approach and delivered by appropriate technologies, inform potential change to teaching practice in a challenging context in Kenya? Research question two sought to understand the implications of the professional development implemented in this study for teachers and professional development teachers (PDTs). Question three sought to understand the sustainability and scalability of the professional development approach The theoretical framework informing this research is based on activity theory- a needs-driven and goal directed process through tool mediation, and entails division of labor and isolation of partial tasks in a community of relationships (Vygotsky, 1978; Leont’ev, 1978; Engestrom, 1987; 1999; 2000; 2008). Key features of activity theory are active engagement and social interaction, which enabled teachers to collaboratively work with each other, studying through appropriate technologies to inform their teaching practices. Based on a review of literature, interviews with teachers and observation of teachers during face-to-face meetings in professional development and in their classroom practice, this study suggests that teachers in a challenging context can inform potential change to their teaching as a result of participation in locally developed content, delivered through blended learning on appropriate technologies. This study observes that through self-directed study on tablets, and occasional face-to-face interaction, teachers can transform into a community of learners that support each other in planning for their lessons. Content development involving local experts is critical to such interventions in challenging contexts, while drawing from global web content, harnessing open educational resources and being sensitive to local culture. Reflective conversations, professional dialogues and technology stewardship were all critical in informing teachers’ practice.
Publisher: Education KerkoCite.ItemAlsoKnownAs: 10.11575/PRISM/27984 2339240:DG2D5LEQ 2339240:HFGVU85N 2405685:3GUCVMD2 2405685:AJ9GX7EE 2534378:9XFBBTYJ 2534378:SQ7895I3
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2457443; __finaldtb; ⛔ No DOI found

Pre-service teacher training in Malawi: findings of a pilot study on the viability of media players for teacher development - Carrier, Carol; Finholt-Daniel, Matt; Sales, Gregory C (International Journal of Education and Development using Information and Communication Technology, 2012)
As part of the United States Agency for International Development (USAID funded Malawi Teacher Professional Development Support project, a sub-task was the piloting of an alternative technology that could be used for improving the quality and consistency of teacher continued professional development (CPD). The pilot, which included 26 open and distance learning (ODL) student teachers, was launched in the spring of 2011 using a low-cost portable MP3 multi-purpose device. A short course on numeracy, containing 5 weekly lessons, was piloted. Each lesson consisted of one or two readings, two videos, and an assignment that directed the learner to complete tasks and document their completion using the camera and audio recorder features of the media player. The viability of using the media player for CPD was evaluated on the ease of use, effectiveness of instruction, and potential for long-term scalability. The evaluation results demonstrated that, with a small amount if initial training, the devices were easy to use and they effectively deliver instruction. Scalability, however, is critical to the long-term success of an initiative based on these or similar devices. An analysis suggests that an affordable option worth considering is the systematic, shared use of media player devices within schools. This approach could dramatically reduce the cost of using this alternative technology for ODL training to pennies per lesson. [PUBLICATION ABSTRACT]
Place: Bridgetown Publisher: University of the West Indies KerkoCite.ItemAlsoKnownAs: 2339240:H5SC64NG 2405685:HNDKMF9C 2534378:5F2RLGL3 2534378:783739U4
Keywords: Distance learning; Education; Learning; Malawi; Software; Student teachers; Teacher education; Teaching; __:import:01; __:match:final; __:matched; __:study_id:2096523; __finaldtb; ⛔ No DOI found

ICT use in the teaching of mathematics: Implications for professional development of pre-service teachers in Ghana - Agyei, Douglas; Voogt, Joke (Education and Information Technologies, 2011)
Included in the contemporary mathematics curricula in Ghana is the expectation that mathematics teachers will integrate technology in their teaching. However, importance has not been placed on preparing teachers to use ICT in their instruction. This paper reports on a study conducted to explore the feasibility of ICT use in mathematics teaching at senior high school levels in Ghana. Interviews and survey data were used for data collection. Preliminary results showed that mathematics teachers in Ghana do not integrate ICT in their mathematics instruction. Among the major perceived barriers identified were: Lack of knowledge about ways to integrate ICT in lesson and Lack of training opportunities for ICT integration knowledge acquisition. To overcome some of these barriers, opportunities of a professional development arrangement for pre-service mathematics teachers were explored. Findings from the study revealed specific features of a professional development scenario that matters for ICT integration in mathematics teaching in the context of Ghana. KeywordsICT use–Professional development–Computer competencies–Mathematics education–Computer attitude–Ghana
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-010-9141-9 2339240:4GH4JJ6N 2405685:GKN47LAT

An experimental study of the performance of prospective teachers of flipped classroom and non-flipped classroom - Minaz, Maksal; Tabassum, Rabia; Idris, Muhammad (Pakistan Journal of Education, 2017)
Video-recording of lectures and creating of podcasts for playback on the computer and other portable devices which accommodate the new formats of self-developed learning are identified as flipped classroom. The study was focused on the objective to Investigate performance of prospective teachers of flipped classroom and non-flipped classroom with respect to flipped classroom strategy. Therefore, null hypotheses were formulated; there is no significant difference between the mean scores of flipped classroom and non-flipped classroom of prospective teachers before and after treatment; Pretest posttest equivalent group experimental research design was taken for the study. A paired random sampling technique was employed to select the sample on the basis of pretest scores from the subjects.. Experimental group was named flipped classroom and control group was named non-flipped classroom. Treatment of flipped classroom strategy provided to the flipped classroom and the non-flipped classroom was thought through lecture demonstration method. Posttest was administered to collect data from both groups without delay after treatment of six academic weeks. Results of the study illustrated that there was significant difference between the performance of flipped and non-flipped classrooms prospective teachers. It was recommended that flipped classroom may be an integral part of curriculum of professional development courses in Pakistan.
Place: Islamabad Publisher: Allama Iqbal Open University Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2364383027?accountid=9851 KerkoCite.ItemAlsoKnownAs: 2339240:JSUA8DQA 2405685:AUM7ANGN 2405685:EC5V2BBM 2534378:Q5BTRXDU 2534378:ZZ43GQ5G
Keywords: Education; Educational technology; Learning; Pedagogy; Podcasts; Professional development; Teacher attitudes; __:import:01; __:match:final; __:matched; __:study_id:2096864; __finaldtb; ⛔ No DOI found

Technology and Teacher Professional Development (TPD): the Process and Content of Microlearning in a School-Based Integrated In-Service Teacher Education (INSET) Project - Junaid, Muhammad Ibn; Ogange, Betty; Allela, Melisa (Commonwealth of Learning (COL), 2019)
Continuing teacher professional development for all teachers across the entire school system poses a challenge in many contexts, especially in developing countries. Teachers from schools located in remote rural areas usually have fewer professional development opportunities due to the lack of accessibility either to their schools or to professional development resources. On-site school-based professional development is a viable option if innovative design is adapted to generate microlearning resources that teachers can easily access and share. This paper reports on a technology enabled school-based integrated INSET project coordinated by the Freetown Teachers College (FTC) in 12 junior secondary schools (JSS) in Sierra Leone under the COL’s Teacher Futures Programme. The project represents an innovation in TPD and is different from the general type of face-to-face and exclusively paper-based in-service teacher training programme common in Sierra Leone. Under the new project a multimodal approach is used where the FTC mentors and the communities of learners (JSS teachers) are presented with both print and microlearning resources and also provided access to an eLearning platform and the use of mobile phones as the main vehicles of delivery. Microlearning is an emergent learning strategy known for its quick response in bridging skills and knowledge gaps. In the context of the INSET Project, it involves a weekly dose of pedagogical content knowledge and skills, including modelling of classroom best practices which teachers can adapt and use. The project design and methods are briefly described, but the main focus of the paper is on the microlearning component of this project and discusses the use of mobile technology in the delivery and implementation of TPD in the 12 project schools. The emphasis is on the methodological and management challenges that arise in creating and nurturing communities of practice (CoPs) in a school-based setting and how these are addressed by the various schools involved.
KerkoCite.ItemAlsoKnownAs: 2405685:AALEIRC2

Understanding language teachers' practice with educational technology: A case from China - Li, Li (System, 2014)
This article explores how eight secondary school teachers integrated educational technology into English language teaching in Beijing, China and considers their views of the factors influencing technology use. Analysing data from classroom recordings and follow-up interviews, this study revealed that PowerPoint was the most frequently used technological application in the classroom, while the internet and other technological tools were also used by the teachers. They employed educational technology for different pedagogical purposes, including addressing professional needs in improving teaching, designing materials and conducting professional development. Teachers also claimed that they used technology to address learners' needs, such as improving engagement, enhancing language acquisition, facilitating understanding and establishing a context for language use. The study identified four important factors in influencing teachers' use of technology, including sociocultural contexts, teachers' beliefs, access to resources, and technology competence and confidence. This study suggests that a critical reflective approach is useful in assisting teachers to understand their needs and pedagogical beliefs concerning technology use. Ongoing professional development is also valuable in promoting teachers' technology competence and confidence, thereby improving the use of technology in their teaching.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.system.2014.07.016 2339240:CXH3G6AE 2405685:SMJ8CD63
Keywords: Case study; China; Socio-cultural context; Teachers' perceptions; Technology use

Transforming Teacher Education and Learning in Ghana: The Impact of a Continuous Professional Development on Physics Teaching at the Colleges of Education - Coffie, Isaac Sonful (International journal of Research and Scientific Innovation, 2019)
The colleges of education in Ghana have been involved in a continuous professional development for over four years with support of Transforming Teacher Education and Learning (T-TEL). The main purpose of this research was to assess the perceived impact of the continuous professional programme on physics teaching at the colleges of education. Descriptive cross sectional survey was used for the study. An online survey was conducted which was completed by 85 physics tutors. The survey data were analysed using means and standard deviations and ANOVA. It was found that the professional development is perceived by the physics tutors to have great impact on their teaching practice. It was also found out that there was no statistical significant difference in the perceived impact of the professional development based on tutors’ experience. It was concluded that if the student teachers who are being trained by these tutors will learn these ideas from their tutors and practice them, teaching at the basic schools will be more interactive, students-centered and gender responsive.
EdTechHub.ItemAlsoKnownAs: 2405685:IPJBNU3S
Keywords: ⛔ No DOI found

Supporting teachers in taking up productive talk moves: The long road to professional learning at scale - O’Connor, Catherine; Michaels, Sarah (International Journal of Educational Research, 2019)
In this paper we describe our early, qualitative work on “teacher talk moves” such as revoicing, situated within the urban classrooms of highly skilled teachers, including their role in the work of managing multiple constraints while maintaining productive inclusivity. We then describe our attempts to discern the impact of these talk tools on student achievement in multiple classrooms, using both post-hoc controls and in vivo studies. We move on to the challenges present in disseminating this work in professional development settings; our approach includes framing talk tools as rational responses to actual classroom challenges. Finally we describe current efforts to disseminate cyber-enabled PD in science education K-12, including a central focus on academically productive talk.
shortDOI: 10/ghgn5s KerkoCite.ItemAlsoKnownAs: 10/ghgn5s 2405685:X9V64KPT 2534378:LDIGVCHK

Teacher Coaching: What We Know - Evans, David (World Bank Blogs - Development Impact, 2017)
“Teacher coaching has emerged as a promising alternative to traditional models of professional development.” In Kraft, Blazar, and Hogan’s newly updated review “The Effect of Teacher Coaching on Instruction and Achievement: A Meta-Analysis of the Causal Evidence, ” they highlight that reviews of the literature on teacher professional development (i.e., ...
KerkoCite.ItemAlsoKnownAs: 2405685:VHFL7S36 VHFL7S36

The specific skills required of teachers who deliver K–12 distance education courses by synchronous videoconference: implications for training and professional development - Rehn, Nicki; Maor, Dorit; McConney, Andrew (Technology, Pedagogy and Education, 2018)
The purpose of this research is to identify the specific skills required of videoconference teachers who teach K–12 distance education courses. Many schools and educational districts worldwide are using videoconference technology to deliver courses to students as an economic solution when they cannot afford specialised teachers at remote locations. However, teachers are rarely trained to use this instructional technology and must therefore translate their experience in face-to-face and/or online teaching to this alternative medium. The collective case study used observations and interviews of eight teachers across five schools to identify the specific skills required to teach in a way that they perceived as successful in a videoconference class. It was found that teachers are largely under-prepared with strategies to project presence, develop relationships, foster interaction, manage the course and teach content across a distance when the screen is the main tool of connection. The authors offer a path to improvement that involves supporting teacher action research, creating communities of inquiry and developing teaching quality standards specific to videoconference.
Publisher: Routledge KerkoCite.ItemAlsoKnownAs: 10.1080/1475939X.2018.1483265 2405685:FP425A4V
Keywords: K–12; Videoconferencing; distance education; instructional technology; teacher roles

Experimental Impacts of a Teacher Professional Development Program in Chile on Preschool Classroom Quality and Child Outcomes - Yoshikawa, Hirokazu; Snow, Catherine; Barata, Clara; Gomez, Celia; Leyva, Diana; Treviño, Ernesto; Weiland, Christina; Moreno, Lorenzo (Developmental Psychology, 2015)
We assessed impacts on classroom quality and on 5 child language and behavioral outcomes of a 2-year teacher professional-development program for publicly funded prekindergarten and kindergarten in Chile. This cluster-randomized trial included 64 schools (child N 1,876). The program incorporated workshops and in-classroom coaching. We found moderate to large positive impacts on observed emotional and instructional support as well as classroom organization in prekindergarten classrooms after 1 year of the program. After 2 years of the program, moderate positive impacts were observed on emotional support and classroom organization. No significant program impacts on child outcomes were detected at posttest (1 marginal effect, an increase in a composite of self-regulation and low problem behaviors, was observed). Professional development for preschool teachers in Chile can improve classroom quality. More intensive curricular approaches are needed for these improvements to translate into effects on children.
shortDOI: 10/f632xg KerkoCite.ItemAlsoKnownAs: 10.1037/a0038785 10/f632xg 2405685:J52Y2D26

The Potential of Mobile Phones to Transform Teacher Professional Development to Build Sustainable Educational Futures in Bangladesh - Walsh, Christopher S; Woodward, Clare; Solly, Mike; Shrestha, Prithvi (Asian Association of Open Universities Journal, 2015)
Futures thinking is used by governments to consider long-term strategic approaches and develop policies and practices that are potentially resilient to future uncertainty. English in Action (EIA), arguably the world's largest English language teacher professional development (TPD) project, used futures thinking to author possible, probable and preferable future scenarios to solve the project's greatest technological challenge: how to deliver audio-visual TPD materials and hundreds of classroom audio resources to 75,000 teachers by 2017. Authoring future scenarios and engaging in possibility thinking (PT) provided us with a taxonomy of question-posing and question-responding that assisted the project team in being creative. This process informed the successful pilot testing of a mobile-phone-based technology kit to deliver TPD resources within an open distance learning (ODL) platform. Taking the risk and having the foresight to trial mobile phones in remote rural areas with teachers and students led to unforeseen innovation. As a result, EIA is currently using a mobile-phone-based technology kit with 12,500 teachers to improve the English language proficiency of 700,000 students. As the project scales up in its third and final phase, we are using the new technology kit — known as the 'trainer in your pocket' — to foster a 'quiet revolution' in the provision of professional development for teachers at scale to an additional 67,500 teachers and nearly 10 million students.
Publisher: Emerald Group Publishing Limited shortDOI: 10/ggx3rj KerkoCite.ItemAlsoKnownAs: 10.1108/AAOUJ-10-01-2015-B005 10/ggx3rj 2405685:6AFZ29KK

The Teachers’ Portal as a tool for teachers’ professional development in Bangladesh: Facilitating nationwide networking and digital multimedia content for 40,000 schools - Hansson, H; Sultana, S; Sarwar, A; Ahmed, F; Uddin, R; Saha, P; Islam, G; Islam, M (International Journal of Education and Development using ICT, 2018)
The Teachers’ Portal (teachers.gov.bd) is an online platform for Bangladeshi teachers designed to store and retrieve digital educational contents of different subjects useful for classroom teaching and students’ learning. The portal also facilitates professional networking among teachers across the country. This study aims to find out the benefits of using this Portal and associated challenges from teachers’ perspective. Following a mixed methods research approach Teachers, head teachers, teacher educators from primary, secondary, madrasa and vocational educational institutions and specialists on teachers’ Portal (N=410) were interviewed and consulted for the study. Telephone interviews, online surveys, Key Informant Interviews (KII), Focused Group Discussions (FGD), Face-to-Face interviews, and large consultative workshops were used to collect data. The results suggest that teachers are motivated to use the Portal as its contents stimulate students’ creativity and encourage students’ active participation in classrooms learning. Besides, it empowers teachers in a number of ways. However, internet connectivity, slow Internet speed, power failure, technical issues, high cost of Internet and unavailability of equipment are found as major challenges. In short, the Teachers’ Portal is a key driver for changing Bangladeshi education and preparing the young generation with quality education.
KerkoCite.ItemAlsoKnownAs: 2339240:YUIF5MMJ 2405685:ZSXBG9LT
Keywords: ⛔ No DOI found

Can new modes of digital learning help resolve the teacher crisis in sub-Saharan Africa? - Moon, Bob; Villet, Charmaine (Journal of Learning for Development, 2017)
Sub-Saharan Africa, more than any other part of the world, is experiencing a crisis in finding sufficiently qualified teachers to meet the needs of expanding school systems. The professional development support provided to serving teachers is also inadequate in most countries. The most recent data on learner outcomes has revealed a worrying picture of significant under-achievement across the region. This paper argues that the teacher education and training structures of the last century will never be able to meet urgent contemporary needs. Given population growth, especially among the young, large-scale expansion of the teaching force and the associated teacher education systems will be the norm through to the middle years of the century and beyond. In this context the paper argues for a significant policy shift to expand quality teacher education and professional support at scale through a more school-based and digitally supported network model of provision. Examples of current digital programmes within the region are considered as well as the new technologies that are emerging with relevance to teacher education. The paper suggests a three-phase process through which national governments might move in making the necessary changes in policy and practice.
Publisher: Commonwealth of Learning, 4710 Kingsway Suite 2500, Burnaby, BC V5H 4M2 Canada KerkoCite.ItemAlsoKnownAs: 2405685:C4EES7UW 2534378:LSYA2A2W
Keywords: Africa; Computer Uses in Education; ERIC; Current Index to Journals in Education (CIJE); Educational Change; Educational Policy; Electronic Learning; Faculty Development; Foreign Countries; Higher Education; Inservice Teacher Education; Online Courses; Postsecondary Education; Preservice Teacher Education; Resource Units; Teacher Shortage; ⛔ No DOI found

The evaluation of "technological pedagogical content knowledge based argumentation practices" training for science teachers - Çoban, Gül Ünal; Akpinar, Ercan; Baran, Bahar; Saglam, Merve Kocagül; Özcan, Erkan; Kahyaoglu, Yasemin (Egitim ve Bilim, 2016)
In science education, creating learning environments supported with technology and students' use of theory-evidence coordination when expressing their ideas is emphasized regarding the development of students' scientific reasoning, critical thinking, decision making skills, and etc. In this process, great responsibilities are fallen to teachers as planner and designer of a learning environment. In this study, it is aimed to assess the training which aims the development of science teachers' technological pedagogical content knowledge (TPACK) through argumentation practices. In this context; this study evaluated the science teachers' argumentation skills, self-efficacy perceptions towards TPACK and the teachers' views about the training. 37 science teachers working at different cities in Turkey participated in the one group pre-test post-test experimental training study, which was lasted 54 hours during a week. The training is composed of both hand and minds on argumentation practices based on TPACK. The participants joined different activities such as collaborative group works, drama, modeling, thematic games, art activities, problem-based learning, field trips, observation and workshops. In the study, Argumentation Test, TPACK Self-Efficacy Belief Scale were used as data collection tools. At the end of the training written views of science teachers towards activities were taken. In the light of the findings, this training was effective on the participants' self-efficacy levels towards technological pedagogical content knowledge. Moreover, this training resulted in a positive change in the participants' views about how a statement could be accepted as an argument. However, the increase in scores of argumentation skills was not significant. Additionally almost all of the participants stated that they found the activities useful and can use in their classes. By considering these results, some suggestions were given.
Place: Ankara Publisher: Turk Egitim Dernegi Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1871595467?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.15390/EB.2016.6615 2339240:E9JW57H6 2405685:V9ACJE9V 2534378:T4XZE24B 2534378:V7KCNHFG
Keywords: Argumentation; Education; Professional development; Science teachers; Technological pedagogical content knowledge; __:import:01; __:match:final; __:matched; __:study_id:2097466; __finaldtb

ICT use in science and mathematics teacher education in Tanzania: Developing Technological Pedagogical Content Knowledge - Kafyulilo, Ayoub; Fisser, Petra; Pieters, Jules; Voogt, Joke (Australasian Journal of Educational Technology, 2015)
Currently, teacher education colleges in Tanzania are being equipped with computers to prepare teachers who can integrate technology in teaching. Despite these efforts, teachers are not embracing the use of technology in their teaching. This study adopted Technological Pedagogical Content Knowledge (TPACK) as a framework for describing the knowledge and skills that pre-service teachers need to develop in order to effectively integrate technology in science and mathematics teaching. Pre-service teachers (N=22) participated in microteaching, hands-on training, collaborative lesson design in design teams, and reflection with peers. Pre- and post-assessment results of the pre-service teachers’ perceived knowledge and skills of integrating technology in teaching, showed significant changes in technology-related components of TPACK. We conclude that opportunities for pre-service teachers to participate in professional development programs that involve lesson design, teaching, evaluation and re-design, can be effective for the development of the knowledge and skills of integrating technology in science and mathematics teaching.
Number: 4 KerkoCite.ItemAlsoKnownAs: 10.14742/ajet.1240 2339240:7KWSVKXS 2405685:7XN4YDQE
Keywords: TPACK; lesson design; microteaching; reflection; technology integration; training

Experimental Impacts of the “Quality Preschool for Ghana” Interventions on Teacher Professional Well-being, Classroom Quality, and Children’s School Readiness - Wolf, Sharon; Aber, J. Lawrence; Behrman, Jere R.; Tsinigo, Edward (Journal of Research on Educational Effectiveness, 2019)
We assessed the impacts of a teacher professional development program for public and private kindergartens in the Greater Accra Region of Ghana. We examined impacts on teacher professional well-being, classroom quality, and children’s readiness during one school year. This cluster-randomized trial included 240 schools (teachers N ¼ 444; children N ¼ 3,345, Mage ¼ 5.2) randomly assigned to one of three conditions: teacher training (TT), teacher training plus parental-awareness meetings (TTPA), and controls. The programs incorporated workshops and in-classroom coaching for teachers and video-based discussion groups for parents. Moderate impacts were found on some dimensions of professional well-being (reduced burnout in the TT and TTPA conditions, reduced turnover in the TT condition), classroom quality (increased emotional support/behavior management in the TT and TTPA conditions, support for student expression in the TT condition), and small impacts on multiple domains of children’s school readiness (in the TT condition). The parental-awareness meetings had counteracting effects on child school readiness outcomes. Implications for policy and practice are discussed for Ghana and for early childhood education in low- and middle-income countries.
shortDOI: 10/ggjrcj KerkoCite.ItemAlsoKnownAs: 10.1080/19345747.2018.1517199 10/ggjrcj 2339240:S3WAE3PS 2405685:H52RQ6MY 2405685:JXYTEU3W
Keywords: Ghana; ___working_potential_duplicate; classroom quality; early childhood education; kindergarten; school readiness; teacher training and coaching

Transforming teacher quality in the Global South: using capabilities and causality to re-examine teacher performance - Tao, Sharon (Palgrave Macmillan, 2016)
A common story of teachers from the Global South portrays them as deficient, unreliable and unprofessional. However, this book uses an innovative Capability Approach/Critical Realist lens to reveal the causal links between teachers' constrained capabilities and their 'criticised' behaviours and offer nuanced, creative strategies for improvements.
Google-Books-ID: kbPtCwAAQBAJ KerkoCite.ItemAlsoKnownAs: 2339240:IX6V82MK 2405685:B9ZP36MT
Keywords: Education / Comparative; Education / Educational Policy & Reform / General; Education / General; Education / Professional Development; Education / Teacher Training & Certification; Social Science / Anthropology / Cultural & Social; Social Science / Developing & Emerging Countries; Social Science / General; Social Science / Sociology / General

Approaches to teacher professional development in low-to-middle-income countries - Power, Tom (Sustainable English language teacher development at scale: Lessons from Bangladesh, 2019)
This chapter begins by situating discussion of approaches to teacher development (TD) in the context of the grand societal challenge of Education for All (UNESCO 2014), as written into the earlier Millennium Development Goals (MDGs) and now Sustainable Development Goal (SDG) 4:‘to ensure inclusive and equitable quality education for all.’ This goal cannot be met without addressing the stark and urgent need for greater numbers of teachers who are adequately equipped with the knowledge and skills to enable effective student learning. Drawing upon personal experiences of work with teachers in LMICs over nearly two decades, the chapter argues against ‘blaming teachers’ for poor student learning outcomes, and advocates instead the development of better understandings of the often challenging contexts in which teachers practise. The chapter then critically examines common approaches to TD that have often failed adequately to equip teachers for classroom practice, outlining a broadly supported agenda for reform. Recent literature has begun to identify certain characteristics of TD programmes that are increasingly associated with effective student outcomes, in what may be an emerging consensus. These characteristics are briefly outlined, before the chapter closes with lessons learned from English in Action. EIA has both contributed to and benefitted from this emerging evidence base and Chapter 5 illustrates how the implementation of EIA exemplifies such characteristics through a cohesive programme design.
Extra URL: http://oro.open.ac.uk/57052/ KerkoCite.ItemAlsoKnownAs: 2339240:D5ABKQWT 2405685:5G9NIHEU 2405685:KJGDVY5F 2405685:P8GU4VUJ 2405685:W9CSF5TT 2534378:3KFFQRC7 2534378:RSWZTN7D
Keywords: Important; Read

Introducing mobile technology for enhancing teaching and learning in Bangladesh: teacher perspectives - Shohel, M. Mahruf C.; Power, Tom (Open Learning: The Journal of Open, Distance and e-Learning, 2010)
This paper reviews the themes emerging from Bangladeshi teachers' experiences of taking part in the initial research and the development stage of a professional development programme they were involved with. The Secondary Teaching and Learning Programme is an information and communications technologies-enhanced supported open distance learning programme of professional development in English-language teaching. This paper presents evidence arising from semi-structured interviews carried out with teachers from a pre-pilot study for the English in Action project. The teachers participating in this study reflect upon six months' experience of using professional development materials (course material of audio podcasts enhanced with text and images; videos of classroom practice; audio of classroom language) and classroom resources (audio recordings of text-book reading passages, songs, poems and stories), all accessed via portable digital media players (iPods). (Contains 1 table and 1 figure.)
Publisher: Routledge, Available from: Taylor & Francis, Ltd. 325 Chestnut Street Suite 800, Philadelphia, PA 19106 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/815957037?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1080/02680513.2010.511953 10/brrchv 2339240:9GRACLAU 2405685:BFA3BZUN 2534378:HMHCMR9X 2534378:KT2WCVFZ 2534378:QXQHZY9I 2534378:UJQAALFW 2534378:ZJT5CTY3
Keywords: BANGLADESH; Bangladesh; COMPUTER assisted language instruction; COMPUTERS in education; CONTINUING education; Computer Assisted Instruction; DISTANCE education; Developing Nations; Digital audio players; Distance Education; Distance learning; ENGLISH language – Study & teaching – Foreign speakers; ERIC; Current Index to Journals in Education (CIJE); Education–Teaching Methods And Curriculum; Educational Development; Educational Technology; Educational technology; Elementary Secondary Education; English (Second Language); English in Action support model; English language; Foreign Countries; Handheld Devices; Higher Education; Inservice Teacher Education; Interviews; LANGUAGE teachers; Language instruction; Multimedia Instruction; OPEN learning; Open Universities; Pilot Projects; Postsecondary Education; Professional development; Program Descriptions; Program Development; Program Effectiveness; Protocol Materials; SECONDARY education; Second Language Instruction; Secondary Education; Secondary School Teachers; Studies; TEACHER development; TEACHERS – Attitudes; TELEMATICS; Teacher Attitudes; Teachers; Technology Integration; United Kingdom; Video Technology; _Source:Intuitive; _THEME: Curriculum and resources; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2098161; ___working_potential_duplicate; __finaldtb; auto_merged; mobile learning; mobile technology; technology intervention

Insights on ESL student teachers reflecting collaboratively online - Suppiah, Shubashini; Wah, (PhD), Lee Kean; Swanto, (PhD), Suyansah; Lajium, (PhD), Denis Andrew (The English Teacher, 2019)
The concept of a collaborative based reflective practice approach is grounded within the theoretical argument that critical reflection can be fostered through the presence of the "knowledgeable other" (Vygotsky, 1978). The present study was a pilot initiative in utilizing EDMODO (a closed educational learning management system) as a platform to explore reflection in a communal approach within a group of pre-service ESL teachers and their teacher educator mentor during a teaching practice placement in the context of the TESL (Teaching English as a Second Language) degree programme in an institute of teacher education (ITE) in Malaysia. The aims of the study are: (1) to examine the nature of the online reflection posts; and (2) to explore the nature of interactions that occurred online and the extent it supported collaborative reflection practices. The study employed a qualitative case study design in which five pre-service teachers (n=5) and their teacher educator mentor used EDMODO to post their reflections and carry out discussions for four weeks (n=4). The sources of data were the online reflection posts, the threaded discussion posts and a semi-structured group interview. Despite initial ambiguities and constraints, the EDMODO learning site as a platform for reflective practice showed positive results in that it allowed collaboration and dialogue to take place. Nevertheless, the facilitation of the reflection process requires further inquiry. The findings of the study suggest the need to establish a more systematic and structured approach when fostering critical reflection practices in a communal setting.
Place: Seri Kembangan Publisher: Malaysian English Language Teaching Association (MELTA) KerkoCite.ItemAlsoKnownAs: 2405685:N9ZPHXCW 2534378:DFCJXPJ2 2534378:VI3TK6EI 2534378:VWP4487Z
Keywords: Collaboration; Distance learning; English as a second language–ESL; Linguistics; Malaysia; Problem solving; Professional development; Reflective practice; Researchers; Social research; Student teachers; Teacher education; Teaching; Web 2.0; __:import:01; __:match:final; __:matched; __:study_id:2095770; __finaldtb; ⛔ No DOI found

An exploration of agency in the localisation of open educational resources for teacher development - Wolfenden, Freda; Adinolfi, Lina (Learning, Media and Technology, 2019)
This study examines the practice of adaptation and translation (localisation) of Open Educational Resources (OER). It employs a sociocultural perspective to focus on the experiences of practitioners (localisers) who undertook the localisation of a suite of 125 OER created as part of a teacher professional development programme in India. This localisation process generated eight unique versions of the OER in five languages. Drawing on project reports, practitioner interviews and analysis of the adapted OER, the study explores how localisers created meaning for the task, the situational and linguistic factors that influenced and mediated their decisions to adapt the materials – or not – and the skills and experiences that emerged through the process. Although the findings revealed that changes to the materials were limited, suggesting that enacting localisation is more difficult than perhaps suggested by OER proponents, the analysis indicated forms of localisers’ emerging professional agency through this endeavour.
Publisher: Routledge _eprint: https://doi.org/10.1080/17439884.2019.1628046 Extra URL: https://doi.org/10.1080/17439884.2019.1628046 KerkoCite.ItemAlsoKnownAs: 10.1080/17439884.2019.1628046 2405685:D4SI9BWU 2534378:ALXXMXLY 2534378:ZPP9MH8V
Keywords: India; Open educational resources (OER); __:import:01; __:match:final; __:matched; __:study_id:2457357; __finaldtb; localisation; professional agency

Using technology for enhancing teaching and learning in Bangladesh: challenges and consequences - Shohel, M. Mahruf C.; Kirkwood, Adrian (Learning, Media and Technology, 2012)
The increasing use of media and technologies for enhancing teaching and learning is an important current trend to overcome the challenges of schooling and teacher training in the changing world. Many countries in the Global South are trying to adopt technologies in their school and teacher training systems to achieve the UN Millennium Development Goals. Though some recent research shows impacts of using technologies for enhancing teaching and learning in technology-poor contexts, no research actually addresses the challenges and difficulties associated with using the technologies in those specific contexts. This article presents interview data derived from secondary schools teachers in Bangladesh, in a context beset with many difficulties associated with technology use. In a pilot project, Apple iPods were introduced in 2009 to explore the challenges and consequences of using technology in schools. The data reveal the implications for the teachers’ professional development when they used the iPod as a multimedia player to access educational resources made available to support teaching and learning. This article has also thrown some light on current debates about using technologies for enhancing teaching and learning in technology-poor contexts.
KerkoCite.ItemAlsoKnownAs: 10.1080/17439884.2012.671177 10/gf5f6w 2339240:IVHSIR7Q 2405685:9ATXKXTE
Keywords: Bangladesh; THEME: Curriculum and resources; THEME: Open systems; THEME: Teacher Professional Development; _Source:Intuitive; teachers’ professional development; teaching and learning; technology; technology-poor contexts; the

The potential of MOOCs for large-scale teacher professional development in contexts of mass displacement - Kennedy, E.; Laurillard, D. (London Review of Education, 2019)
The mass displacement of people across the world, currently estimated at 65 million, creates a massive demand for new forms of education for children, young people and adults. However, this cannot be addressed without attending to what this means for teachers and other professionals involved in education and training. Clearly, there is a need for large-scale teacher professional development (TPD). Digital technology has the potential to meet this demand, but challenges are presented by the poor digital infrastructure in contexts of mass displacement. Data from two projects are analysed to explore the viability of scaling up TPD in the form of co-designed massive open online courses (MOOCs). The first data set is from a co-designed TPD MOOC project Blended Learning Essentials, to show that digital technology can be effective for scaling up TPD, but that a sustainability plan must be in place from the outset. The second data set is from a project that built on the first to run stakeholder co-design workshops in Lebanon, as a way of developing large-scale TPD in this most challenging context. Lebanon has the highest proportion of refugee to host communities in the world. This case study indicates that MOOCs could be viable in such a context, but also highlights the need to balance the generic principles being offered with a focus on localized practice. A theory of change is presented to outline a method of meeting these challenges by employing a co-design methodology to create self-sustaining digital TPD in the context of Lebanon, and to test this model with the contexts of mass displacement experienced by other participants in the MOOC.
Number: 2 Publisher: Taylor & Francis KerkoCite.ItemAlsoKnownAs: 2339240:3R3E5UKD 2405685:IWSGHR2Y

Reflective Teacher Supervision Through Videos of Classroom Teaching - Kaneko-Marques, Sandra Mari (PROFILE Issues in Teachers' Professional Development, 2015)
The main objective of this paper is to briefly present roles of different teacher supervisors according to distinct models, highlighting the importance of collaborative dialogues supported by video recordings. This paper will present results from a qualitative study of an English as a foreign language teacher education course in Brazil. The results indicated that collaborative supervision was an efficient tool to address adversities within educational contexts and that student teachers who observed their pedagogical actions through videos became more reflective and self-evaluative, as they provided a deeper analysis regarding their practice. With collaborative supervision, teacher candidates can be encouraged to recognize and understand the complexities of language learning and teaching both locally and globally.
KerkoCite.ItemAlsoKnownAs: 10.15446/profile.v17n2.44393 2339240:MHGIE5L4 2405685:INATDUP5

Integrating problem-based learning with ICT for developing trainee teachers' content knowledge and teaching skill - Karami, Mehdi; Karami, Zohreh; Attaran, Mohammad (International Journal of Education and Development using Information and Communication Technology, 2013)
Professional teachers can guarantee the progress and the promotion of society because fostering the development of next generation is up to them and depends on their professional knowledge which has two kinds of sources; content knowledge and teaching skill. The aim of the present research was studying the effect of integrating problem-based learning with Information and Communications Technology (ICT) on developing content knowledge and teaching skill of trainee teachers. The research design was a quasi-experimental one, and the participants were elementary education trainee teachers of Shahid Bahonar teacher training center of Hamadan, Iran. Two groups were given tests of theory and practice on teaching mathematical concepts at elementary school, and then a multivariate analysis of variance (MANOVA) was conducted to compare the pretest-posttest scores. There was a significant difference, in both multivariate and univariate analyses, in scores. The findings suggest that trainee teachers who integrate problembased learning with ICT in solving a problem may develop more professional content knowledge and teaching skill than those who merely employ ICT.
KerkoCite.ItemAlsoKnownAs: 2339240:K4C794SK 2405685:T3GBM8CA 2534378:DMHQTSGS 2534378:DRGJJFB4
Keywords: _THEME: Curriculum and resources; __:import:01; __:match:final; __:matched; __:study_id:2096422; __finaldtb; ⛔ No DOI found

Understanding the relationship between teachers’ pedagogical beliefs and technology use in education: a systematic review of qualitative evidence - Tondeur, Jo; van Braak, Johan; Ertmer, Peggy A.; Ottenbreit-Leftwich, Anne (Educational Technology Research and Development, 2017)
This review was designed to further our understanding of the link between teachers’ pedagogical beliefs and their educational uses of technology. The synthesis of qualitative ﬁndings integrates the available evidence about this relationship with the ultimate goal being to facilitate the integration of technology in education. A meta-aggregative approach was utilized to analyze the results of the 14 selected studies. The ﬁndings are reported in terms of ﬁve synthesis statements, describing (1) the bi-directional relationship between pedagogical beliefs and technology use, (2) teachers’ beliefs as perceived barriers, (3) the association between speciﬁc beliefs with types of technology use, (4) the role of beliefs in professional development, and (5) the importance of the school context. By interpreting the results of the review, recommendations are provided for practitioners, policy makers, and researchers focusing on pre- and in-service teacher technology training.
KerkoCite.ItemAlsoKnownAs: 10.1007/s11423-016-9481-2 10/gbgzn4 2339240:ZFEQC5I7 2405685:HIV77NKT

Provision of continuing professional development by resource centres in selected high schools of the Copperbelt province - Mwale, Kelly Kezala (2011)
The purpose of the study was to investigate the effectiveness of resource centres in providing Continuing Professional Development to high school teachers in the Copperbelt Province.Major concerns have been expressed by various stakeholders that not enough has been done in enhancing and strengthening the concept of Continuing Professional Development among high school teachers. The Teacher Resource Centres that are supposed to be custodians of In-service Training of Teachers(INSET) now Continuing Professional Development (CPD) are perceived not to have done enough. The establishment of Teacher Resource Centres throughout the country was meant to help upgrade the skills and competencies of teachers at both basic and high school levels. These Continuing Professional Development activities that should be on-going include School Programme of In-service for the Term (SPRINT), Demonstrate, Observe, Discuss and Implement (DODIS) and Subject Meeting at the Resource Centre (SMARC).A purposive sample of 8 teacher resource centres and 12 high schools giving the study a number of 84 respondents was selected.Data were collected by way of questionnaires, interviews and Focus Group Discussions. The major informants were the following: Headteachers, Heads of Department, Teachers and Resource Centre Coordinators.The results of the study revealed that Teacher Resource Centres were not effectively providing Continuing Professional Development (CPD) activities among high school teachers. The findings further revealed that the Continuing Professional Development activities such as School Programme of In-service for the Term (SPRINT), Demonstrate, Observe, Discuss and Implement (DODIS) and Subject Meeting at the Resource Centre (SMARC) were almost non-existent in high schools despite clustering them with basic schools.Generally, the findings indicated lack of commitment both by the coordinators in Resource Centres and school administrators. Further revelations by the study indicate that little or no effort has been given to school - based workshops, seminars, professional meetings and conferences. Additionally,constant monitoring of CPD activities was not given prominence by Resource Centre Coordinators hence the glaring lapses in the actual implementation of Continuing Professional Development programmes.Further analysis of both quantitative and qualitative data revealed that there was lack of significant advocacy and sensitisation on the difference between Continuing Professional Development activities and In-service Teacher Education tenable at colleges of education and universities. In view of the research findings, recommendations were made. Teacher Resource Centres ought to enhance advocacy and sensitisation of Continuing Professional Development activities. Pedagogical competences and skills would be strengthened at high school level if Teacher Resource Centres played their expected role of providing Continuing Professional Development to teachers. The study has also shown that school administrators did not apportion equal weight to Continuing Professional Development as they did with sporting activities. There is need to give both areas equal attention.
Accepted: 2011-06-09T14:56:49Z KerkoCite.ItemAlsoKnownAs: 2405685:IX3GN9W6

Turkish pre-service teachers' reflective practices in teaching English to young learners - Güngör, Muzeyyen Nazli (Australian Journal of Teacher Education, 2016)
The course "Teaching English to Young Learners" is the first stage where pre-service teachers are introduced to a child's world, developmental characteristics, needs, interests as well as teaching and learning techniques for these learners in English language teaching pre-service teacher education programmes in Turkey. This action research study identifies the gap that pre-service teachers experience between the theoretical considerations and realities of teaching, and the problems they face in this course. It provides the opportunity for monitoring and evaluating themselves in a pre-service teacher education programme in Turkey. Hence, this piece of research aims to promote reflective practice at the preservice level in teaching English to young learners through video recorded microteaching sessions, reflective journals, and lesson plans of pre-service teachers. The study reports on the results by highlighting the contribution of these reflective tools to pre-service teachers' professional development, self- and peer- reflections and the preparedness to teach English to young learners. Finally, insights and recommendations concerning teacher educators and pre-service programmes are offered to promote reflective practice and make methodology courses more beneficial before pre-service teachers embark on their practicum experience.
Publisher: Edith Cowan University, Bradford Street, Mount Lawley, West Australia 6050, Australia Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1826521925?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.14221/ajte.2016v41n2.9 2405685:LGB6A2T8 2534378:MA7EKPTA 2534378:MK9KRY6K
Keywords: Action Research; ERIC; Current Index to Journals in Education (CIJE); Educational Technology; Elementary Education; English (Second Language); Foreign Countries; Higher Education; Journal Writing; Language Teachers; Lesson Plans; Postsecondary Education; Preservice Teacher Education; Preservice Teachers; Qualitative Research; Reflection; Reflective Teaching; Second Language Instruction; Teaching Methods; Turkey; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096127; __finaldtb

The effects of continuing professional development (CPD) through SPRINT on teacher classroom practices and student learning outcomes - Mazala, Chileya Mbasilu (2011)
This study looked at the effects of Continuing Professional Development (CPD) through School Programmes for In -Service for the Term (SPRINT) on teacher classroom practices and student learning outcomes. The purpose of the study was to find out if SPRINT had any effect on teacher classroom practice and student learning outcomes. The target population was all Ndola high schools. The sample consisted of 196 respondents that is, five head teachers, five deputy heads, fifteen heads of department, five School In- Service Providers (SIP), five Zone INSET Providers (ZIP) and twelve teachers from each of the five schools and one Resource Centre Coordinator. The sample also included one hundred grade twelve pupils, twenty randomly picked from each of the five schools Purposive sampling was used to select the schools, head teachers, heads of department, INSET providers and the subject coordinator. Teachers and pupils were selected using simple random sampling. Questionnaires, observations, interviews, Focus Group Discussions and documentary evidence were the research instruments used to gather information. A review of relevant literature and its implication for CPD was undertaken to provide interrogation framework for this study. Guskey's five levels of evaluation were used to structure the framework Data were analyzed by identifying and categorizing significant themes relevant to research objectives. The data were presented in form of tables, percentages,graphs and charts. Qualitative data from interviews were coded and emerging themes grouped into categories The themes and categories of initial data were compared with those of subsequent interviews. Categories were then regrouped to get the most significant categories and themes.The findings from this study indicated that teachers at all career stages expressed the desire to take part in Continuing Professional Development through SPRINT.Research findings also showed that SPRINT activities did impact on teacher classroom practice basing on the twelve observable skills recommended by The Ministry of Education. The findings from this study further revealed that SPRINT had an impact on student learning outcomes as shown by the average scores of students whose teachers took part in CPD and those whose teachers did not.Average scores for the latter were lower than the former category of students.The findings further revealed that although there was evidence of the effect of CPD through SPRINT on teacher classroom practices and student learning outcomes, this programme was hindered by weak organisational support.The results of the study showed that teachers were not enthusiastic about continuing with the CPD programme as it lacked adequate funding and support from both local administrators and the Ministry of Education. Teachers were not involved in identifying training needs and as such did not feel they were the owners of CPD Teachers also felt that this kind of CPD did not help in career progression as the credit system was not effective. At organizational level, this study found that policies and guidelines on how to organize and manage CPD were lacking.CPD leaders also did not have adequate training to prepare them for their roles. Because of this lack of training, CPD leaders could not carry out assessment of the effects of CPD through SPRINT on teacher classroom practices and student learning outcomes.On the basis of these findings, it is recommended that teachers should be in charge of their own CPD and be involved in needs assessment .Secondly, CPD leaders should be properly trained for their role and they should have clear job specifications. In addition, adequate funding for the programme should be made available by both the Government and the School Administration. The Ministry of Education also needs to formulate national policies and guidelines on management and evaluation of SPRINT .A standardized accreditation system which would enable teachers to experience career progression through SPRINT should also be put in place. Lastly, CPD through SPRINT should be made research based with teachers having access to INTERNET and good library facilities.
Accepted: 2011-05-19T07:47:10Z KerkoCite.ItemAlsoKnownAs: 2405685:JBMTM89Y

Enhancing the teaching skills of the multi-grade teachers through lesson study - Thephavongsa, Souphanh (International Journal of Learning, Teaching and Educational Research, 2018)
Teaching in the multi-grade class is more difficult than mono-grade for teachers, however, multi-grade teaching was defined as the best strategy to achieving access to Education For All (EFA) of children especially those from rural areas. Teachers have been working diligently but unmethodical in their classroom. This study aimed to improve and enhance the teachers' professional skills which they have been facing in the classroom through the Lesson study and discuss why most of the teachers did not like to prepare and/or develop lesson plans. There were 100 participants who teach in the multi-grade schools in the Salavan district. The results represented that pre-test scores and post-test scores from two of training groups were significantly different and found that most of teachers do not usually prepare lesson plans. The research findings also determined that a Lesson study can be beneficial to enhance the development the teachers' professional skills.https://doi.org/10.26803/ijlter.17.4.5
Number: 4 KerkoCite.ItemAlsoKnownAs: 10.26803/ijlter.17.4.5 2339240:UR5ZQL62 2405685:GB9ETR4N
Keywords: Development a lesson plan; Lesson study approach; Multi-grade class; Multi-grade teaching; Training Multi-grade teachers; ⛔ No INSPIRE recid found

Investigating effects of using digital video in teacher training in Cambodia - Lok, Leandra; Schellings, Gonny; Brouwer, Niels; Den Brok, Perry (Journal of Technology and Teacher Education, 2018)
While research has shown that video can be an effective tool in the professional learning of teachers in industrialized countries, it is unknown whether this is also true for other countries with distinctive cultural, political, and historical contexts, such as Cambodia. This paper presents results from a study which examined the effectiveness of using video to introduce student-centered teaching to teachers in Cambodia. The training consisted of collaboratively watching and discussing videos of teaching practices. A 2x2 design was used, varying group conditions (team versus pair) and relevance of the material (model video versus action video). The findings indicated that although it was not possible to determine if there had been changes in teacher behavior, using video had led to an increase in teachers' perceived knowledge of student-centered teaching, especially for the team and the model video conditions.
Publisher: Association for the Advancement of Computing in Education, P.O. Box 1545, Chesapeake, VA 23327 KerkoCite.ItemAlsoKnownAs: 2405685:DBMD28PC 2534378:5IAKXKPQ 2534378:INDI72PC 2534378:W5INGKSD 2534378:ZPX4ANVW
Keywords: Active Learning; Behavior Change; Cambodia; Cultural Context; ERIC; Current Index to Journals in Education (CIJE); Education–Computer Applications; Faculty Development; Foreign Countries; Instructional Effectiveness; Knowledge Base for Teaching; Learning; Mixed Methods Research; Questionnaires; Student Centered Learning; Studies; Teacher Attitudes; Teacher Behavior; Teacher education; Teachers; Teaching; Teaching Methods; Training; Video; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2095890; __finaldtb; ⛔ No DOI found

Interaction in a discussion list: an exploration of cognitive, social, and teaching presence in teachers’ online collaborations - Nami, Fatemeh; Marandi, S Susan; Sotoudehnama, Elaheh (ReCALL: the Journal of EUROCALL, 2018)
Discussion lists have gained a significant popularity in professional development research over the past few decades for the opportunity they provide for asynchronous interaction. This article presents findings from a small-scale case study that aimed at exploring the nature of teachers’ asynchronous exchanges in a discussion list. The data comprised the archived log of the messages in a Yahoo Group discussion list by five in-service English as a foreign language (EFL) teachers who volunteered to take part in a hybrid computer-assisted language learning (CALL) teacher education course in a state university in Iran. The discussion list was incorporated into the course to engage participants in professional dialogue on topics related to technology/CALL. During the initial data analysis, participants’ asynchronous exchanges were grouped as suggestions, questions, unclassified, answers, and delivery, drawing upon Oriogun and Cave’s (2008) SQUAD categorization, following the constant comparative method of analysis. Through a follow-up computer-mediated discourse analysis, cognitive, social, and teaching presence functional moves were identified in the data. Participants used the space not only for socializing and peer instruction but also for constructing knowledge. Despite an uneven pattern of contribution, asynchronous exchanges provided opportunities for knowledge construction at different levels of cognitive presence on topics ranging from technology tools and their affordances/constraints to computer-assisted language testing, materials development, and classroom management. The findings provide CALL teacher education researchers and course designers insights into the potential of asynchronous interaction for online and blended language teacher education.
Place: Cambridge Publisher: Cambridge University Press Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2084810389?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1017/S0958344017000349 2405685:WM42S327 2534378:59HFNMGI 2534378:A5Y5932K 2534378:EEFLCSXC 2534378:G3TW72LP
Keywords: Asynchronous Communication; Blended Learning; CALL teacher education; CASE studies; COMPUTER assisted language instruction; Cognitive processes; Collaborative learning; Colleges & universities; Computer Mediated Communication; Computer assisted instruction–CAI; Computer assisted language learning; Critical thinking; Curriculum development; Data analysis; Discourse Analysis; Distance learning; ERIC; Current Index to Journals in Education (CIJE); Educational Technology; Educational technology; English (Second Language); English as a second language instruction; Faculty Development; Foreign Countries; Foreign languages; Group Discussion; Higher Education; Higher education; Hybrid computers; Interactive learning; Iran; LANGUAGE & languages; Language Teachers; Linguistics–Computer Applications; PROFESSIONAL education; Professional development; School environment; Second Language Instruction; Second language teachers; Social factors; TEACHERS; Teacher Education Programs; Teacher education; Teachers; Teaching; Technology Uses in Education; __:import:01; __:match:final; __:matched; __:study_id:2095858; __finaldtb; asynchronous interaction; cognitive presence; online collaboration; social presence; teaching presence

New modes of teacher pre-service training and professional support - Anamuah-Mensah, Jophus; Banks, Frank; Moon, Bob; Wolfenden, Freda (Teacher education and the challenge of development: a global analysis, 2012)
KerkoCite.ItemAlsoKnownAs: 2339240:66DBFE2I 2339240:QKU3SVEH 2405685:2WMAM3CW 2405685:7TSLQG4X 2405685:QKECWWAV 2534378:3FC4SJYU
Keywords: Economic development – Effect of education on – Developing countries.; Teachers – Training of – Developing countries.; Teaching – Developing countries.

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
EdTechHub.Source: 2129771:I2CG3TP3 shortDOI: 10/ghgk6z KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1204703 10/ghgk6z 2129771:I2CG3TP3 2129771:SI7RBL6P 2405685:46SDL9HI
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Digital Literacies for International Teacher Education: a Ghanaian perspective - Taner, Lisa (The Open University, 2018)
Teacher education in Sub Saharan Africa has been highlighted as key in helping to ensure inclusive and equitable quality education across the continent. Digital technologies that support new modes of teacher education can improve access and quality in developing regions (Moon and Villet, 2017a, b; Moon, 2007; Power, 2013), however little is known about how teachers develop digital literacies to enable them to effectively use these new resources, nor the ways in which student teachers are introduced to the technologies they need to support their professional development. Given the scarcity of research in this area and with teacher support and preparation having been the least examined topics in mobile learning research, this project investigated the ways in which student teachers in one College of Education in Ghana participate in learning experiences that develop their digital literacies to support their professional development throughout the college course, both on campus and in school placements. Using ethnographic approaches within a sociocultural theoretical rationale, the aim of this research was to address the gap in literature by examining the ways in which student teachers participate in learning experiences that develop their digital literacies during their training at a College of Education in Ghana. In view of the slow pace of ICT infrastructure advancement in Ghanaian schools, tutors at one college of education are encouraging the use of student teachers’ personal devices such as mobile phones to support their professional learning, both on campus and in the absence of other equipment in school placements. Smartphone use was found to be an enabling tool for students, whose formal and informal use of communication tools such as WhatsApp supported their developing professionalism and gave them access to new ways to locate and use materials for teaching and their wider professional development, including the academic requirements of their courses.
Publisher: The Open University KerkoCite.ItemAlsoKnownAs: 2339240:HMVJWSZ2 2405685:4IUVXWK9
Keywords: ___working_potential_duplicate

Digital literacies for international teacher education: a Ghanaian perspective - Taner, Lisa (The Open University, 2018)
Teacher education in Sub Saharan Africa has been highlighted as key in helping to ensure inclusive and equitable quality education across the continent. Digital technologies that support new modes of teacher education can improve access and quality in developing regions (Moon and Villet, 2017a, b; Moon, 2007; Power, 2013), however little is known about how teachers develop digital literacies to enable them to effectively use these new resources, nor the ways in which student teachers are introduced to the technologies they need to support their professional development. Given the scarcity of research in this area and with teacher support and preparation having been the least examined topics in mobile learning research, this project investigated the ways in which student teachers in one College of Education in Ghana participate in learning experiences that develop their digital literacies to support their professional development throughout the college course, both on campus and in school placements. Using ethnographic approaches within a sociocultural theoretical rationale, the aim of this research was to address the gap in literature by examining the ways in which student teachers participate in learning experiences that develop their digital literacies during their training at a College of Education in Ghana. In view of the slow pace of ICT infrastructure advancement in Ghanaian schools, tutors at one college of education are encouraging the use of student teachers’ personal devices such as mobile phones to support their professional learning, both on campus and in the absence of other equipment in school placements. Smartphone use was found to be an enabling tool for students, whose formal and informal use of communication tools such as WhatsApp supported their developing professionalism and gave them access to new ways to locate and use materials for teaching and their wider professional development, including the academic requirements of their courses.
http://oro.open.ac.uk/54964/ KerkoCite.ItemAlsoKnownAs: 2339240:6I3C4XC6 2405685:UNPAN57F 2534378:GVRULWW2 2534378:SQKD29GI
Keywords: _Source:Intuitive; _THEME: Curriculum and resources; _THEME: Education management; _THEME: Open systems; _THEME: School management; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2426091; ___working_potential_duplicate; __finaldtb

Digital Literacies for International Teacher Education: a Ghanaian perspective - Taner, Lisa (The Open University, 2018)
Teacher education in Sub Saharan Africa has been highlighted as key in helping to ensure inclusive and equitable quality education across the continent. Digital technologies that support new modes of teacher education can improve access and quality in developing regions (Moon and Villet, 2017a, b; Moon, 2007; Power, 2013), however little is known about how teachers develop digital literacies to enable them to effectively use these new resources, nor the ways in which student teachers are introduced to the technologies they need to support their professional development. Given the scarcity of research in this area and with teacher support and preparation having been the least examined topics in mobile learning research, this project investigated the ways in which student teachers in one College of Education in Ghana participate in learning experiences that develop their digital literacies to support their professional development throughout the college course, both on campus and in school placements. Using ethnographic approaches within a sociocultural theoretical rationale, the aim of this research was to address the gap in literature by examining the ways in which student teachers participate in learning experiences that develop their digital literacies during their training at a College of Education in Ghana. In view of the slow pace of ICT infrastructure advancement in Ghanaian schools, tutors at one college of education are encouraging the use of student teachers’ personal devices such as mobile phones to support their professional learning, both on campus and in the absence of other equipment in school placements. Smartphone use was found to be an enabling tool for students, whose formal and informal use of communication tools such as WhatsApp supported their developing professionalism and gave them access to new ways to locate and use materials for teaching and their wider professional development, including the academic requirements of their courses.
Publisher: The Open University KerkoCite.ItemAlsoKnownAs: 2339240:HMVJWSZ2 2405685:4IUVXWK9
Keywords: ___working_potential_duplicate

Online teacher professional development in ICT integration in Tanzania: An experience report - Ngeze, Lucian Vumilia; Iyer, Sridhar (Proceedings of the 27th International Conference on Computers in Education., 2019)
Integration of Information and Communication Technology (ICT) in teaching and learning in schools has been hindered by many barriers, including lack of in-service teacher training, teacher beliefs and lack of infrastructure. In the effort to solve the challenge of teacher training in Tanzania, few in-service teachers, based on different parameters, are selected to participate in the face to face ICT training at the specified training centre. Scaling of such teacher training initiatives has been challenging over time. To reach more school teachers, we developed a ten-day online course, run over Moodle. A total of 134 teachers from all the regions of Tanzania registered and participated. Topics were developed based on the preference of the in-service teachers. Online surveys were used to collect qualitative and quantitative data before and after the course. Teachers were active during the duration of the course and many of them applied the skills in their schools by improving their teaching strategies, use of technology tools and sharing experiences with other teachers in their schools.
KerkoCite.ItemAlsoKnownAs: 2339240:ADH54AWX 2405685:DEL3AXBD
Keywords: ⛔ No DOI found

Demonstrating a situated learning approach for in-service teacher education in rural India: The Quality Education Programme in Rajasthan - Saigal, Anju (Teaching and Teacher Education, 2012)
Recent educational policy in India has repositioned elementary school teachers as active, reflective practitioners, not just ‘deliverers’ of syllabus material. This article examines innovations in teacher support in Rajasthan's government schools through the ‘Quality Education Program.’ Drawing on qualitative research of collaborative learning processes, the paper discusses two support strategies used by the program: professional dialogic interactions and modeling of pedagogic strategies, which paralleled introductory or developmental phases within a ‘collaborative apprenticeship model’ of teacher professional development. In doing so, the paper outlines the potential of situated, collaborative approaches for Indian in-service teacher education and education development reform, more broadly.
shortDOI: 10/f37ckq KerkoCite.ItemAlsoKnownAs: 10/f37ckq 2405685:62L4J6HD

Bridging between research and practice: Supporting professional development through collaborative studies of classroom teaching with technology - Hennessy, Sara (Sense Publishers, 2014)
This book presents a fresh approach to bridging the perceived gap between academic and classroom cultures. It describes a unique form of research partnership whereby Cambridge University academics and school teachers together grappled with and reformulated theory – through in-depth case studies analysing practice using interactive whiteboards in five subject areas. The inquiry exploited the collaborators’ complementary professional knowledge bases. Teachers’ voices are particularly audible in co-authored case study chapters. Outcomes included deeper insights into concepts of sociocultural learning theory and classroom dialogue, more analytical mindsets, sustained new practices and ways of working collegially. The book reflects upon the power of lesson video review and details how the co-inquirers negotiated “intermediate theory” – bridging educational theory and specific settings – framed in mutually accessible language and embodied in interactive multimedia resources for teacher development. These include video clips, analytic commentary from multiple perspectives, lesson materials, plus optional prompts for reflection and critique – not models of “best practice”. The resources make pedagogy explicit and vividly illustrate the book’s ideas, offering theory-informed yet practical tools designed with and for practitioners. Hennessy and colleagues have tested a model of ongoing, teacher-led development and innovation, professional dialogue and classroom trialing stimulated by discussing selected multimedia resources. The book will interest academic and teacher researchers, initial teacher educators, professional development leaders, mentors, plus practitioners interested in using interactive whiteboards and dialogic teaching. It explores widening approaches to collegial development to reach educators working in other contexts (with and without technology). This could involve intermediate theory building or shortcutting by sharing and adapting the outcomes – springboarding teachers’ further critique and professional learning. “I cannot recommend this book too highly … it weaves a complex developmental story with a range of facets. It emphasises clearly the rigour of the research that was conducted, while demonstrating the complexity of the inter-relationships, practices and issues for both teachers and researchers in developing practical and theoretical knowledge. Its graphic insights through text and associated media provide exemplars for teachers and those who work with teachers as a rich resource. It shows us all what can be achieved and the means of achieving it.” Prof. Barbara Jaworski, University of Loughborough
KerkoCite.ItemAlsoKnownAs: 2405685:TSJ3FNKZ 2534378:F6KIMYGG

How does professional development improve teaching? - Kennedy, Mary M. (Review of Educational Research, 2016)
Professional development programs are based on different theories of how students learn and different theories of how teachers learn. Reviewers often sort programs according to design features such as program duration, intensity, or the use of specific techniques such as coaches or online lessons, but these categories do not illuminate the programs’ underlying purpose or premises about teaching and teacher learning. This review sorts programs according to their underlying theories of action, which include (a) a main idea that teachers should learn and (b) a strategy for helping teachers enact that idea within their own ongoing systems of practice. Using rigorous research design standards, the review identifies 28 studies. Because studies differ in multiple ways, the review presents program effects graphically rather than statistically. Visual patterns suggest that many popular design features are not associated with program effectiveness. Furthermore, different main ideas are not differentially effective. However, the pedagogies used to facilitate enactment differ in their effectiveness. Finally, the review addresses the question of research design for studies of professional development and suggests that some widely favored research designs might adversely affect study outcomes.
Publisher: SAGE Publications Sage CA: Los Angeles, CA Extra URL: https://journals.sagepub.com/doi/abs/10.3102/0034654315626800 KerkoCite.ItemAlsoKnownAs: 10.3102/0034654315626800 2405685:T5F8AEJQ 2534378:WFATBSZB

Introducing mobile technology for enhancing teaching and learning in Bangladesh: teacher perspectives - Shohel, M. Mahruf C.; Power, Tom (Open Learning: The Journal of Open, Distance and e-Learning, 2010)
This paper reviews the themes emerging from Bangladeshi teachers’ experiences of taking part in the initial research and the development stage of a professional development programme they were involved with. The Secondary Teaching and Learning Programme is an information and communications technologies‐enhanced supported open distance learning programme of professional development in English‐language teaching. This paper presents evidence arising from semi‐structured interviews carried out with teachers from a pre‐pilot study for the English in Action project. The teachers participating in this study reflect upon six months’ experience of using professional development materials (course material of audio podcasts enhanced with text and images; videos of classroom practice; audio of classroom language) and classroom resources (audio recordings of text‐book reading passages, songs, poems and stories), all accessed via portable digital media players (iPods).
Publisher: Routledge _eprint: https://doi.org/10.1080/02680513.2010.511953 shortDOI: 10/brrchv KerkoCite.ItemAlsoKnownAs: 10.1080/02680513.2010.511953 10/brrchv 2405685:EEAEL6VW 2405685:UTNGW9R7
Keywords: Bangladesh; C:Bangladesh; English in Action support model; ___working_potential_duplicate; mobile learning; mobile technology; technology intervention

Scrutinizing practicum for a more powerful teacher education: a longitudinal study with pre-service teachers - Tülüce, Serdar Hande; Çeçen, Sevdeger (Educational Sciences: Theory and Practice, 2016)
This study aims to explore the role of school-based practicum in promoting pre-service English language teachers' professional development through the use of a longitudinal design in combination with qualitative methods. To achieve this aim, pre-service teachers were asked to successively reflect on video-recordings of their micro-lessons in their university-based methodology courses directly after delivering the micro-lessons and retrospectively after their practicum experience. The participants of this study were 13 pre-service English language teachers studying at a foundation university in Istanbul, Turkey. The same data collection methodology was adapted before and after the practicum to gain a deeper understanding of the learning stemming from school-based practicum. The data for the study came from pre- and post-self-evaluation reports as well as pre- and post-focus-group interviews that had been collected based on the pre-service teachers' video-recorded microteaching simulations. The findings indicate that pre-service teachers commented on the same pedagogical, psychological, and physical factors they had noticed regarding their micro-lesson before and after the practicum. However, some qualitative changes were detected in their views over time as they had become more learner-oriented and had developed a more reflective view of teaching following the practicum. These findings have implications for the impact of practicum for future teacher education programs.
Publisher: Educational Consultancy, Ltd (EDAM). Kisikli Mh. Alemdag Cd. Yan Yol Sk., SBK Is Merkezi No:5 Kat:1, Uskudar-Istanbul, 34692 Turkey Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1871571396?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.12738/estp.2016.1.0207 2339240:AESWNP5A 2405685:8BT7QT4R 2534378:CULKT9D2 2534378:IWBXDRHW 2534378:N5T6GPE5
Keywords: Attitude Change; Case Studies; ERIC; Current Index to Journals in Education (CIJE); English (Second Language); Focus Groups; Foreign Countries; Higher Education; Language Teachers; Learning Processes; Longitudinal Studies; Microteaching; Physical Characteristics; Postsecondary Education; Practicums; Preservice Teacher Education; Preservice Teachers; Pretests Posttests; Professional Development; Psychological Patterns; Qualitative Research; Reflective Teaching; Second Language Instruction; Self Concept; Self Evaluation (Individuals); Simulation; Student Teacher Attitudes; Teaching Methods; Transformative Learning; Turkey (Istanbul); Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096126; __finaldtb

Introducing mobile technology for enhancing teaching and learning in Bangladesh: teacher perspectives - Shohel, M. Mahruf C.; Power, Tom (Open Learning: The Journal of Open, Distance and e-Learning, 2010)
This paper reviews the themes emerging from Bangladeshi teachers’ experiences of taking part in the initial research and the development stage of a professional development programme they were involved with. The Secondary Teaching and Learning Programme is an information and communications technologies‐enhanced supported open distance learning programme of professional development in English‐language teaching. This paper presents evidence arising from semi‐structured interviews carried out with teachers from a pre‐pilot study for the English in Action project. The teachers participating in this study reflect upon six months’ experience of using professional development materials (course material of audio podcasts enhanced with text and images; videos of classroom practice; audio of classroom language) and classroom resources (audio recordings of text‐book reading passages, songs, poems and stories), all accessed via portable digital media players (iPods).
Publisher: Routledge _eprint: https://doi.org/10.1080/02680513.2010.511953 shortDOI: 10/brrchv KerkoCite.ItemAlsoKnownAs: 10.1080/02680513.2010.511953 10/brrchv 2405685:EEAEL6VW 2405685:UTNGW9R7
Keywords: Bangladesh; C:Bangladesh; English in Action support model; ___working_potential_duplicate; mobile learning; mobile technology; technology intervention

Professionalizing in- service teachers’ focus on technological pedagogical and content knowledge - Getenet, Seyum Tekeher; Beswick, Kim; Callingham, Rosemary (Education and Information Technologies, 2016)
In Ethiopia, primary school teachers of science and mathematics are encouraged to integrate Information and Communication Technology (ICT) into their teaching as a means to improve the quality of education. However, there has not been the same emphasis placed on providing professional learning opportunities for teachers on how to use ICT in their teaching. The present study investigated how a group of practising primary school science and mathematics teachers developed the skills needed to integrate ICT into their teaching. The study employed a combination of qualitative and quantitative research methods within an action research approach. The teachers took part in activities from a Technological Pedagogical and Content Knowledge (TPACK) based professional learning workshop, including designing lessons, classroom instruction, and reflection activities in teams. A lesson evaluation sheet, questionnaire, observation checklist, and logbook were used to gather data. The results showed that the teachers acquired an improved competency to integrate available ICT into their teaching through the intervention activities.
shortDOI: 10/gf5f37 KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-013-9306-4 10/gf5f37 2339240:X5KT8D38 2405685:M6FHA5XE

Prospective teachers' teaching experience: teacher learning through the use of video - Osmanoglu, Aslihan (Educational Research, 2015)
Background: Future teachers need to observe, interpret and analyse teaching during the initial teacher education period. The use of videoed teaching and learning in teacher education promotes reflection, and analysing videos of teaching is helpful in learning effective classroom practices that prospective teachers mostly do not have the chance to observe during fieldwork experiences. The analysis of videos of teaching can be seen as a way to enhance the development of prospective teachers' professional vision, which, in turn, improves instruction. Purpose: The purpose of this study was to examine prospective teachers' reflections on video examples depicting their own teaching experiences. It aimed to create a professional development environment to facilitate the prospective teachers' reflection on their own videos and those of their peers to improve their professional vision. Sample: This study was conducted with over 200 (in 31 groups) third-year prospective mathematics teachers in a university in Western Turkey. The student teachers, receiving training to teach first- to fourth-grade elementary school pupils, were taking a teaching methods course. Design and methods: In the first week of the semester, the student teachers, working in groups, were assigned mathematics topics to teach the elementary school pupils. During the semester, each group prepared by trying out their activities in front of other student teachers in other groups. At the end of the semester, one student teacher from each group presented a short lesson related to their mathematical topic to the elementary school pupils. This lesson was videotaped, then later it was watched and discussed by the student teachers. Of the student teachers who undertook the teaching in the videos, 22 volunteers agreed to be interviewed. All groups of student teachers provided written reflections on their experience. Selected videos of the class discussions about the videos of teaching were also used for triangulation. The data were analysed to identify the issues the prospective teachers reflected upon. A content analysis technique was employed. Results: The data indicated that the prospective teachers were able to reflect on several issues related to effective teaching, connect their theoretical knowledge to their practice and consider issues related to pupil learning and difficulties. Conclusion: The findings suggested that the use of video, together with discussions between the student teachers, had the potential to create promising learning opportunities for prospective teachers.
Publisher: Routledge, Available from: Taylor & Francis, Ltd. 325 Chestnut Street Suite 800, Philadelphia, PA 19106 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1826519864?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1080/00131881.2015.1117321 2339240:IDCYSM7U 2339240:JN6DATHN 2405685:8R9AMXSP 2405685:UXX82Q2E 2534378:2ENRXCPY 2534378:6ZC4QF9U 2534378:CZGC7EHH
Keywords: Case Method (Teaching Technique); Case Studies; Case-based pedagogy; Content Analysis; Data Analysis; Discussion (Teaching Technique); EDUCATION of student teachers; EFFECTIVE teaching; ELEMENTARY school teachers; ERIC; Current Index to Journals in Education (CIJE); Educational Benefits; Electronic Learning; Elementary Education; Elementary School Teachers; Foreign Countries; Higher Education; Knowledge Base for Teaching; Learning Activities; Mathematics Teachers; Methods Courses; Microteaching; Outcomes of Education; PROFESSIONAL education; Postsecondary Education; Preservice Teacher Education; Preservice Teachers; Reflective Teaching; Student Teacher Attitudes; Student Teachers; TEACHER education; TEACHING methods; TRAINING of student teachers; Teacher Effectiveness; Teaching Experience; Theory Practice Relationship; Turkey; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096187; __finaldtb; class discussions; prospective teacher education; reflection; video case study

Using design-based research to bring partnership between researchers and practitioners - Getenet, Seyum (Educational Research, 2019)
Background: A key aim of educational research is for findings to inform practice, thereby bringing about improvements in teaching and learning. However, the relationship between research and practice is complex, and there is often no clear link between changes in practice and research findings. One of the challenges for research and practice is breaking down barriers and finding effective and sustainable ways to translate research findings into practical solutions in the classroom.Purpose: This discursive paper focuses on describing the nature of the partnership working involved when a design-based research (DBR) approach was employed to bring researchers and practitioners together. The researchers and practitioners worked in collaboration to design a professional development (PD) programme, in order to solve classroom problems and enhance practitioners’ research engagement.Sources of evidence: This paper describes the author’s experience of using DBR to co-design a PD programme that was responsive to a particular context and practitioners’ needs. It illustrates and exemplifies the ways in which the researcher–practitioner collaboration itself sits at the heart of the design process and enabled solutions to be found. The paper also considers the epistemological positions of the practitioners and researchers in the different stages of DBR. The context for the description is a mixed-methods intervention study conducted in two colleges of teacher education, which documented the design and refinement of a PD programme to facilitate teachers’ effective use of technology to teach mathematics.Discussion and conclusions: The examples presented and discussed here suggest how a DBR process is able to facilitate fruitful collaborations between researchers and practitioners and increase engagement in research. By working with practitioners to design interventions such as PD programmes, DBR can provide a practical approach for improving practice and deepening the relationship between educational research and classroom practice.
EdTechHub.Copy: 2129771:XWT48UG5 shortDOI: 10/ggd8hp KerkoCite.ItemAlsoKnownAs: 10.1080/00131881.2019.1677168 10/ggd8hp 2129771:XWT48UG5 2339240:FNGCAY8H 2405685:SXE25TP7
Keywords: Design-based research; evidence-informed practice; practice; practitioners; professional development; teacher education

Low Cost Mobile Phones for Large Scale Teacher - Walsh, Christopher S; Shaheen, Robina; Power, Tom; Hedges, Claire; Kahtoon, Masuda; Mondol, Sikander (2012)
Education has the power to transform societies and contribute to social and economic development. In this paper we present the mobile technologies used for teacher professional development (TPD) and communicative language teaching in English in Action (EIA). The project aims to assist 25 million people access greater social and economic opportunities through English language teaching and TPD. EIA, in partnership with the Government of Bangladesh, will work with 80,000 teachers through a work-based programme of TPD using audio and visual resources on low cost mobile phones. With access to over 700 audio files aligned with the national textbook English for Today and professional development films that explain and then illustrate successful student-centred English teaching and learning, the project has already documented significant improvement in teachers’ and pupils’ English language competency. This paper provides an account of, and rationale for, the changes in the technologies used across two phases of the project, from the iPod Nano and Touch used in the pilot study with 690 teachers (2009-2010) to the low cost Nokia C1-01 mobile phone with a micro secure digital (SD) being used in upscaling to 12,500 teachers (2012-2014). We argue the low cost alphanumeric mobile phone with micro SD cards provides unprecedented opportunities to both deliver TPD and improve teachers’ and students’ communicative English language skills. The paper considers the unique suitability mobile phones present for resource constrained education systems in developing countries. Simultaneously we highlight the need for further application and research into the use of mobile technologies, not only for large-scale TPD projects, but for a diversity of international development projects and programmes which aim to achieve sustainable change at scale.
KerkoCite.ItemAlsoKnownAs: 2405685:XPZGL85X

A framework for an ICT-based development program for science teachers in state universities and colleges in region VI - Magallanes, Amel Lavezores; Lavezores, Amel (Universal Journal of Educational Research, 2014)
Curriculum reform is central to the aspirations of many developing countries as they strive to deliver a quality education to their citizens. In State Universities and Colleges in Region VI, with its remarkable achievement of a high literacy rate in a few decades, the next step is bringing its resources to bear on providing a quality education so that Filipino science professors and students may take their places in the global labor force. This study concerns the integration of information and communications technologies (ICT) into the science curriculum of Higher Education Institutions in State Universities and Colleges in the Philippines particularly in Region VI, and the training and development requirements of science professors in this regard. A mixed methodology was employed to obtain qualitative data from 11 policy makers as represented by the Vice President of Academic Affairs of the SUC's in region VI, and quantitative data from a questionnaire for which 139 replies were received from SUC's science professors in Region VI.The findings of this study confirmed those citations in the literature that inefficient management planning and inadequate resources influence the integration of ICT in the science curriculum. Furthermore, the qualitative and quantitative findings confirmed that teachers' access to training is affected by time constraints, ineffective ICT course material, unavailability of ICT infrastructures and facilities, and high cost of ICT trainings. The policy makers interviewed in this study perceived the teachers as having a positive attitude toward ICT integration in the science curriculum, quantitative data from the teachers pointed to a high interest in ICT integration, and their willingness to pursue further professional development in the effective use of ICT in the science curriculum. Furthermore, age factor exhibited a significant difference in ICT skills, utilization and individual barriers of science teachers in SUC's Region VI. The length of service also showed a very significant difference as to the ICT skills, utilization attitudes, and individual barriers of the teacher respondents. However, as to their gender and highest educational attainment, home location and school location, there was no such factor implicating a non-significant difference in the attitudes, skills, utilization and perceived barriers.
Publisher: Horizon Research Publishing, 506 North Garfield Avenue #210, Alhambra, CA 91801 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1697502673?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.13189/ujer.2014.020909 2405685:FXQZCGHG 2534378:CCZ6ZKIL
Keywords: Barriers; College Faculty; College Science; Computer Literacy; Computer Uses in Education; ERIC; Current Index to Journals in Education (CIJE); Foreign Countries; Higher Education; Information Technology; Mixed Methods Research; Philippines; Postsecondary Education; Science Teachers; State Colleges; State Universities; Teacher Attitudes; Technology Integration; Training

Mobile literacy among Syrian refugee women teachers - Bradley, Linda; Bahous, Rima; Albasa, Ali (CALL and complexity – short papers from EUROCALL 2019, 2019)
This research project investigates mobile literacy of Syrian refugee women teachers settled in Lebanon and Sweden. Our research provides input into Syrian refugee women teachers' professional aspirations and their connection to informal mobile learning. In both countries, training programs are used for these newly arrived teachers, enabling them to move forward in their careers, where digital and mobile learning play an important part. The purpose is to investigate how Syrian refugee women teachers are blending their teaching profession and vocational training with mobile literacy and digital technology. A qualitative method approach was applied, interviewing 20 refugee women in Lebanon and Sweden, all teachers from Syria. The outcomes show that the teachers are developing their vocational abilities in getting more career-oriented training in their areas of education by means of enhancing their language skills through mobile technology. [For the complete proceedings, see ED600837.]
Publisher: Research-publishing.net, La Grange des Noyes, 25110 Voillans, France KerkoCite.ItemAlsoKnownAs: 10.14705/rpnet.2019.38.986 2339240:ZAUCKJ67 2405685:45VMGDEX 2405685:8RNRFPG7 2405685:HUEZG3W8 2534378:93K5R9FV 2534378:NR6VFNNC
Keywords: Career Development; Cross Cultural Studies; ERIC; Resources in Education (RIE); Faculty Development; Females; Foreign Countries; Handheld Devices; Informal Education; Information Technology; Land Settlement; Lebanon; Literacy; Occupational Aspiration; Refugees; Second Language Instruction; Second Language Learning; Sweden; Syria; Teacher Attitudes; Telecommunications; Videoconferencing; __:import:01; __:match:final; __:matched; __:study_id:2095768; ___working_potential_duplicate; __finaldtb

Digital storytelling and reflection in higher education: a case of pre-service student teachers and their lecturers at a university of technology - Ivala, Eunice; Gachago, Daniela; Condy, Janet; Chigona, Agnes (Journal of Education and Training Studies, 2014)
Employers in South Africa are calling for students graduating from higher education institutions (HEIs) to exhibit the capacity for reflection. However, many tertiary institutions fall short in allowing opportunities for reflection. As a result, HEIs are grappling to find ways of fostering reflection amongst their students. This paper argues that digital storytelling if implemented properly is one of the ways which can be used to help HEIs in this accomplishment. It documents results of production of digital stories by 29 final-year pre-service student teachers at the Cape Peninsula University of Technology (CPUT), South Africa, as part of their assessment in their professional development course. The study was informed by structuration theory and levels of reflection and cognitive processing to help the researchers understand the potential of digital storytelling in enhancing reflection. Qualitative methods of collecting data were utilized. Focus group interviews were conducted with the students and their facilitators to elicit whether production of digital stories led to reflection. Findings showed that the production of digital stories promoted the three levels of reflection and thus deep learning and higher-order thinking skills.
Publisher: Redfame Publishing Inc, 9450 SW Gemini Drive #99416, Beaverton, OR 97008 KerkoCite.ItemAlsoKnownAs: 10.11114/jets.v2i1.286 2339240:5UUL3KML 2405685:ECTD3I55 2405685:IZMKPN8S 2534378:IEFUXYHR 2534378:KPXZTCDD
Keywords: Case Studies; Cognitive Processes; College Faculty; ERIC; Current Index to Journals in Education (CIJE); Educational Technology; Focus Groups; Foreign Countries; Higher Education; Personal Narratives; Postsecondary Education; Preservice Teachers; Professional Development; Qualitative Research; Reflection; Skill Development; South Africa; Story Telling; Teaching Methods; Technology Uses in Education; Video Technology; __:import:02; __:match:final; __:matched; __:study_id:2096367; __finaldtb

Strengthening Teacher Professional Development: Local and global communities of practice in Kakuma Refugee Camp - Mendenhall, Mary (Columbia University, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:7WPJ543M 2405685:32Z977JS
Keywords: C:Kenya / Rwanda

Technology for professional development: access, interest and opportunity for teachers of English in South Asia - British Council (British Council, 2015)
KerkoCite.ItemAlsoKnownAs: 2405685:UE23QGKH

An overview of e-learning in China: History, challenges and opportunities - Wang, Yan; Liu, Xuan; Zhang, Zhenhong (Research in Comparative and International Education, 2018)
The Chinese government has attached great importance to the development of e-learning since its emergence in the 1990s. As a consequence of the implementation of a series of policies, China has made significant achievements in the e-learning arena with respect to infrastructure construction, production of resources, academic education, non-academic training, and education for disadvantaged groups. However, due to the constraints of China’s traditional culture, information literacy, and educational mechanisms, challenges have emerged in the implementation of e-learning that need urgently to be addressed. As e-learning in China continues to grow, major research areas such as students’ and teachers’ perspectives on developments in e-learning, teachers’ pedagogical capacity and ongoing professional development in e-learning settings, and the production of more convenient and useful e-learning resources, are likely to be topics of continuing research interest.
Publisher: SAGE Publications KerkoCite.ItemAlsoKnownAs: 10.1177/1745499918763421 2405685:5RZFNBJU 2534378:WASU4R5U
Keywords: Challenges; China; ICT in education; e-learning; professional development; successes

Identifying the essential ingredients to literacy and numeracy improvement: teacher professional development and coaching, student textbooks, and structured teachers’ guides - Piper, Benjamin; Zuilkowski, Stephanie; Dubeck, Margaret; Jepkemei, Evelyn; King, Simon J. (World Development, 2018)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.worlddev.2018.01.018 2339240:W6C7ZW2X 2405685:53C9AZ8Q 2405685:RIK9NWV4 2534378:E5TCHLS4 2534378:QFTE8W6H
Keywords: Africa; Literacy; Numeracy; Program evaluation; Randomized controlled trial; Reading; ___working_potential_duplicate

Identifying the essential ingredients to literacy and numeracy improvement: teacher professional development and coaching, student textbooks, and structured teachers’ guides - Piper, Benjamin; Zuilkowski, Stephanie; Dubeck, Margaret; Jepkemei, Evelyn; King, Simon J. (World Development, 2018)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.worlddev.2018.01.018 2339240:W6C7ZW2X 2405685:53C9AZ8Q 2405685:RIK9NWV4 2534378:E5TCHLS4 2534378:QFTE8W6H
Keywords: Africa; Literacy; Numeracy; Program evaluation; Randomized controlled trial; Reading; ___working_potential_duplicate

Emerging fundamental issues of teacher education in Tanzania: a reflection of practices - Mgaiwa, Samson J (Educational Process: International Journal, 2018)
Quality of teachers is recognized as one of the critical dimensions for promoting student learning in schools. However, in Tanzania there are several emerging issues that affect teacher education and teachers, and as a result affect students’ learning. The existing corpus of literature indicates a death of studies on the systematic understanding of issues that affect teacher education in Tanzania, especially at a time when education across the world is encountering a number of challenges. Employing documentary review and interviews as data collection methods, this paper attempts to analyze the emerging issues affecting teacher education in Tanzania. Employing the Teacher Education Model for the 21st Century, the paper identified five major issues affecting teacher education namely; lack of specific policies for teacher education, lack of continuing professional development, lack of an autonomous teacher regulatory body, inadequate ICT and teacher education, and poor quality of candidates joining teacher education. Generally, the findings indicate that teacher education is not effectively planned in terms of policy imperatives to meet the contemporary professional demands for 21st century education in Tanzania, and beyond. Finally, conclusions and certain recommendations which take a futuristic perspective in preparing 21st century teachers are offered.
Place: Kutahya Publisher: Universitepark, Co. Ltd. Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2377711234?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.22521/edupij.2018.74.3 2339240:5CD78LSE 2405685:9MDTIC8U 2534378:6CREM8X4 2534378:Q89SIFIE
Keywords: 21st century; Education; Learning; Tanzania; Teacher education; __:import:01; __:match:final; __:matched; __:study_id:2095912; __finaldtb; students’ learning; teacher education; teachers

Designing an Educational Innovation to Achieve Scale: Five Critical Concepts - Dede, Chris (The EvoLLLution, 2016)
Research has documented that in education, unlike other sectors of society, the scaling of successful instructional programs from a few settings to widespread use across a range of contexts is very difficult (Dede, Honan, & Peters, 2005). In fact, research typically shows a huge influence of setting (e.g., the teacher’s content preparation, students’ self-efficacy, prior […]
KerkoCite.ItemAlsoKnownAs: 2405685:TX3BDCL8

Effectiveness of Teachers’ Guides in the Global South: Scripting, Learning Outcomes, and Classroom Utilization - Piper, Benjamin; Sitabkhan, Yasmin; Mejia, Jessica; Betts, Kellie (RTI Press, 2018)
This report presents the results of RTI International Education’s study on teachers' guides across 13 countries and 19 projects. Using quantitative and qualitative methods, we examine how teachers’ guides across the projects differ and find substantial variation in the design and structure of the documents. We develop a scripting index so that the scripting levels of the guides can be compared across projects. The impact results of the programs that use teachers’ guides show significant impacts on learning outcomes, associated with approximately an additional half year of learning, showing that structured teachers’ guides contribute to improved learning outcomes. During observations, we find that teachers make a variety of changes in their classroom instruction from how the guides are written, showing that the utilization of structured teachers’ guides do not create robotic teachers unable to use their own professional skills to teach children. Unfortunately, many changes that teachers make reduce the amount of group work and interactivity that was described in the guides, suggesting that programs should encourage teachers to more heavily utilize the instructional routines designed in the guide. The report includes a set of research-based guidelines that material developers can use to develop teachers’ guides that will support effective instructional practices and help improve learning outcomes. The key takeaway from the report is that structured teachers' guides improve learning outcomes, but that overly scripted teachers' guides are somewhat less effective than simplified teachers' guides that give specific guidance to the teacher but are not written word for word for each lesson in the guide.
shortDOI: 10/ggjrfk KerkoCite.ItemAlsoKnownAs: 10.3768/rtipress.2018.op.0053.1805 10/ggjrfk 2339240:G6QUKYB2 2405685:8N3DSXF9 2405685:BX25H7CF 2405685:NLYSQ2ZG 2534378:AJ5Q28IL

Transforming education for girls in Tanzania and Nigeria: Cross country analysis of endline research studies - Unterhalter, Elaine; Heslop, Jo (ActionAid, 2012)
This cross country summary of the findings from the endline study conducted for the TEGINT project highlights a number of issues of particular pertinence to the community of policy makers, practitioners, and researchers concerned with gender equality, rights and girls’ education. Firstly, the considerable expansion of education provision at primary and junior secondary levels enhances girls’ enrolment, attendance, progression, attainment and empowerment. However, there are regional and locational differences, and the effects of the emergence of private schools on gender equality and girls’ empowerment merits careful scrutiny. It is a matter of concern, that despite the introduction of free primary education, schools continue to charge levies and that the costs of improving education are being passed down to the poorest. Secondly, there are clear indications that girls’ clubs give an important space for girls to learn about their rights and confidence to articulate solutions to their problems. This is the case both when girls in clubs come from higher performing girls in terms of class position and more marginalised girls. Thus girls clubs, widely used in many projects throughout Africa, but not till now well evaluated, appear an important strategy to continue to support. Thirdly, rurality appears as a particular condition of marginalisation, associated with higher levels of gender inequality. This is evident from the lower levels of girls’ empowerment in rural schools, and differences in articulating solutions. Thus particularly engaged interventions are needed with girls in remote areas to support empowerment. Fourthly, while improving teacher qualifications and engagement with gender equality is a necessary condition for enhancing education rights for all children, this is not a standalone intervention, and needs to be supported by other initiatives, possibly associated with teachers’ pay, work conditions and status. Fifthly, an intervention like TEGINT, appears particularly useful in helping to break the silence around gender based violence, however, such an intervention cannot be seen in isolation from work on other aspects of gender inequalities, poverty, and limited social provision. In a country like Tanzania, where there is more legislation and political action around gender equality than in Nigeria, girls, even the poorest, appear more knowledgeable about rights. Gender equality and girls’ education cannot thus be separated from other initiatives on rights, social development and addressing injustice.
Num Pages: 18 Publication Title: ActionAid KerkoCite.ItemAlsoKnownAs: 2339240:4FGB56K3 2405685:53CECDLI

Cultivating a personal learning network that leads to professional change - Stewart, Benjamin L. (Northcentral University, 2015)
Teacher professional development opportunities in Mexico are currently lacking. The traditional approaches of professional development such as workshops and conferences are commonplace but do little to bridge the gap between abstract concepts about teaching and learning and the practicalities teachers face in the classroom. The purpose of this qualitative multiple case study was to describe how ideas, materials, and social interactions form a PLN through online, informal pedagogical dialogues among English language educators as it relates to professional learning. The five participants of this study were selected from a total of 10 based on their willingness to complete an informed consent form, complete an initial online survey, interact with other professionals publically online, and participate in a final interview. The online survey contained demographic information about each case and included both open and closed items; a content analysis was done on public interactions that tool place online; and a final in-depth interview used open questions to inquire about how respective PLNs changed over time. All data was coded, categorized, and placed into themes based on the ideational, material, and social aspects of each PLN. The findings show that professional knowledge, skills sets, and overall dispositions emerge in unique ways based on how ideas, technologies, and personal contacts interrelate with each other over time, and that an individual’s PLN provides unanticipated benefits when sharing publicly online.
ISBN: 978-1-339-39148-9 Publication Title: ProQuest Dissertations and Theses 3746019 Loc in Archive 1758252241 KerkoCite.ItemAlsoKnownAs: 2405685:TCB3AT84 2534378:8ZJEL8UE 2534378:HG5HYUVR
Keywords: 0444:Foreign language education; 0449:Educational leadership; 0710:Educational technology; Actor-network theory; Complexity; Content analysis; Education; Educational leadership; Educational technology; English; Foreign Language; Learning; Personal learning network; Polls & surveys; Teacher education; __:import:01; __:match:final; __:matched; __:study_id:2096277; __finaldtb

Developing great teaching: lessons from the international reviews into effective professional development - Cordingley, P; Higgins, S; Greany, T; Buckler, N; Coles-Jordan, D; Crisp, B; Saunders, L; Coe, R (Teacher Development Trust, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:VRGQHSQ6 2405685:P7V7CHIN

Recommendation 7: Use ICT to provide access to content, professional development and professional learning communities - Lawrie, J.; Hennessy, Sara; Haßler, Björn; Phalachandra; Lawrie, J. (Where it's needed most: Quality professional development for all teachers, 2015)
EdTechHub.Source: 2129771:KQGAREE9 EdTechHub.Source: 2129771:KQGAREE9 KerkoCite.ItemAlsoKnownAs: 2129771:KQGAREE9 2405685:PKLI25VA
Keywords: C:Fragile contexts; dode_eth-src-dode; dode_eth-trf2-dode

Developing Quality Teacher Professionals: a Reflective Inquiry on the Practices and Challenges in Tanzania - Anangisye, William A.L. (Papers in Education and Development, 2011)
KerkoCite.ItemAlsoKnownAs: 2405685:MG76SQYP
Keywords: ⛔ No DOI found

English in Action: a new approach to continuing professional development through the use of mediated video, peer support and low-cost mobilephones in Bangladesh - Woodward, Clare; Griffiths, Malcolm; Solly, Mike (Innovations In The Continuing Professional Development Of English Language Teachers, 2014)
KerkoCite.ItemAlsoKnownAs: 2405685:VLPHGQ5H
Keywords: C:Bangladesh

Cultivating a Personal Learning Network that Leads to Professional Change - Stewart, Benjamin L (2015)
Teacher professional development opportunities in Mexico are currently lacking. The traditional approaches of professional development such as workshops and conferences are commonplace but do little to bridge the gap between abstract concepts about
KerkoCite.ItemAlsoKnownAs: 2339240:LTYD65AU 2405685:N45ZAWC5
Keywords: ⛔ No DOI found

Cultivating a Personal Learning Network that Leads to Professional Change - Stewart, Benjamin L (2015)
Teacher professional development opportunities in Mexico are currently lacking. The traditional approaches of professional development such as workshops and conferences are commonplace but do little to bridge the gap between abstract concepts about
KerkoCite.ItemAlsoKnownAs: 2339240:LTYD65AU 2405685:N45ZAWC5
Keywords: ⛔ No DOI found

USAID/Madagascar impact evaluation of the Mahay Mamaky Teny (MMT) project - Moussa, Wael; Cao, Yvonne; Louge, Nathalie (United States Agency for International development, 2018)
KerkoCite.ItemAlsoKnownAs: 2405685:57KZZLLD 2405685:DXY44ZMG

Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason; Thornton, Rebecca L. (SSRN Electronic Journal, 2018)
shortDOI: 10/ghgn5h KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.3002723 10/ghgn5h 2405685:NY5IKG96
Keywords: _C:Australia AUS; _C:Chad TCD; _C:Ecuador ECU; _C:India IND; _C:Kenya KEN; _C:Mexico MEX; _C:Spain ESP; _C:Tanzania TZA; _C:Uganda UGA; _C:United States USA; __C:scheme:1

Technology for Teacher Training - IDEAS (IDEAS | Institute of Development and Economic Alternatives, 2017)
The project will be introducing a new model of delivering in-service teacher training to government sector primary school teachers (PSTs), which builds upon the existing structure of cluster-based Continuous Professional Development (CPD) in Punjab.The Directorate of Staff Development (DSD) employs a cluster-based approach to in-service teacher training which constitutes a cascading model. Although the model […]
KerkoCite.ItemAlsoKnownAs: 2339240:6KEW4AH9 2405685:8E46E4T2

Hello, I’m Björn, Director of Research – The EdTech Hub - Haßler, Björn (EdTech Hub, 2019)
I’m Dr Björn Haßler, one of the three Directors of Research for the programme. Research, and particularly at-scale research, is a core focus for the #EdTechHub and that’s why we have three Directors of Research, who will also introduce themselves. I am — we all are — extremely happy that we have been awarded the programme. We, like all our competitors, worked hard for around 1.5 years until the final submission. However, this work paid off! It means we can get going on the important mission.
EdTechHub.Copy: 2129771:NPLNWHCZ shortDOI: 10/ghgnfd KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3906829 10/ghgnfd 2129771:NPLNWHCZ 2129771:XKQV2EDS 2405685:3IM8DBXI
Keywords: _DOILIVE; _EdTechHub_Output; _yl:r; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

OER4Schools: Participants Book - Hennessy, Sara; Haßler, Björn; Blair, Janet; Duggal, Nitu; Shin Leong, Wei; Makonga, Abel; Tembo, Agness (The Centre for Commonwealth Education, 2014)
KerkoCite.ItemAlsoKnownAs: 2339240:58TW376N 2405685:FBGNRJ43
Keywords: dode_eth-src-dode; dode_eth-trf2-dode

Worst practice in ICT use in education - Trucano, Michael (World Bank Blogs, 2010)
In business and in international development circles, much is made about the potential for 'learning from best practice'. Considerations of the use of educational technologies offer no exception to this impulse. That said, 'best practice' in the education sector is often a rather elusive concept (at best! some informed observers would say it ...
KerkoCite.ItemAlsoKnownAs: 2405685:5KWQPQ8G
Keywords: auto_merged

An Evaluation of ELLN Digital: Technology-Supported Teacher Professional Development on Early Language, Literacy, and Numeracy for K-3 Teachers - Oakley, Grace; King, Ronnel; Scarparolo, Gemma (Digital Learning for Development, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:KW3JXUFD 2405685:QDANF5S7
Keywords: ⛔ No DOI found

Mathematical modelling in teacher education: dealing with institutional constraints - Barquero, Berta; Bosch, Marianna; Romo, Avenilde (ZDM: The International Journal on Mathematics Education, 2018)
Considering the general problem of integrating mathematical modelling into current educational systems, this paper focuses on the "ecological dimension" of this problem–the institutional constraints that hinder the development of mathematical modelling as a normalised teaching activity–and the inevitable step of the professional development of teachers. Within the framework of the Anthropological Theory of the Didactic, this step is approached using the "study and research paths for teacher education" (SRP-TE), an inquiry-based process combining practical and theoretical questioning of school mathematical activities. We present a research study focusing on the design and analysis of an online and distance-learning course for in-service mathematics teachers based on the SRP-TE methodology. This course starts from the initial question of how to analyse, adapt and integrate a learning process related to mathematical modelling and how to sustain its long-term development. Our analysis is based on a case study consisting in four successive editions of a course for Latin American in-service mathematics teachers held at the Centre for Applied Research in Advanced Science and Technology in Mexico. The starting point is a modelling activity about forecasting the number of Facebook users, which includes functional modelling and regression. The results show how the course represents a valuable instrument to help teachers progress in the critical issue of identifying institutional constraints–most of them beyond the scope of action of teachers and students and not approached by previous research–hindering the integration of mathematical modelling in current secondary schools.
Publisher: Springer, 233 Spring Street, New York, NY 10013 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2101593199?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1007/s11858-017-0907-z 2339240:4YXECT54 2405685:2GGB99HT 2405685:6B4BREQ8 2534378:8BWRCH2S 2534378:RTGC7399
Keywords: Anthropological theory of the didactic; Barriers; Case Studies; Distance Education; ERIC; Current Index to Journals in Education (CIJE); Ecological Factors; Ecology; Foreign Countries; Functions; Inservice Teacher Education; Institutional constraints; Instructional Design; Mathematical Models; Mathematical modelling; Mathematics Teachers; Mexico; Online Courses; Prediction; Regression (Statistics); Social Media; Study and research path; Teacher education; __:import:01; __:match:final; __:matched; __:study_id:2095891; __finaldtb

Identifying strategies to enhance the educational inclusion of visually impaired children with albinism in Malawi - Lynch, Paul; Lund, Patricia; Massah, Bonface (International Journal of Educational Development, 2014)
Oculocutaneous albinism is an inherited condition with significant health and social impact on the lives of those affected throughout sub-Saharan, including in Malawi. Myths and superstitions surrounding the condition lead to stigmatisation, rejection and misconceptions. In a participatory study, consultations with educational professionals, children with albinism and their families documented the barriers to full educational access and revealed low-cost strategies that could be implemented in mainstream schools, to minimise the effect of the visual impairment associated with albinism. These were captured in two information booklets in English and vernacular, one for children and the other appropriate for teacher training.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2014.07.002 2339240:MXTDK768 2405685:K9AQNHDY
Keywords: Albinism; Resource centres; Special educational needs; Teacher training; Visual impairment

A different approach to scaling up educational technology initiatives - Trucano, Michael (World Bank Blogs, 2013)
the way most projects 'scale up' just might yield inequitable results Much is made of the necessity to 'scale up' in international development circles. Here at the World Bank, a quick search on our web site reveals publications and conferences with titles like Scaling Up Knowledge Sharing for Development, Global ...
KerkoCite.ItemAlsoKnownAs: 2405685:FJEJAEUD

Policy Report on UNHCR’s Community Technology Access Program: Best Practices and Lessons Learned - Anderson, Jessica (Refuge: Canada's Journal on Refugees, 2013)
This report gives an overview of UNHCR’s Community Technology Access (CTA) program, which aims to improve education and livelihood opportunities for displaced populations via technology. Th e paper analyzes the key findings of a comprehensive external evaluation of the program conducted in 2012. According to the evaluation, the areas of greatest positive impact for people of concern were in the enjoyment of basic rights to freedom of expression and information, in building relationships with the host community, and social networking. However, access to technology alone is not sufficient to achieve the goals of quality education and self-reliance. Therefore, the evaluation recommends developing strategic, contextualized education and livelihood content and tools in order to achieve the desired goals of learning, skills, and access to employment, as well as a reassessment of CTAs’ potential for operational and fiscal autonomy in different countries.
Number: 1 shortDOI: 10/gg26fc KerkoCite.ItemAlsoKnownAs: 10/gg26fc 2339240:ZNJSLVXD 2405685:BTCH5KTC
Keywords: Google Scholar/ teacher "professional development" AND refugees AND technology; RER theme_pedagogies and modalities

Factors affecting teachers’ continuation of technology use in teaching - Kafyulilo, Ayoub; Fisser, Petra; Voogt, Joke (Education and Information Technologies, 2016)
This study was conducted to investigate the continuation of technology use in science and mathematics teaching of the teachers who attended a professional development program between 2010 and 2012. Continuation of technology use was hypothesized to be affected by the professional development program and by personal, institutional, and technological factors. Twelve teachers and three school leaders participated in the study. Data was collected through interviews. Findings showed that the continuation of technology use differed for the teachers involved in the professional development program. While all teachers reported to have gained knowledge and skills through the professional development program and were positive about technology use in education, only some teachers continued the use of technology. The data revealed that despite the challenges that all teachers in the sample encountered when using technology in their teaching (such as large classrooms, problems with electricity supply, lack of time and lack of technology tools), the encouragement of school management was a critical factor in teachers’ continuation of technology use. Implications of the findings are discussed.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-015-9398-0 2339240:GMCWDGDM 2405685:LCDEJKQW

Improving procedural and conceptual mathematics outcomes: evidence from a randomised controlled trial in Kenya - Piper, Benjamin; Ralaingita, Wendi; Akach, Linda; King, Simon (Journal of Development Effectiveness, 2016)
To improve learning outcomes, an intervention in Kenya called the Primary Math and Reading (PRIMR) Initiative provided pupil learning materials, teachers’ guides and modest teacher professional development in mathematics. This paper presents the causal impact of PRIMR’s mathematics intervention on pupil achievement indices for procedural and conceptual numeracy, using a diﬀerences-in-diﬀerences analytic strategy. The mathematics intervention produced modest, statistically signiﬁcant results: generally similar results for males and females, a larger impact in grade 2 than grade 1, a larger impact in nongovernment schools than public schools, and smaller outcomes in mathematics than for English or Kiswahili. These ﬁndings have relevant policy implications in Kenya given an impending national mathematics programme.
shortDOI: 10/gftrqc KerkoCite.ItemAlsoKnownAs: 10.1080/19439342.2016.1149502 10/gftrqc 2339240:9H3B7D35 2339240:U483WVFF 2405685:J47PXP4U 2405685:SUWZCIEL
Keywords: Kenya; Numeracy; elementary school; instruction; international education; mathematics

Examining factors affecting beginning teachers’ transfer of learning of ICT-enhanced learning activities in their teaching practice - Agyei, Douglas D.; Voogt, Joke (Australasian Journal of Educational Technology, 2014)
This study examined 100 beginning teachers’ transfer of learning when utilising Information Communication Technology-enhanced activity-based learning activities. The beginning teachers had participated in a professional development program that was characterised by ‘learning technology by collaborative design’ in their final year of their pre-service preparation program. Transfer of learning was proposed as characteristic of (i) the professional development program,(ii) beginning teachers and (iii) school environment. Beginning teachers held positive views about active learning and ICT use developed during the professional development program, which seemed the strongest predictor in transfer of their learning. The study also showed that a significant amount of explained differences in the level of transfer of ICT-enhanced activity-based learning innovation could be attributed to range of factors across individual beginning teachers and school environment characteristics. Implications of these findings are discussed.
Number: 1 KerkoCite.ItemAlsoKnownAs: 10.14742/ajet.499 2339240:5D3VSVHR 2405685:EBNRF3XR 2405685:KB9RS4H4 2534378:L2FKFKGZ 2534378:SI3VKRQI
Keywords: __:import:02; __:match:final; __:matched; __:study_id:2425905; __finaldtb

An investigation of appropriate new technologies to support interactive teaching in Zambian schools (ANTSIT). A joint report from Aptivate and the Centre for Commonwealth Education (University of Cambridge). Final Report to DfID. - Haßler, Björn; Hennessy, S.; Lord, T.; Cross, A.; Jackson, A.; Simpson, M. (Aptivate and University of Cambridge, 2011)
0007 EdTechHub.Source: 2129771:ZATDIRKP EdTechHub.Source: 2129771:ZATDIRKP KerkoCite.ItemAlsoKnownAs: 2129771:ZATDIRKP 2405685:3TABTBW7
Keywords: Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
shortDOI: 10/ghgngb KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1196830 10.5281/zenodo.1219919 10/ghgnf9 10/ghgngb 1867969:MS4YEFUV 2129771:3HPEHK45 2339240:6UEQFTXM 2339240:HYX3RTJZ 2339240:WNVALD7D 2405685:A8G2S2ZT 2405685:FUKJ5SE8 2405685:IGGQMIXI 2405685:PWCIYQJM
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

How to Improve Teaching Practice? Experimental Comparison of Centralized Training and In-classroom Coaching - Cilliers, Jacobus; Fleisch, Brahm; Prinsloo, Cas; Taylor, Stephen (Research on Improving Systems of Education (RISE), 2018)
We experimentally compare two modes of in-service professional development for South African public primary school teachers. In both programs teachers received the same learning material and daily lesson plans, aligned to the ofﬁcial literacy curriculum. Pupils exposed to two years of the program improved their reading proﬁciency by 0.12 standard deviations if their teachers received centralized Training, compared to 0.24 if their teachers received in-class Coaching. Classroom observations reveal that teachers were more likely to split pupils into smaller reading groups, which enabled individualized attention and more opportunities to practice reading. Results vary by class size and baseline pupil reading proﬁciency.
shortDOI: 10/ghgnff KerkoCite.ItemAlsoKnownAs: 10.35489/BSG-RISE-WP_2018/024 10/ghgnff 2405685:WYIY3SSM
Keywords: C: South Africa

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
previousshortDOI: 10/ghgnfm previousDOI: 10.5281/zenodo.3523935 EdTechHub.Copy: 2129771:NB3WMPDJ shortDOI: 10/ghgnfm KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523935 10.53832/edtechhub.0016 10/ghgnfm 2129771:NB3WMPDJ 2339240:B5AIHWDZ 2405685:2GC35JLV 2405685:LSEETV6K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

MOOC adaptation and translation to improve equity in participation - Wolfenden, Freda; Cross, Simon; Henry, Fiona (Journal of Learning for Development, 2017)
There is an urgent need to improve elementary and secondary school classroom practices across India and the scale of this challenge is argued to demand new approaches to teacher professional learning. Massive Open Online Courses (MOOCs) represent one such approach and one that, in the context of this study, is considered to provide a means by which to transcend traditional training processes and disrupt conventional pedagogic practices. This paper offers a critical review of a large-scale MOOC deployed in English, and then in Hindi, to support targeted sustainable capacity building within an education development initiative (TESS-India) across seven states in India. The study draws on multiple sources of participant data to identify and examine features, which stimulated a buzz around the MOOCs, leading to over 40,000 registrations and a completion rate of approximately 50% for each of the two MOOCs.
Publisher: Commonwealth of Learning KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v4i2.209 2339240:5AVZ6N24 2405685:B6HCB8RM 2405685:CPXFIVAY 2405685:NV7NW6T5 2534378:M4U3QCYL 2534378:SPVQ8ST8 2534378:VD62UHJM 2534378:WXPHBJ7Y
Keywords: Access to Computers; Access to Education; Attitude Measures; ERIC; Current Index to Journals in Education (CIJE); Educational Technology; Equal Education; Foreign Countries; Higher Education; India; International Programs; Large Group Instruction; Online Courses; Partnerships in Education; Postsecondary Education; Pretests Posttests; Program Implementation; Questionnaires; Surveys; Teacher Education Programs; Teacher Educators; Technology Uses in Education; United Kingdom; __:import:01; __:match:final; __:matched; __:study_id:2096064; ___working_potential_duplicate; __finaldtb; ⛔ No DOI found

Effective teacher professional development - Darling-Hammond, Linda; Hyler, Maria E.; Gardner, Madelyn (Learning Policy Institute, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:U3TNTQVM 2405685:CHPTP257

Factors influencing teachers’ level of participation in online communities - Khalid, Fariza; Joyes, Gordon; Ellison, Linda; Daud, Md Yusoff (International Education Studies, 2014)
The use of an online learning community is one possible approach to teachers’ professional development that can enhance the opportunity for collaboration. Discussions in online learning communities not only allow community members to share resources, ideas and expertise, but also contribute to the fulfilment of teachers’ needs in terms of continuous learning and professional development. This paper reports the findings of a study that aimed to explore the factors that influence the way teachers behave in online communities. The research participants were 16 teachers from five secondary schools in Malaysia who were teaching English, science and mathematics. These teachers were involved in online learning communities via blogs in which they exchanged stories and experiences related to their teaching and learning activities. Data were generated through one-to-one interviews. Based on thematic analysis, the overall findings indicate that teachers’ levels of participation in their online learning communities were largely influenced by cultural issues. Other factors that impacted upon their engagement were time, enforcement by school administrators and their need for an online community.
Original URL: http://www.ccsenet.org/journal/index.php/ies/article/view/43598 KerkoCite.ItemAlsoKnownAs: 10.5539/ies.v7n13p23 2339240:CV52XQZG 2405685:2FFJVPVH 2405685:VMFM6CSP 2534378:EDAZA3Z4 2534378:ZN92H5YX
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2096356; __finaldtb

Teacher reflections and praxis: a case study of Indian teachers of English as a foreign language - Makarani, Sakilahmed A. R. (University of Hawai'i at Mānoa, 2012)
This case study engaged Gujarati English as Foreign Language (EFL) teachers in video-based reflection with the goal of increasing their reflective abilities and uncovering their understandings about reflective teaching practices in the Indian pedagogical and cultural context. The study aimed to explore, and gain a deeper understanding of how structural, institutional, and social dynamics of the larger socio-political cultural context of India affected the classroom teachers' thinking and their teaching practices. It was hoped that not only would the Gujarati teachers demonstrate an ability to reflect on their practice, but that they would also engage in a critical examination of the factors that impacted their context. The computer-based qualitative data analysis software, Atlas.ti, was used to analyze data using a grounded theoretical approach. The findings indicated that participants successfully engaged in reflection about their teaching using video as the tool for their professional development. Initially teacher participants had mixed feelings about recording and watching videos of their classroom instruction; however, teacher participants later enjoyed the experience, explicitly stating that such reflection helped them. The study also revealed that teacher participants perceived parental, social, institutional, and economic factors as influences on their students' learning, however these were simply identified as problems or conditions without any type of deeper critical analysis. Further, it was found that the teachers did not reach a critical level of reflection, nor did they consider taking action to address fundamental contextual issues. While this study showed that teacher reflection using digital video recordings of classroom practice can be a productive approach to meaningful teacher reflection in India, the study also demonstrated that teachers need specific exposure to deeper critical pedagogical thinking to go beyond simply identifying or blaming the social or economic issues embedded in their context. The study concludes with recommendations on how to reach critical teacher reflection. It is hoped that this case study will add to the growing body of research literature related to teacher self-reflection as a means to improving teaching practice and preparing teachers to take on social challenges in the Indian context. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]
ISBN: 9781303035289 Pages: 173 Publication Title: ProQuest LLC Loc in Archive 1697502591; ED554753 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/1697502591?accountid=9851 KerkoCite.ItemAlsoKnownAs: 2339240:NZ8XTVSM 2339240:ZZQBKRNI 2405685:FMI8USWB 2405685:V48XT6S6 2534378:C6KXYQA7 2534378:IW3DL8F8
Keywords: Case Studies; Computer Software; Cultural Context; ERIC; Resources in Education (RIE); Economic Factors; English (Second Language); Foreign Countries; Grounded Theory; India; Indians; Language Teachers; Qualitative Research; Reflective Teaching; Second Language Instruction; Second Language Learning; Social Influences; Teacher Attitudes; Teaching Methods; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096525; __finaldtb

Short message service (SMS)–based remote support and teacher retention of training gains in Malawi - Slade, Timothy S.; Kipp, Scott; Cummings, Stirling; Nyirongo, Kondwani (Cultivating dynamic educators: case studies in teacher behavior change in Africa and Asia, 2018)
This book responds to growing recognition by international education professionals, policy makers, and funding partners of the need for qualified teachers and interest in the subject of teacher professional development (also referred to as "teacher behavior change"). The book responds to important questions that are fundamental to improving teaching quality by influencing teaching practice. These questions include: How do we provide high-quality training at scale? How do we ensure that training transfers to change in practice? What methods are most cost-effective? How do we know what works? The book includes case studies describing different approaches to teacher behavior change and illustrates how specific implementation choices were made for each context. Individual chapters document lessons learned as well as methodologies used for discerning lessons. The key conclusion is that no single effort is enough on its own; teacher behavior change requires a system-wide view and concerted, coordinated inputs from a range of stakeholders. This book contains the following chapters: (1) Understanding and Influencing Teacher Behavior Change: Editorial Introduction (Sarah Pouezevara); (2) Changing Teacher Educators' Conceptions and Practices Around Literacy Instruction: Lessons from Teacher Educators' Professional Development Experiences in Ethiopia (Dawit Mekonnen, Marion Fesmire, Adrienne Barnes, Stephen Backman, and Flavia Ramos-Mattoussi); (3) School Leadership and Early Grade Reading: Examining the Evidence in Zambia (Mitchell Rakusin and Guy Bostock); (4) Making Sense of Teacher In-Service Training in the Philippines (Nancy Clark-Chiarelli and Bonita Cabiles); (5) Short Message Service (SMS)-Based Remote Support and Teacher Retention of Training Gains in Malawi (Timothy S. Slade, Scott Kipp, Stirling Cummings, and Kondwani Nyirongo); (6) Relationships Between Coach Support and Teachers' Adoption of New Instructional Practices: Findings from the Nigeria Reading and Access Research Activity (RARA) (Karon Harden, Alison Pflepsen, and Simon King); (7) Using Activity Theory to Understand Teacher Peer Learning in Indonesia (Sarah Pouezevara, Feiny Sentosa, and Tifa Asrianti); (8) Teacher Motivation and Behavior Change: Results of the Teacher Motivation Diagnostic Tool in Northern India (Molly Hamm-RodrÃguez, Emily Richardson, and Jarret Guajardo); and (9) Once More Up the Mountain: The Promise of High-Quality Teaching Depends on Behavior Change (Lee E. Nordstrum). Contains a section about the contributors and an index. (Individual chapters contain references.) [Erin Newton compiled this volume.]
Publisher: ERIC KerkoCite.ItemAlsoKnownAs: 2339240:2M2HXSJN 2405685:SNDDADWB 2405685:SNTV94NA 2534378:7FFHYISA 2534378:ASX6DAFV 2534378:WH9M9DZM
Keywords: __:import:02; __:match:final; __:matched; __:study_id:3123693; __finaldtb; ⛔ No DOI found

EDUsummIT 2011 report from TWG3: teacher professional development - Twining, Peter; Albion, Peter; Knezek, Don (UNESCO, 2011)
KerkoCite.ItemAlsoKnownAs: 2339240:E272UVBQ 2405685:PUNUJQ3I 2405685:TT2AEKHE 2534378:T48EQGLU

Malawi Teacher Professional Development Support Program: Baseline Report - USAID (2011)
KerkoCite.ItemAlsoKnownAs: 2339240:UVTM7PAJ 2405685:ECQAAQQY

Introducing ICT into Teacher-Training Programs: Problems in Bangladesh - Khan, Shahadat Hossain; Hasan, Mahbub (Journal of Education and Practice, 2013)
Information and Communication Technology can offer more adaptable and efficient ways of teacher training for improvement of quality of professional development programs. But the use of ICT into teacher training usually faces certain obstacles. In this paper, we identified different barriers of introducing ICT into teacher training model (this model had been discussed by the authors in a separate paper, titled as “A model for integrating ICT into teacher training programs in Bangladesh based on TPCK) in Bangladesh, a developing country. We then described the strategies to overcome these problems for improving the current status of ICT integration into teacher training. Finally, we concluded with emerging research issues and offered pertinent recommendation with respect to ICT integration into teacher training program for improving quality of teaching in Bangladesh.
KerkoCite.ItemAlsoKnownAs: 2339240:JV86HLB6 2405685:L7TKD9JC
Keywords: ⛔ No DOI found

What professional development makes the most difference to teachers? - Walter, Catherine; Briggs, Jessica (University of Oxford Department of Education, 2012)
KerkoCite.ItemAlsoKnownAs: 2339240:6FD437X4 2405685:RS5JRWCB

National Framework for Continuous Professional Development for Practicing Teachers - Ministry of Education, Science and Technology (United Republic of Tanzania, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:F5D7RDCT 2405685:GFCJSMIU 2405685:SFYUBD4B
Keywords: _B:important; _G:important; _G:reviewed; _Tanzania; _final_bib; _important

Teacher factors influencing classroom use of ICT in sub-Saharan Africa - Hennessy, Sara; Harrison, David; Wamakote, Leonard (Itupale Online Journal of African Studies, 2010)
This paper synthesises the research literature on teachers‟ use of Information and Communication Technology (ICT) in primary and secondary schools in sub-Saharan Africa, with a particular emphasis on improving the quality of subject teaching and learning. We focus on the internal factors of influence on teachers‟ use, or lack of use, of technology in the classroom. Our discussion attends to perceptions and beliefs about ICT and their motivating effects, technological literacy and confidence levels, pedagogical expertise related to technology use, and the role of teacher education. These factors are discussed in light of significant infrastructure and other external issues. We conclude by drawing out a number of pedagogical implications for initial teacher education and professional development to bring schooling within developing contexts into the 21 st century.
EdTechHub.Copy: 2129771:J94BQM7C KerkoCite.ItemAlsoKnownAs: 2129771:J94BQM7C 2339240:957DANTW 2405685:RXIW5GY7
Keywords: Schools; Secondary; Scientific literature; ⛔ No DOI found

Where it's needed the most: Quality professional development for all teachers - Burns, M.; Lawrie, J. (Inter-Agency Network for Education in Emergencies, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:V4SP3RKS 2405685:GXPBN6L8 2405685:WZCNCBLM 2405685:XJ326CKU

Coherence and the positioning of teachers in professional development programs. A systematic review - Lindvall, Jannika; Ryve, Andreas (Educational Research Review, 2019)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.edurev.2019.03.005 2405685:UXEQSP6H 2534378:R7UFM8RT
Keywords: Important; Read

Coherence and the positioning of teachers in professional development programs. A systematic review - Lindvall, Jannika; Ryve, Andreas (Educational Research Review, 2019)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.edurev.2019.03.005 2339240:T6FJICU7 2405685:NECFNMUF
Keywords: Important; Read

Coherence and the positioning of teachers in professional development programs. A systematic review - Lindvall, Jannika; Ryve, Andreas (Educational Research Review, 2019)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.edurev.2019.03.005 2339240:T6FJICU7 2405685:NECFNMUF
Keywords: Important; Read

A Professional Development Program for the Mother Tongue-Based Teacher: Addressing Teacher Perceptions and Attitudes Towards MTBMLE - Stone, Rebecca J Paulson (University of Massachusetts Amherst, 2012)
KerkoCite.ItemAlsoKnownAs: 2405685:9CAEQJCZ 4042040:KDCL2XKB

Effects of an Early Literacy Professional Development Intervention on Head Start Teachers and Children - Powell, Douglas; Diamond, Karen; Burchinal, Margaret (Journal of Educational Psychology, 2010)
shortDOI: 10/cgt5m7 KerkoCite.ItemAlsoKnownAs: 10.1037/a0017763 10/cgt5m7 2405685:BYGJSXSA

WhatsApp: Creating a virtual teacher community for supporting and monitoring after a professional development programme - Moodley, Maglin (South African Journal of Education, 2019)
KerkoCite.ItemAlsoKnownAs: 10.15700/saje.v39n2a1323 2339240:R7L9J4C3 2405685:HSIJJWM4

Teachers in Tatweer Primary Schools in Saudi Arabia and Interactive White Boards: Towards a Professional Development Model - Alghamdi, Azzah Hamed (Durham University, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:EC9JYRN8 2405685:8EYRA9BQ

The effects of continuing professional development (CPD) though SPRINT on teacher classroom practices and student learning outcomes. In Collaboration toward Greater Autonomy in Educational Development - Mubanga, R (2012)
KerkoCite.ItemAlsoKnownAs: 2405685:NALKEFXU

The Use of Video in Teacher Professional Development Design, Implementation and Impact Evaluation of an Innovative In-service Course for Mathematics Teachers in Indonesia - Ragatz, Andrew B.; Sugiarti, Susie; Iskandar, Susiana (World Bank, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:YYLBDFVL 2405685:8WVE9V2U

Access, use and perceptions of teachers and students towards mobile phones as a tool for teaching and learning in Tanzania - Kafyulilo, Ayoub (Education and Information Technologies, 2014)
This study explored the access, use and perceptions of teachers and students towards mobile phones as a tool for facilitating teaching and learning beyond the classroom walls. A total of 29 pre-service teachers and four college instructors from Dar es salaam University College of Education (DUCE) as well as 12 in-service teachers and 40 students from Kibasila secondary school in Tanzania, participated in the study. Data were collected by using pre-service teachers’ questionnaire, students’ questionnaire, and the instructors’, and in-service teachers’ interviews. Findings showed that all in-service teachers, college instructors and pre-service teachers had mobile phones. Also 60 % of school students owned mobile phones, or had access to mobile phones. Students, pre-service teachers and college instructors were in favour of the use of mobile phones for learning, but the majority of in-service teachers were against it. Since mobile phones are the most available technological tools in schools, this study, recommend a professional development programme for in-service teachers to help them develop a positive attitude towards mobile phones use in teaching and learning.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-012-9207-y 2339240:XSTQQSQK 2405685:SP36ZFFU

The Impact of Teachers Professional Development in Video Technology on Mathematics and English Learning of Preschoolers in a Rural Primary School in Pakistan - Ikram, Hamid (International Journal for Digital Society, 2015)
Learning media technologies are common and affordable tools in preschools for teaching and learning purposes. Unfortunately, many young children from low socio-economic communities do not have challenging and stimulating learning environment as compared to their advantaged peers.
KerkoCite.ItemAlsoKnownAs: 10.20533/ijds.2040.2570.2015.0131 2339240:UGARGA2L 2405685:Z3SIF5WJ

Moving towards more participatory practice with Open Educational Resources (OER): TESS-India Academic Review - Wolfenden, Freda; Adinolfi, Lina; Cross, Simon; Lee, Clare; Paranjpe, Sandhya; Safford, Kimberly (The Open University, 2017)
The purpose of this academic review of TESS-India activity in three states (Bihar, Madhya Pradesh and Odisha) was to seek evidence for change brought about by TESS-India in teacher education in each of these states. The findings offer informed guidance on future trajectories for TESS-India activity and support discussions with key stakeholders in each of these states. The overarching goal of TESS-India is to support delivery of quality pedagogic change in teacher education and school classrooms. TESS-India activity is designed to meet identified professional development needs of teachers and teacher educators in each state. Thus it takes a slightly different form in each state, appropriate to local priorities and conditions. The Review focus was similarly differentiated in each state to align to TESS-India activity in that state. The review field work was carried out by academics from the Open University UK and the Head Academic, TESS-India Country Office, between 30 January and 4 February 2017. It adopted an essentially qualitative approach to understand educators’ (trainee teachers, teachers, local teacher educators and DIET faculty) experiences with the TESS-India resources and the influence of this engagement on their pedagogic practice. Data was generated from multiple sources including analysis of key documentation, semi-structured interviews with teachers, teacher educators and policy makers, and classroom observation. Teachers, teacher educators and SRG members were sampled at different locations within each state. The focus of TESS-India activity to date has been to strengthen the existing government (state) educational system at the elementary stage - SCERT, SSA, DIETS, DEO, DPC (SSA), BEO, BRP, BRC, CRCC, HT, Teacher, Child – in alignment with national policies, frameworks and the RTE Act. The project aims at supplementing and complementing GoI and State specific efforts and activities. Although TESS-India has produced original Open Educational Resources (OER) to support educators working in the secondary stage, as yet there is very little evidence of sustained TESS-India activity with this phase of schooling or with the TESS-India School Leader OER. The review findings are therefore focussed on activity at the elementary stage and are reported at different levels of the system in line with the TESS-India theory of change. The report found that use of TESS-India OER is contributing to quality change in classrooms with students and trainee teachers. • SRG members met by the review team were using the TESS-India OER and described how this use was prompting them to experiment with more interactive and participatory practices. • Teachers observed and / or interviewed by the review team were drawing on TESS-India OER to inform their lesson planning and subsequent teaching. Evidence seen by the review team (learning journals and learning plans) indicates that the practices being developed by these teachers are shared by other teachers in the cohort of teachers participating in TESS-India focus district activity. However the innovation in practice and transformation in pedagogy promised by TESS-India OER is still in the early stages and the evidence is highly emergent. But, critically, through engagement with the MOOC and other TESS-India learning resources, policy makers and lead teacher educators (for example SCERT Directors) are changing their thinking about teacher professional development, moving away from cascade models to a focus on continuous professional development and learning of teachers in their classrooms with support from teacher educators/ experts, either virtually or face-to face.
KerkoCite.ItemAlsoKnownAs: 2339240:AHU462BA 2339240:YXLKRLBI 2405685:34CVA9XF 2405685:GFP5DZJS 2405685:J2QYZC4N 2405685:PNQ2QI9P 2405685:Y9UA4ULS 2534378:H6UD8JMP 2534378:N7WIEWKK 2534378:RF4RFHAF
Keywords: C: India; __:import:01; __:match:final; __:matched; __:study_id:2457359; __finaldtb

A Comparative Study of Online and Directly Selected Secondary School Teachers Regarding Teaching Proficiency and Classroom Management in Kohat Division, Pakistan - Suleman, Qaiser; Hussain, Ishtiaq (International Journal of Learning and Development, 2013)
Secondary school teachers occupy the most critical and crucial position in the entire education system (Suleman, et al, 2011a). The purpose of the study was to compare the performance of online and directly selected secondary school teachers regarding teaching proficiency and classroom Management. All the students at secondary school level in Kohat Division, Khyber Pakhtunkhwa (Pakistan) constituted the population of the study. Only 600 students studying at secondary school level in Kohat Division were selected as sample randomly. The study was delimited to only male students at secondary school level. The study was descriptive type and questionnaire was used as research instrument. Data was collected through personal visits. After the collection of data, it was organized, tabulated, analyzed and interpreted. The statistical tools i.e. means, standard deviation and differences of means were computed for each variable. Significance of difference between the mean values of the responses of students about online and directlly selected secondary school teachers were tested at 0.05 levels by applying t-test. After statisitcal analysis of the data, the researchers conclduded that the overall performance of the directly selected secondary school teachers was better and satisfactory. They were found to have the knowledge of teaching methods and the ability to control classroom disruptive behaviour. Conversely, the overall performance of the online selected secondary school teachers was poor and unsatisfactory. They have no knowledge of teaching methodologies and subject mastery. They were found unable to manage classroom disruptive behaviour and other related activities. Based on findings, it was strongly recommended that a special professional training programme should be arranged to the existing online selected SSTs in teaching methodologies and classroom management to equip them with the modern teaching methods and techniques of managing classroom behaviour so that they become able to perform their duties effectively.
Number: 3 KerkoCite.ItemAlsoKnownAs: 10.5296/ijld.v3i3.4130 2339240:MKBAFBWM 2405685:856AQDD2

Understanding factors affecting primary school teachers’ use of ICT for student-centered education in Mongolia - Li, Shengru; Yamaguchi, Shinobu; Takada, Jun-ichi (2018)
The past two decades witnessed continuous uptake of ICT in education, and the importance of teachers’ beliefs for adopting ICT in education was revealed in the context of educational change. In recent years, the Mongolian educational system has placed more emphasis on student-centered education and the use of ICT in teaching and learning. Teacher training has become a local responsibility under the Education Master Plan (Government of Mongolia, 2006), New Education Standard and Core Curriculum which focus on the introduction of ICT into education and the implementation of student-centered education (Asian Development Bank, 2008; Ministry of Culture Education and Science, 2014). Despite the growing interest in using ICT for student-centered education, a limited number of studies exist in Mongolia to understand primary school teachers’ perception on use of ICT for student-centered education. This study aims to understand the factors affecting teachers’ perceptions on use of ICT for student-centered education. Based on Fullan’s educational change theory, the analysis through multiple linear regression and focus group discussion was conducted on 838 primary school teachers in Mongolia which found that teacher’s professional competency and perceived benefits on use of ICT are significant factors affecting teachers’ perceptions on use of ICT tool for student-centered education. Furthermore, teacher’s professional competency, perceived benefits on use of ICT and teacher cooperation are affecting teachers’ perceptions on use of digital contents for student-centered education.
KerkoCite.ItemAlsoKnownAs: 2339240:J6FMCEMP 2405685:UJYVC9Z6
Keywords: ⛔ No DOI found

Use ICT to provide access to content, professional development and professional learning communities (Recommendation 7) - Lawrie, J.; Hennessy, S.; Haßler, Björn; Phalachandra (Where it's needed most: quality professional development for all teachers, 2015)
EdTechHub.Source: 2129771:KQGAREE9 EdTechHub.Source: 2129771:KQGAREE9 Book DOI: 10.13140/RG.2.1.2044.3761 KerkoCite.ItemAlsoKnownAs: 2129771:KQGAREE9 2339240:CBYR6TWI 2405685:8Q6BDGWE 2405685:PKLI25VA 2405685:ZIXCZS28 2534378:DMKTGVXQ
Keywords: C:Fragile contexts; docs.opendeved.net

Supporting Change in Literacy Instruction in Malawi - Sailors, Misty; Hoffman, James V.; Pearson, P. David; McClung, Nicola; Shin, Jaran; Phiri, Liveness Mwale; Saka, Tionge (Reading Research Quarterly, 2014)
In this study, we examined the effectiveness of an innovative approach to literacy instruction in Malawi on teachers' perceptions, attitudes, and instructional practices. Two groups participated in the study: Treatment teachers received complementary teaching and learning materials, workshops, and directive coaching, and control teachers received no intervention. After this five-month intervention, treatment teachers were significantly more comfortable with their languages of instruction and were more positive about their teaching ability, beliefs about the learning materials in their classroom, and beliefs about the culture of reading in their communities than control teachers were. There were no significant differences between groups when we analyzed their teaching practices or the engagement of their students. The coaching model proved to be associated with changes in teachers' beliefs and perceptions on many of our variables. These findings suggest that the program under examination was successful in promoting the conditions for success (teacher beliefs and perceptions). Further, the findings suggest that the implementation of coaching was an important source of support in implementing changes.
shortDOI: 10/ggvk3t KerkoCite.ItemAlsoKnownAs: 10.1002/rrq.70 10/ggvk3t 2339240:FPRQN6RV 2405685:IVTVDACJ
Keywords: Adult; C:Malawi; Childhood; Coaching; Decoding; Discussion; Early childhood; English as a second language; English for speakers of other languages; English language learners; English learners; Experimental; Fairy tales; Family literacy; Home language; Home-school connections; In-service; Instructional models; Language learners; Literature; Literature-based instruction; Oral language; Parental involvement; Phonics; Program evaluation; Reading strategies; Research methodology; School based; Sight words; Sociocultural; Socioeconomic factors; Strategies; Supplementary resources; Teacher education; Textbooks; and materials; folk tales; methods; phonemic awareness; phonological awareness; professional development; quasi-experimental; word recognition

Five starting points on innovation for the EdTech Hub – The EdTech Hub - Simpson, Lea (EdTech Hub, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:XCJNWSVR XCJNWSVR
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Using technology for enhancing teaching and learning in Bangladesh: challenges and consequences - Mahruf, C.; Shohel, M.; Kirkwood, Adrian (Learning, Media and Technology, 2012)
Extra URL: https://www.tandfonline.com/doi/full/10.1080/17439884.2012.671177 KerkoCite.ItemAlsoKnownAs: 10.1080/17439884.2012.671177 10/gf5f6w 2339240:95DVIPCS 2339240:IVHSIR7Q 2405685:NXQEUUZM 2534378:CSPF7NEB 2534378:MLD48MMR 2534378:UQYRQ249
Keywords: BANGLADESH; Bangladesh; COMPUTER assisted instruction; COMPUTERS in education; CONTINUING education; DEVELOPING countries; EDUCATIONAL technology; INFORMATION technology; PROFESSIONAL education; SECONDARY school teachers; TEACHER development; TEACHERS – In-service training; _Source:Intuitive; _THEME: Curriculum and resources; _THEME: Open systems; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2096535; __finaldtb; teachers’ professional development; teaching and learning; technology; technology-poor contexts; the

Survey of the Use of Assistive Technology in Schools in Nigeria - Ajuwon, Paul M.; Chitiyo, George (Journal of the International Association of Special Education, 2015)
In this study, the researchers explored the state of the use of assistive technology (AT) in Nigeria through a survey of 165 special educators. The underlying structure of the respondents' perceptions, and their challenges and barriers to the use of AT, were examined. Among other findings, the largest proportion of students using AT are those with deafness or hearing impairment (53.3%), followed by those with a learning disability (40%). Training in the use of AT lags behind, with most professionals having received little or no training in the use of AT. The lack of appropriate AT devices and services in classrooms, and irregular electricity to operate available devices, were frequently cited as the biggest challenges regarding AT. Correlations between students' conditions and factors of teachers' perceptions suggested the need to make AT available for students with certain conditions, as well as the need for effective training for teachers.
KerkoCite.ItemAlsoKnownAs: 2339240:2B5LKGDA 2405685:XS664IV7
Keywords: Access to Computers; Assistive Technology; Barriers; Computer Uses in Education; Deafness; Disabilities; Educational Technology; Energy; Faculty Development; Foreign Countries; Hearing Impairments; Learning Disabilities; Likert Scales; Special Education Teachers; Statistical Analysis; Teacher Competencies; Teacher Surveys; Technological Literacy; Training; ⛔ No DOI found

Using instructional video to improve awareness of scientific approach in science classroom - Susantini, Endang; Faizah, Ulfi; Yonata, Bertha; Kurniasari, Ika; Suryanti (Asia-Pacific Forum on Science Learning and Teaching, 2018)
Instructional videos have been developed to engage pre-service teachers to learn how to teach scientific approach in science classroom. This study aimed to improve preservice teachers' awareness of scientific approach in science classroom through instructional video along with their responses. Thirty two pre-service science teachers from Universitas Negeri Surabaya, Surabaya, Indonesia, participated in this study and observed two different instructional videos using video-analysis worksheet supplemented by the supervisor. In response to the instructional video, results showed that pre-service teachers noticed well about application of scientific approach in inquiry-based teaching and cooperative learning models. Pre-service teachers also showed positive views about the instructional videos and became a reflection for their own future teaching actions and practices. Supplementation of the video-analysis worksheet during the implementation and peer-discussion among preservice teachers can be used to improve pre-service teachers' awareness as well as to provide clear exemplary about how to integrate scientific approach at each phase of inquiry-based teaching and cooperative learning models. This study implies that the present instructional videos and followed-up video-analysis task are adequate to facilitate pre-service teachers to understand what to do in actual classroom in terms of applying scientific approach as envisioned by Indonesia curriculum reform.
Publisher: Hong Kong Institute of Education, 10 Lo Ping Road, Tai Po, New Territories, Hong Kong KerkoCite.ItemAlsoKnownAs: 2339240:BN9QC37H 2339240:LBY74V36 2405685:DVSNFSAI 2405685:S42A5QRW 2534378:JX3N56UR 2534378:JZI7NCMR 2534378:WYRLILRV
Keywords: Active Learning; Biology; Chemistry; Classrooms; Cooperative Learning; Cooperative learning; Curricula; ERIC; Current Index to Journals in Education (CIJE); Educational technology; Foreign Countries; Higher Education; Hypotheses; Indonesia; Inquiry; Inquiry method; Instructional Material Evaluation; Mathematics; Models; Pedagogy; Preservice Teacher Education; Preservice Teachers; Professional development; Science Instruction; Science Teachers; Science education; Sciences: Comprehensive Works; Scientific Methodology; Student Attitudes; Students; Teacher education; Teaching Methods; Teaching methods; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2097317; __finaldtb; ⚠️ Invalid DOI; ⛔ No DOI found

Context and Appropriate Technology: The Unavoidable Partnership - Onguko, Brown (Proceedings of the European Conference on e-Government, ECEG, 2012)
Teachers in rural parts of Kenya lack opportunities for professional development (PD). In addition, the teachers have no access to eLearning opportunities like their colleagues in urban parts. Among the factors that do not favor Kenyan rural teachers’ access to PD through eLearning include: lack of access to relevant technologies and lack of electricity. This paper shares research findings on provision of teachers’ PD through a blended learning approach, utilizing appropriate technologies in a rural school in western Kenya. Ten teachers and two Professional Development Teachers (PDTs) participated in this research. In the study, teachers’ needs assessment was done, to inform the instructional design on the topic: How to teach a large class of mixed ability students. The PD was implemented by engaging teachers in a variety of activities including: pairs of teachers collaboratively using a tablet to access self-study content; teachers studying through multimedia content; teachers planning and delivering lessons using activity-based learning and cooperative learning approaches; and PDTs and teachers participating in fortnightly face-to-face meetings. The findings of the study suggest that teaching practices of rural educators can be improved working with local experts to create locally-relevant content for needs-based PD, implemented in a blended learning approach while providing technology stewardship. Teachers accessed and studied through offline content; planned for and implemented cooperative learning and activity-based learning in lessons, using locally available materials; engaged in reflective conversations on successes and challenges; and spontaneously engaged in very lively professional dialogues. While teachers appreciated that it took long to prepare for active learning lessons, it was less strenuous to implement the lessons, because the students took responsibility for their own learning.
KerkoCite.ItemAlsoKnownAs: 2339240:24H28YGJ 2339240:ISIT39J6 2405685:5KI53BLU 2405685:W7KJBF6N 2405685:X3EGT59M 2405685:ZHM4CF5K 2534378:7IHB745E 2534378:SU4VP6FM
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2096499; __finaldtb; ⛔ No DOI found

Mobile solution for better reading instruction in rural Africa - Ojanen, Emma; Jere-Folotiya, Jacqueline; Yalukanda, Christopher; Sampa, Francis; Nshimbi, Chomba; Katongo, Maggie; Choopa, Mapenzi; Lyytinen, Heikki (2015 IST-Africa Conference, 2015)
GraphoGame Teacher Training Service is a mobile-based solution for providing teachers with scientifically validated pedagogical training in literacy instruction. In many African countries teachers currently have insufficient knowledge to teach literacy in local languages and learning materials are scarce, especially for children with learning difficulties. As part of the GraphoWorld network, CAPOLSA/University of Zambia is developing new mobile-based method for providing in-service training for teachers in literacy instruction and assisting children with learning difficulties. GraphoGame Teacher Training Service was piloted in October 2014 in rural Zambia. An orientative workshop was given to 24 teachers who learned about literacy instruction methodology and then organized a GraphoGame intervention to randomly selected 2nd grade children either at home or in a school environment. Parents of the children in the home intervention group were also encouraged to play GraphoGame. GraphoGame learning analytics shows that both the children and their parents improved their word reading skills. Children who played GraphoGame performed better than their non-playing classmates in the EGRA letter-sound knowledge test at the end of the intervention. Teachers, parents and children were all motivated to use ICT-based literacy learning tools and their literacy skills levels show high demand for support services for literacy instruction.
ISSN: null shortDOI: 10/gf62qw KerkoCite.ItemAlsoKnownAs: 10.1109/istafrica.2015.7190559 10/gf62qw 2339240:FYCG4SIF 2405685:HTPQU2DR
Keywords: Africa; African country teachers; CAPOLSA/University of Zambia; Conferences; EGRA letter-sound knowledge test; Electronic learning; Games; GraphoGame; GraphoGame learning analytics; GraphoGame teacher training service; GraphoWorld network; ICT-based literacy learning tools; Mobile handsets; Training; Zambia; computer games; educational institutions; home environment; home intervention group; in-service teacher training; information science education; learning materials; literacy; literacy instruction; literacy skills levels; local languages; mobile learning; mobile-based method; orientative workshop; professional aspects; reading instruction; rural Africa; rural Zambia; rural areas; school environment; scientifically validated pedagogical training; teacher training; word reading skills

English language teaching in Bangladesh today: Issues, outcomes and implications - Rahman, Mohammad Mosiur; Islam, Md Shaiful; Karim, Abdul; Chowdhury, Takad Ahmed; Rahman, Muhammad Mushfiqur; Seraj, Prodhan Mahbub Ibna; Singh, Manjet Kaur Mehar (Language Testing in Asia, 2019)
Given the significance of English in the global world, English language teaching in Bangladesh has become subject to a supreme concern in maintaining economic growth and developing a skilled workforce. In this article, several barriers have been discussed based on a critical analysis of published materials. This review article covers several key issues such as the status of English in the country; English in education policies; factors affecting the implementation of communicative language teaching curriculum, method, and materials in Bangladesh; validity of the current assessment and its washback effect on English language teaching in Bangladesh; and current situation of teachers’ professional development. The article concluded with language policy and planning implications for policymakers, curriculum and material developers, public exams’ test-setters, and future English teacher training programmes, keeping the overall development of ELT in Bangladesh in mind.
KerkoCite.ItemAlsoKnownAs: 10.1186/s40468-019-0085-8 10/gg398d 2339240:6DJW9B5P 2339240:T5V5WJQJ 2405685:EH4KT3RK 2405685:VUKTNAHY

Evaluations of situational judgement tests to assess non-academic attributes in selection - Patterson, Fiona; Ashworth, Victoria; Zibarras, Lara; Coan, Philippa; Kerrin, Maire; O’Neill, Paul (Medical Education, 2012)
Medical Education 2012: 46: 850–868 Objectives This paper presents a systematic review of the emerging international research evidence for the use of situational judgement tests (SJTs) for testing important non-academic attributes (such as empathy, integrity and resilience) in selection processes. Methods Several databases (e.g. MEDLINE, PsycINFO, Web of Science) were searched to retrieve empirical studies relating to SJTs published between 1990 and 2010. Personal contact with experts in the field was made to identify any unpublished research or work in progress to obtain the most current material. Finally, reference lists were checked to access other relevant journal articles and further research. All research studies were required to meet specific inclusion criteria selected by two independent reviewers. Results Over 1000 citations were identified during the initial literature search; following the review of abstracts, full-text copies of 76 articles were retrieved and evaluated. A total of 39 articles that adequately met the inclusion criteria were included in the final review. The research evidence shows that, compared with personality and IQ tests, SJTs have good levels of reliability, predictive validity and incremental validity for testing a range of professional attributes, such as empathy and integrity. Conclusions SJTs can be designed to test a broad range of non-academic constructs depending on the selection context. As a relatively low-fidelity assessment, SJTs are a cost-efficient methodology compared with high-fidelity assessments of non-academic attributes, such as those used in objective structured clinical examinations. In general, SJTs are found to demonstrate less adverse impact than IQ tests and are positively received by candidates. Further research is required to explore theoretical developments and the underlying construct validity of SJTs.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1365-2923.2012.04336.x shortDOI: 10/f37fc9 KerkoCite.ItemAlsoKnownAs: 10/f37fc9 2405685:2LTPTJHB 2405685:WDJGKHTC

The Effects of a Technology-Aided Learning Environment on the Improvement of a Primary Special Education School - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people's expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming '"learning" or "effective" schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers' functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed.
Publisher: Academic Journals KerkoCite.ItemAlsoKnownAs: 10.5897/ERR2015.2523 10.5897/err2015.2523 10/gjj9dr 2339240:ZXNUGEXT 2405685:SHM89EW9
Keywords: Academic Achievement; Assistant Principals; Attitude Measures; Case Studies; Cooperation; Educational Innovation; Educational Technology; Elementary Education; Elementary School Teachers; Foreign Countries; Observation; Parents; Principals; Qualitative Research; School Personnel; Semi Structured Interviews; Special Education; Statistical Analysis; Teaching Methods; Technology Uses in Education; ___working_potential_duplicate

The Effects of a Technology-Aided Learning Environment on the Improvement of a Primary Special Education School - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people's expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming '"learning" or "effective" schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers' functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed.
Publisher: Academic Journals KerkoCite.ItemAlsoKnownAs: 10.5897/ERR2015.2523 10.5897/err2015.2523 10/gjj9dr 2339240:ZXNUGEXT 2405685:SHM89EW9
Keywords: Academic Achievement; Assistant Principals; Attitude Measures; Case Studies; Cooperation; Educational Innovation; Educational Technology; Elementary Education; Elementary School Teachers; Foreign Countries; Observation; Parents; Principals; Qualitative Research; School Personnel; Semi Structured Interviews; Special Education; Statistical Analysis; Teaching Methods; Technology Uses in Education; ___working_potential_duplicate

M-learn lessons learnt: Bangladesh perspective - Imam, Zaki (QScience Proceedings, 2013)
M-learning is a form of distance learning in that it provides a communication tool( the mobile phone) to bridge the distance between the providing institution and the learners and facilitates 2-way (synchronous and asynchronous) interactivity between teacher and the learner (McWilliams et al, 2007). M-learning allows the remote teachers to stay in frequent contact with teacher educators, to ask questions and discuss issues as they adapt new teaching practices. This programme has been initiated by Ministry of Education upon requested by ADB, Manila to implement technology based training programme for reaching remote and disadvantaged areas. M learning has been piloted by teacher educators of Government Teachers’ Training College in one district (Barisal, located in the southern part of Bangladesh) and later extended to four districts to train teachers of remote schools of Patuakhali, Sandwip, Hatya and Thakurgaon districts. Regular 14 day and 5 day follow-up face-to-face inservice Continuing Professional Development (CPD) training was adapted as a two day face-to-face orientation, followed by a 6 week programme with regular conference calls to support classroom practices. Findings of the programme are very promising for adapting new practices. The CPD training by using mobile phone became very successful for increasing teachers and student’s competence level. Government of Bangladesh and Development Partners are very keen to maximize the use of technology in CPD for teachers especially for addressing female teachers and reaching training facilities to remote areas.
KerkoCite.ItemAlsoKnownAs: 10.5339/qproc.2013.mlearn.24 10/gj37jm 2339240:A9MNH3VF 2405685:DA3TGYS8

Learning from international experiences with interactive whiteboards - Hennessy, Sara; London, Laura (OECD, 2013)
This paper describes teacher strategies and experiences with interactive whiteboards (IWBs) and draws on the published research in this area to understand how a systemic approach to technology-based innovations in schools can contribute to quality education for all. It explores ways to support the cultural shift in teacher and learner roles that helps to integrate the technology effectively into classroom teaching. It begins by considering how the features of IWB technology might potentially be exploited in the primary or secondary school classroom to support subject teaching and learning. International experiences of implementing IWB programs are then described, mostly from the United Kingdom where integration efforts are the most prominent, and implications for future intervention efforts are examined. The review concludes by defining the organisational conditions for enhancing teacher commitment and thus the likelihood for successful change. In particular, the role of teacher professional development is foregrounded and characteristics of effective programmes are outlined. Some comments about the relative costs and benefits, and recommendations for policymakers, are made.
KerkoCite.ItemAlsoKnownAs: 2339240:TTB8Z79I 2405685:HQG3IHPW 6018420:4TZJWG3F

Evaluating the Implementation Fidelity of Technology Immersion and its Relationship with Student Achievement - Shapley, Kelly S.; Sheehan, Daniel; Maloney, Catherine; Caranikas-Walker, Fanny (The Journal of Technology, Learning and Assessment, 2010)
In a pilot study of the Technology Immersion model, high-need middle schools were “immersed” in technology by providing a laptop for each student and teacher, wireless Internet access, curricular and assessment resources, professional development, and technical and pedagogical support. This article examines the fidelity of model implementation and associations between implementation indicators and student achievement. Results across three years for 21 immersion schools show that the average levels of school support for Technology Immersion and teachers’ Classroom Immersion increased slightly, while the level of Student Access and Use declined. Implementation quality varied across schools and classrooms, with a quarter or less of schools and core-content classrooms reaching substantial implementation. Using hierarchical linear modeling, we found that teacher-level implementation components (Immersion Support, Classroom Immersion) were inconsistent and mostly not statistically significant predictors of student achievement, whereas students’ use of laptops outside of school for homework and learning games was the strongest implementation mediator of achievement.
KerkoCite.ItemAlsoKnownAs: 2129771:NJE58HBR 2405685:HMXQHGHR
Keywords: ⛔ No DOI found

Interactive White Boards in Preschool and Primary Education - Drigas, Athanasios; Papanastasiou, George (International Journal of Online and Biomedical Engineering (iJOE), 2014)
Technologies within the domain of interactive, remote and on line science which are extensively adopted in education’s everyday life are interactive whiteboards and related applications. Interactive whiteboards indicate positive effects on students’ learning and instructors' teaching, promoting whole class teaching. In this review-paper we cope with the studies that explore the integration of IWBs in preschool and primary education in the last decade (2004-2013). Research has shown that interactive whiteboards are able to keep students involved and foster their attention in every aspect of the curriculum, much easier than without it. This technology has proven its value added to students and teachers in different facets of teaching and learning, in literacy, in mathematics, in science, in physics, its impact on English Language Learners, on relations and learning, on the use of IWBs by kindergartners, professional development of teachers, pedagogical orchestration, classroom dialogue and pedagogic practice.
Number: 4 KerkoCite.ItemAlsoKnownAs: 10.3991/ijoe.v10i4.3754 2339240:K4FVSNGK 2405685:4IP459NY
Keywords: IWB; collaboration; e-learning; e-teaching; interactive; multimodal teaching

Factors determining digital divide in Ghana's basic schools - Quaicoe, James Sunney; Pata, Kai (2015 IST-Africa Conference, 2015)
This paper explores the concept of digital divide (DD) in Ghana’s basic schools in Sekondi-Takoradi Metropolis in Western Region. We tested the ICT culture variables as well as school location factor in respect to school’s digital divide. A survey sample contained 17 regional city schools from three different locations – central city in the region, towns away from the central city, and village schools. The survey instrument was developed with ten ICT culture variables. The variables in the instrument met the Cronbach’s Alpha threshold value of α = 0.70. Data was analysed with Descriptive statistics, Hierarchical Cluster analysis, Independent t-test, and Canonical discriminant analysis. We found that school location did not determine the schools DD, nonetheless the schools were digitally divided, – 2 clusters were found among schools. This DD was determined by certain ICT culture variables: Teacher’s ICT competences and the usage of ICT in Teacher’s professional practice were paramount.
KerkoCite.ItemAlsoKnownAs: 10.1109/istafrica.2015.7190518 10/ggn3wz 2339240:H83HTANQ 2405685:XZBJRR36

The effects of a technology-aided learning environment on the improvement of a primary special education school - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people’s expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming ‘learning’ or ‘effective’ schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers’ functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed. Key words: School development, technology, innovation, hearing impaired.
KerkoCite.ItemAlsoKnownAs: 10.5897/ERR2015.2523 2339240:9SHHNJCH 2405685:WQ7ZLZVW
Keywords: ___working_potential_duplicate

GIS in Education Planning: The Kenyan School Mapping Project - Mulaku, G.C.; Nyadimo, E. (Survey Review, 2011)
School mapping consists of the building of geospatial databases of educational, demographic and socioeconomic data for educational institutions in order to support educational planning and decision making. Such databases contain data such as the geographic location of schools, the numbers of existing schools of different levels in the public and private sectors, their capacities, physical condition and facilities, enrolment and the number of teachers and their attributes. Also often included are data on related natural features and infrastructure such as rivers, roads, economic and administrative centers, medical facilities, religious facilities, etc. This paper describes the Kenyan School Mapping Project, whose objective was to collect such data for all Kenyan learning institutions and to integrate them in a GIS database that could be queried to provide useful information for educational planners, other professional users and average citizens. Results show that at the time of the project, there were nearly 73000 learning institutions in Kenya, ranging from early childhood schools to universities; useful information products on important educational indicators such as schools distribution, enrolments, pupil-teacher ratios and gender parity indices have also been generated from GIS analysis of the data. These results have demonstrated the utility of the database for its stated purpose and therefore shown the project to be a useful model that can be emulated by other developing countries.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1179/003962611X13117748892155 KerkoCite.ItemAlsoKnownAs: 10.1179/003962611X13117748892155 2405685:HH3GP4V2 4042040:NJ6E8C3M
Keywords: EMIS; GIS; KENYA; SCHOOL MAPPING

10 principles to consider when introducing ICTs into remote, low-income educational environments - Trucano, Michael (World Bank Blogs, 2013)
there must be an I, a C, and a T here somewhere ... There are, broadly speaking, two strands of concurrent thinking that dominate discussions around the use of new technologies in education around the world. At one end of the continuum, talk is dominated by words like 'transformation'. The ...
Library Catalog: blogs.worldbank.org KerkoCite.ItemAlsoKnownAs: 2339240:5I5XNP44 2339240:7ENMXVAZ 2339240:7TDXW2WT 2339240:M7NFMPY5 2405685:23SM2GHY 2405685:2KLF59UJ 2405685:4QHLLY7H 2405685:BJSJWEMM 2405685:EJG6JBSL 2405685:EY7WAUHY 2405685:MDR3XLXP 2405685:N584ISNZ 2405685:RCHYAVL3 2405685:SVDWLWHS 2405685:XED3H9S7 4042040:MXSNKXZ5 4656463:P4BDEDD3 4656463:YXDWWIE2

A Study on Using Serious Games in Teaching German as a Foreign Language - Alyaz, Yunus; Spaniel-Weise, Dorothea; Gürsoy, Esim (Journal of Education and Learning, 2017)
The interest in Digital Game-Based Language Learning (DGBLL) has increased considerably in recent years although being a relatively new approach. Despite the interest that DGBLL took, the studies in the context of German as a Foreign Language (FL) are quite limited. Moreover, DGBLL in the Turkish context is not prevalent. Due to this gap in the literature, a research project was launched at a big state university in Turkey in 2014 to explore the potentials and limitations of DGBLL. The study focuses specifically on serious games for FL teaching and learning. The aim of the project, in addition to the promotion of linguistic skills of the learners, is to contribute to the development of professional qualifications of the future FL teachers. The present research aims to report on the pilot study of the project. A one group pre-test post-test research design was used in the study. Quantitative data was collected via two opinion questionnaires implemented at the beginning and at the end of the process as well as a receptive vocabulary test. Qualitative data was collected via semi-structuted interviews and game diaries that participants kept. Two serious games for German was selected and used with traditional dictation, transcription and reading comprehension activities. The results of an 11-week gaming activity indicated significant differences between pre- and post-tests in vocabulary. Additionaly, age was found to be an important factor that affects participants’ attitudes towards serious games. The results indicate that the participants found game activities useful for the development of other language skills.
KerkoCite.ItemAlsoKnownAs: 10.5539/jel.v6n3p250 2339240:ZT2EQPGY 2405685:8EG4FU28

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
EdTechHub.Source: 2129771:9IYKEUKJ shortDOI: 10/f8f6mc KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12123 10/f8f6mc 2129771:6YGVDBXS 2129771:9IYKEUKJ 2129771:BFWTG2BG 2129771:HX6DBG7W 2317526:3V7LV2NP 2339240:C6LDZSDW 2339240:GNBA7ZJI 2339240:WPK23R37 2339240:YYGY6J8F 2405685:7552P2EL 2405685:9I6F956M 2405685:J6HBWCZL 2405685:SZ2DB7K2 503888:U6FRZHMB
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets

Learning ecologies through a lens: Ontological, methodological and applicative issues. A systematic review of the literature - Sangrá, Albert; Raffaghelli, Juliana Elisa; Guitert‐Catasús, Montse (British Journal of Educational Technology, 2019)
The concept of learning ecologies emerged in a context of educational change. While the “learning ecologies” construct has offered a broad semantic space for characterizing innovative ways of learning, it is also true that its potential to promote innovative educational interventions may have been hindered by this same broadness. Based on this assumption, in this paper the authors carried out a systematic review of the literature on learning ecologies with the aim of analysing: (1) the varying definitions given to the concept, including the ontological perspective underlying the phenomena studied; (2) the methodological approaches adopted in studying the phenomenon; and (3) the applications of the research on this topic. Throughout this analysis, the authors attempt to describe the criticalities of the existing research, as well as the potential areas of development that align well with the theoretical/ontological issues, methodological approaches and educational applications. The authors selected and analysed 85 articles, which they then classified in a set of 20 categories defined by them on a theoretical basis. Moreover, in order to triangulate the manual coding, a bibliometric map was created showing the co-citation activity of the 85 papers. The emerging picture showed significant variability in the ontological definitions and methodological approaches. In spite of this richness, few educational applications currently exist, particularly with regard to technology-enhanced learning developments. Most research is observational, devoted to describing hybrid (digital and on-site) learning activities that bridge the gap between the school and social spaces. Furthermore, many of the studies relate to the field of secondary education, with fewer studies exploring adult learning and higher education. The studies dealing with professional development relate mostly to teachers’ continuing education. The authors conclude that the concept of learning ecologies could be used to address further experimental and design-based research leading to research applications if there is proper alignment between the ontological, methodological and applicative dimensions. The main potential of this strategy lies in the possibility of supporting learners by raising their awareness of their own learning ecologies, thereby empowering them and encouraging them to engage in agentic practices. This empowerment could help maintain and build new and better learning opportunities, which every learning ecology can incorporate, amidst the chaotic abundance that characterizes the digital society.
shortDOI: 10/gf5f7h KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12795 10/gf5f7h 2339240:B3XDZLNT 2405685:64NV5INX
Keywords: Reviewed

What Matters Most for Education Management Information Systems: A Framework Paper - Abdul-Hamid, Husein (World Bank Group, 2014)
KerkoCite.ItemAlsoKnownAs: 2339240:2Y2DWADG 2339240:5LA79R5Z 2339240:EZKRKLTS 2339240:F9REFA7S 2339240:M9MLNKW5 2339240:QWFNRS65 2339240:ULVY9AQR 2405685:9VTR62BA 2405685:BZZR4UPE 2405685:CDIF7BWM 2405685:F2H3C785 2405685:KVCFX5IC 2405685:TIVM2VGM 2405685:Z29BM6ES 4656463:5T27DWL5
Keywords: Academic Assessments; Access to Data; Access to Education; Access to Information; Adult Education; Annual School Census; Application Programming; Assessment Framework; Average Teacher Salaries; Basic Education; Basic Education Statistics; Best Practice; Business Intelligence; Care Providers; Class Sizes; Classroom; Classroom Learning; Classrooms; Client Countries; Communication Technology; Communications Technologies; Communications Technology; Completion Rates; Continuing Education; Curriculum; Data Analysis; Data Collection; Data Coverage; Data Gathering; Data Providers; Data Sharing; Data Sources; Data Systems; Data Warehouse; Decision Makers; Decision Making; Decision-Making; Demand for Education; Domain; Domains; Early Childhood; Early Childhood Development; Early Childhood Education; Educated Population; Education Budget; Education Data; Education Development; Education Institutions; Education Management; Education Management Systems; Education Outcomes; Education Planning; Education Policies; Education Policy; Education Providers; Education Services; Education Statistics; Education Strategy; Education System; Education Systems; Education Targets; Education Teachers; Education for All; Educational Development; Educational Expenditures; Educational Inputs; Educational Outcomes; Educational Planning; Educational Processes; Educational Quality; Educational Sciences; Educators; Enabling Environment; Enrollment Data; Enrollment Levels; Enrollment Rates; Enrollment Statistics; Equitable Education; Expert Opinion; Female Teachers; Financial Performance; Formal Education; Functionalities; Functionality; Gender Equality; Gender Equity; Gender Parity; Gender Parity Index; Girls; Global Education; Gross Enrollment; Gross Enrollment Ratio; High Quality Education; Human Resources; Improvement of Education; Information Gaps; Information System; Information Systems; Information Technology; Innovation